Porous loofah sponge meets bimetallic MOF: Synergistic effect for efficient tetracycline removal - Lei She; Yuan Zhao; Mei-Jin Li; Jing-Yi Zhao; Hao-Zheng Li; Jie Gao; Ya-Yang Tian; Lin-feng Chen; Zhi-Jun Zhang; Tao Chen (Biomass and Bioenergy, 2027)

Polystyrene nanoparticles impair endometrial decidualization in early pregnant mice via oxidative stress-driven autophagy suppression and ferroptosis induction - Li-Qing Wang; Qian-Feng Qiao; Huang-Nian You; Yi-bin Zheng; Xiao-Mei Wu; Wen-Jie Yu; Zeng Liu; Wen-Juan Song; Lin-Hong Zhang; Jia-Rui Hu; Xin-Yu Mao; Yong-Jiang Zhou (Food and Chemical Toxicology, 2026)

Nicotine-induced mitophagy in bronchial epithelial cells and MYST1 downregulation in cigarette smoke–exposed lungs: potential mechanisms of COPD progression - Kai Liu; Dongchuan Xu; Jie Zhao; Rubing Mo; Mei Lin; Chanyi He; Qi Lin; Tian Xie; Quanni Li; Yipeng Ding (Molecular Biology Reports, 2026)

Targeting EFEMP1 enhances chondrogenesis and inhibits hypertrophic differentiation in a spontaneous osteoarthritis mouse model - Yuhan Chang; Pei-Heng Jiang; Yung-Heng Hsu; Yu-Chih Lin; Chih-Chien Hu; Yi-Zhen Li; Steve Wen-Neng Ueng; Mei-Feng Chen (Journal of Molecular Medicine, 2026)

MiR-4327 targets TP53 to promote cervical cancer cell proliferation - Mei-Lin Chen; Chen-Yang Chu; Feng-Xian Zhang; Li-Pei Zhang; Ying Yang; Bai-Zhao Peng; Chuang-Hai Wu; Xiao-Mei Chen; Yan-Ting You; Bing-Ying Rong; Hiu Yee Kwan; Xiao-Shan Zhao; et al. (Functional & Integrative Genomics, 2026)
Cervical cancer is a leading cause of female malignancy worldwide. While microRNA-4327 (miR-4327) has been implicated as a potential oncogene, its functional role and molecular mechanisms in cervical cancer pathogenesis remain unclear. This study aimed to determine the oncogenic function of miR-4327 and elucidate its downstream regulatory mechanism in cervical cancer pathogenesis. We measured miR-4327 expression in clinical cervical cancer tissues and cell lines using quantitative real-time PCR (qRT-PCR). We then assessed its effects on proliferation, migration, invasion, and cell cycle progression through functional assays including cell counting kit-8 (CCK-8), colony formation, transwell, and flow cytometry. To evaluate tumor growth in vivo, we established a xenograft model in non-obese diabetic (NOD)-severe combined immune-deficient (scid) mice. Using bioinformatic analysis and luciferase reporter assays, we identified TP53 as a direct target of miR-4327 and further validated this regulatory relationship with gain- and loss-of-function experiments. We found that miR-4327 was significantly upregulated in cervical cancer and promoted malignant phenotypes such as proliferation, migration, invasion, and cell cycle progression in vitro. Consistent with this, overexpression of miR-4327 accelerated tumor growth in vivo. Mechanistically, we confirmed TP53 as a direct functional target of miR-4327. Knocking down TP53 phenocopied the oncogenic effects of miR-4327, while restoring TP53 expression rescued the tumor-promoting effects mediated by miR-4327. These findings reveal a novel miR-4327/TP53 regulatory axis and nominate miR-4327 as a potential therapeutic target for intervention.

Enhancing biocontrol efficacy against postharvest chili pepper soft rot via LuxS/AI−2-mediated activation of Lactobacillus paracasei WX322 - Liuyang Li; Yuze Zheng; Jinling Lin; Baitong Mei; Yifei Li; Honghai Li; Lanhua Yi (Postharvest Biology and Technology, 2026)

TBBPA facilitates splenic inflammation and pyroptosis by targeting HMGB1 - Fu-Wei Jiang; Jing-Han Lin; Jia-Xin Wang; Ming-Shan Chen; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Ming Lou; Zi-Yan Hu; Yi Zhao; Jin-Long Li (Journal of Environmental Sciences, 2026)

Advanced membrane modifications for reverse osmosis fouling mitigation: mechanistic insights and practical applications - Liu Yang; Fangbo Zhao; Peng Lin; Caixu Wang; Zhiguo Li; Wennan Liu; Ruofan Wang; Yushi Mei; Hee-Deung Park (Desalination, 2026)

Size matching between laccase and carrier via tunable diamine-derived flexible spacer arms for enhanced phenolic wastewater degradation - Jie Zhang; Yiqi Gong; Zhipeng Qin; Xinyi Liu; Jiao Yu; Tao Feng; Wan Zhang; Wenjing Lin; Kaiyue Kang; Xuemei Tan; Lin Zhuo; Ruiqi Wang; et al. (Journal of Water Process Engineering, 2026)

Process-aware SSA-Conv-PatchTST for robust multi-horizon aeration-demand forecasting in full-scale wastewater treatment plants - Ran Song; Xiaole Mei; Xinhua Jiang; Xuelei Ma; Muqier Wudan; Wenlong Bai; Hao Lin; Zhi Li; Shengbin Gao (Journal of Water Process Engineering, 2026)

Development of TM hypoallergenic enzymatic products with the potential to induce immune tolerance in Lateolabrax japonicus - Meng-Si Li; Qing-Mei Liu; Fei Xia; Su-Jie Huang; Shun-Xian Lin; Li-Qiang Zhong; Hao-Tian Zhang; Gui-Xia Chen; Guang-Ming Liu (Food Bioscience, 2026)

Thermal response analysis of permeable energy piles with different backfill materials under seepage conditions based on equivalent permeability characterization - Zhipeng Geng; Qiqi Wu; Jinli Lin; Xiang Li; Yongyi Li; Guoxiong Mei (Energy and Buildings, 2026)

A fish-skin-inspired wearable scale-ionogel composite for impact protection and motion sensing - Tianyu Xu; Zimu Li; Lin Mei; Hanshen Huang; Jie Tian; Zijian Mei; Shuting Liu; Xiaoming Liu; Xinglong Gong; Tianzhi Luo (Chemical Engineering Journal, 2026)

Scalable cancer cell-derived liposome capable of homologous tumor-homing to encapsulate near-infrared light-responsive drug delivery nanocomposites for enhanced combination therapy - Fang-Yi Hsu; Wen-Jyun Wang; Li-Ting Yang; Yi-Zi Chen; Ting-Chi Lo; Jia-Sin Chen; Wei-Lun Huang; Yen-Liang Li; Hidenobu Takahashi; Wen-Chun Hung; Chi-Wen Luo; Shu-Yi Lin; et al. (Chemical Engineering Journal, 2026)

Isotopic compositions reveal distinct roles of in-cloud and below-cloud scavenging in dissolved and particulate mercury in precipitation - Zixuan Wang; Tao Li; Hongming Cai; Mei Meng; Jiubin Chen; Lin Du; Jiebo Zhen; Ping Du; Yan Wang (Atmospheric Environment, 2026)

Advancing startup control procedures for enhanced reduction of persistent organic pollutant emissions from municipal solid waste incinerators - Nicholas Kiprotich Cheruiyot; Cindy Soo Yun Tan; Hsi-Hsien Yang; Kuan-Hsien Li; Syeda Seemab Naqvi; Mei-Jou Lu; Guo-Ping Chang-Chien; Lin-Chi Wang (Waste Management, 2026)

Chondroitin sulfate: an environmentally friendly immune inducer enhanceing plant resistance to potato virus X and tobacco mosaic virus - Cui-Hong Hao; Wei Xu; Tian-Qi Liang; Yun-Mei Li; Yi-Lin Guan; Ru-Xin Li; Dan-Ya Ju; Chun-E Peng; Li-Zeng Peng; Qing-Bin Wang (Physiological and Molecular Plant Pathology, 2026)

Sustainable enhancement of rheological properties of asphalt: A strategy for utilizing recycled lead and zinc tailings - Huaxin Deng; Hang Lin; Yinfei Du; Huanhuan Mei; Jiangteng Li; Fenghua Nie (Minerals Engineering, 2026)

Electrochemical strategies for efficient PFAS removal from water: Mechanisms, performance, and sustainability perspectives - Kaini Peng; Jiale Lin; Mei Chen; Junjian Zheng; Yang Li; Liang Tang (Journal of Hazardous Materials, 2026)

Permafrost degradation amplifies infrastructure-related inequalities across the Qinghai-Tibet Plateau - Xinlong Du; Chunling Zhang; Yunjie Jia; Yuguo Wei; Jinyue Song; Mei Mu; Xiaoqing Peng; Zongxing Li; Peng Zhang; Lin Liu; Zhuoxuan Xia; Rongkun Liu; et al. (Global Environmental Change, 2026)

Unlocking collagen-derived novel antioxidant peptides from by-product bones of silver carp: label-free peptidomic discovery, bioinformatics-aided mechanistic elucidation, and cytoprotective effects against oxidative damage - Jin Zhang; Feng Lin; Yimeng Mei; Ruoyu Xie; Jiaxin Chen; Jun Hu; Hongying Du; Guijie Hao; Shuangxi Li; Wenxuan Chen (Food Research International, 2026)

Multi-omics Analysis Reveals the Protection of a Quadruple Probiotic Mixture in Experimental Autoimmune Hepatitis - Yu Chen; Shuhui Wang; Anzhuo Chen; Zhuoying Lin; Han Wang; Wanneng Li; Jun Liu; Jia Yao; Dean Tian; Yu Lei; Mei Liu (Probiotics and Antimicrobial Proteins, 2026)

Poricoic acid A administered during DSS exposure attenuates acute colitis in mice and is accompanied by barrier-associated changes and endpoint fecal microbiota shifts - Mei Wang; Kunkun Zhang; Danli Wang; Mingtao Cao; Rong Yong; Xiangqian Li; Wenyi Chen; Chengcheng Peng; Jiale Chang; Lu Fang; Feiyang Zhou; Yuyue Wan; et al. (Journal of Natural Medicines, 2026)

Apigenin in TMG inhibits colorectal tumorigenesis by targeting GSK3β/APC/β-catenin signaling pathway - Mei Li; Wei Wang; Renjing Lin; Fan Hu; Chongsi Xu; Biao Xie (In Vitro Cellular & Developmental Biology - Animal, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Dimeric 2-(2-phenethyl)chromones from agarwood of Aquilaria malaccensis - Wei Li; Xian-Yun Yan; Hao Wang; Li Yang; Sheng-Zhuo Huang; Jun Zeng; Fei Wu; Guang-Ying Chen; Wen-Li Mei; Lin-Fu Liang; Hao-Fu Dai; Yong-Min Zhang (Phytochemistry, 2026)

Inhibitory effects of fruit powders on heterocyclic amine formation in charcoal-grilled pork: A comparative study of application methods and development of a functional barbecue sauce spray - Mei-Ling Li; Yu-Shun Lin; Pei-Yu Wu; Ling-Hsuan Chang; Shang-Ming Huang; Kuo-Chiang Hsu (Food Research International, 2026)

Recombinant bovine αs1-casein as an enhanced precursor for sleep-promoting peptides: A structural, peptidomic, and molecular docking study - Long Pan; Lin-Lin Ding; Meng-Jia Song; Xiang-Li Mu; Ai-Mei Liao; Yin-Chen Hou; Ji-Hong Huang; Guang-Hai Yu (Food Bioscience, 2026)

Simulated freeze–thaw cycles restructure plastisphere microbiomes and functional gene co-occurrence networks in alpine lake sediment microcosms - Li Naying; Zhong Bo; Wu Wei-Min; Liu Xin; Liu Ruixi; Mei Xintong; Wang Xiaofeng; Zhou Li; Yi Shaoliang; Lin Honghui; He Yixin (Environmental Pollution, 2026)

Integrated electrochemistry enables deep decontamination and resource recovery of rare earth wastewater - Kaibo Hu; Luyu Mei; Chao Wang; Hong Liu; Jiuyang Lin; Yinhua Wan; Xuewei Li (Chemical Engineering Journal, 2026)

Efficacy and Mechanisms of Combined Central-Peripheral Magnetic Stimulation on Prefrontal-Sensorimotor Cortex Connectivity in Post-Stroke Dysphagia after Supratentorial Stroke: A Randomized, Single-Blind, Parallel-Controlled Trial - Zirui Luo; Zhiying Zhu; Yujue Wang; Na Su; Yajing Xue; Wanqi Zhang; Wei Liao; Yaoyao You; Lin Ling; Mei Li; Junjie Liang; Zulin Dou; et al. (Translational Stroke Research, 2026)

Infection risks associated with b/tsDMARDs in rheumatoid arthritis: a systematic review and network meta-analysis - Xue-Mei Zhang; Li Liu; Yi-Dan Yan; Zai-Li Zhang; Ke-Jia Le; Yang-Xi Liu; Xiao-Jun Ni; Liang-Jing Lu; Guo-Hua Zhou; Zhi-Chun Gu; Jia Li; Hou-Wen Lin (European Journal of Clinical Pharmacology, 2026)

Three new diterpenoids from the aerial parts of Callicarpa macrophylla - Liang Gou; Rong-Shuai Li; Jian-Lin Lai; Yan-Mei Ning; Xue-Ting Ji; Xiong Qiu; Chao Peng; Xiao-Li Li; Xing-Jie Zhang; Wei-Lie Xiao (Natural Product Research, 2026)

Individual and joint association between per- and polyfluoroalkyl substances and skeletal muscle among 6-9 years old children in China - Xue-Mei Liao; Li-Zi Lin; Wan-Ting He; Yun-Ting Zhang; Si-Hui Guo; Shu-Jun Liang; Zhen Hong; Zhe-Qing Zhang; Guang-Hui Dong; Qin-Zhi Wei (International Journal of Hygiene and Environmental Health, 2026)

A food-derived octapeptide SRGQIEEL from yellow field pea protein hydrolysates inhibits xanthine oxidase via a tunnel-occlusion-like mechanism - Mei-Ling Li; Cheng-Hong Hsieh; Pei-Yu Wu; Shang-Ming Huang; Chung-Yu Tang; Yu-Shun Lin; Kuo-Chiang Hsu (Food Bioscience, 2026)

Sulfur-doped MgFe2O4 with oxygen vacancies: Unveiling the synergistic role of electron transfer pathways in boosting radical generation for efficient peroxymonosulfate activation - Lin Wang; Shoudie Yue; Mengyang Li; Mei Wang; Wenqi Wang; Jirong Yu; Shaolong Wang; Baojun Liu (Chemical Engineering Journal, 2026)

Heteronemin suppresses chemoresistant oral squamous cell carcinoma cells through ROS-mediated apoptosis and cuproptosis-associated mitochondrial stress - Chiung-Wei Huang; Fan-Li Lin; Chun-Feng Chang; Hsiao-Hsuan Huang; Wan-Ju Wu; Hui-Min Chang; Mei-Ying Lin; Jue-Liang Hsu; Shih-Ya Hung; Chien Hsing Lee (Apoptosis, 2026)

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

Bioactive coumarins and chromones with anti-neuroinflammatory effect from Gerbera piloselloides - Cong Zhang; Kuan Lin; Qing-Qin He; Hao Gong; Li-Juan Hu; Mei Zhou; Shi Chen; Wei Liu; Xian-Sheng Ye; Xi-Ji Shu (Phytochemistry Letters, 2026)

Functional characterization of chemosensory proteins in Pharsalia antennata with special emphasis on the roles of CSP2 orthologs in pheromone detection - Fu-Peng Li; Xiao-Rong Xiong; Zi-Hui Liu; Zi-Hao Long; Lin-Mei Pu; Nai-Yong Liu (Insect Biochemistry and Molecular Biology, 2026)

Potential structure-immunostimulatory activity relationship of Tartary buckwheat sprout pectic polysaccharides: Influences of molecular mass and esterification degree - Bo Li; Lin Zhang; Ding-Tao Wu; Qin Yuan; Shengpeng Wang; Mao-Ling Tan; Mei-Lin Feng; Yi-Chen Hu; Liang Zou; Zi-Peng Wang; Ya-Nan Cao; Jing-Wei Huang (Food Research International, 2026)

A dual-functional fluorescent sensor based on a single soybean-derived carbon dots for discrimination and quantification of tetracyclines in food - Xin Lin; Jiaqi Wang; Meiqi Xia; Shuang Li; Yixin Xu; Jingyi Sun; Han Leng; Tianqun Song; Yanzhi Xing; Mei Yang (Food Chemistry, 2026)

Hyaluronic acid-based supramolecular peptide-drug conjugate prodrug nanosystems for precise multiple myeloma therapy - Xiangyu Deng; Qili Huang; Li Cao; Ran Luo; Wenyan Wang; Hongzhong Chen; Chendi Ding; Lina Su; Lin Mei (Carbohydrate Polymers, 2026)

Corrigendum to “Hellebrigenin induces cell cycle arrest and apoptosis in human hepatocellular carcinoma HepG2 cells through inhibition of Akt” [Chemico. Biol. Interact. 219 (2014) 184-194] - Li-Juan Deng; Li-Ping Hu; Qun-Long Peng; Xiao-Lin Yang; Liang-Liang Bai; Anita Yiu; Yong Li; Hai-Yan Tian; Wen-Cai Ye; Dong-Mei Zhang (Chemico-Biological Interactions, 2026)

ErbB4 in the Dorsolateral Prefrontal Cortex is Required for Sensory Gating and Working Memory in Monkey - Minzhe Yang; Yingying Han; Hongfei Zhang; Chaolin Ma; Lin Mei; Baoming Li (Neuroscience Bulletin, 2026)

Shorter to be effective: subanesthetic-dose ketamine infusion reduces the global and regional path length of brain functional connectivity in patients with treatment-resistant depression and suicidal ideation - Wei-Chen Lin; Li-Kai Cheng; Tung-Ping Su; Li-Fen Chen; Pei-Chi Tu; Cheng-Ta Li; Ya-Mei Bai; Shih-Jen Tsai; Mu-Hong Chen (Psychopharmacology, 2026)

Endophyte-engineered plant immunity: A post-GMO strategy for programmable crop defense - Fan Zhang; Jing Zheng; Xinyun Xie; Mengru Tang; Hongyang Li; Linyin Zuo; Lu Zheng; Hao Liu; Junbin Huang; Zhinan Mei; Xiao-Lin Chen (Molecular Plant, 2026)

Microplastic pollution enhances methane emissions from remote mountainous lakes via plastisphere-mediated microbial processes - Naying Li; Bo Zhong; Wei-Min Wu; Xintong Mei; Ruixi Liu; Xin Liu; Xianxiang Li; Rehman Abdul; Shaoliang Yi; Li Zhou; Honghui Lin; Xiaofeng Wang; et al. (Journal of Environmental Sciences, 2026)

Formaldehyde activates the RUNX1–ISX axis to promote leukemic reprogramming, a pathway associated with poor prognosis in pediatric B-ALL - Pei-Chin Lin; Li-Ting Wang; Li-Heng Ye; Pin-Ying Tseng; Pei-Hsien Huang; Wan-Yi Hsu; Yu-Mei Liao; Shyh-Shin Chiou; Shih-Hsien Hsu (Environmental Pollution, 2026)

Building a yeast cell factory for green biomanufacturing of (R)-(+)-γ-decalactone: A natural peach-like aroma compound - Yizi Yu; Kaifeng Wang; Tao Sun; Shushu Li; Ying Zhou; Mei-Li Sun; Lu Lin; Rodrigo Ledesma-Amaro; Xiao-Jun Ji (Chemical Engineering Journal, 2026)

Sinomenine ameliorates experimental autoimmune neuritis by suppressing pro-inflammatory immune components and restoring immune balance - Yan-Mei Gong; Zhen-Lin Liu; Si-Miao Li; Yi-Fan Wei; Guo-Hui Gao; Rui-Qi Xu; Xue-Min Li; Yu-Dong Liu; Rui-Sheng Duan; Ying Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

An Enzymatic Recombinase Amplification Coupled Lateral Flow Assay for Rapid, Visual, and Cost-Effective Detection of Bordetella pertussis - Piaoting Wen; Jian Liu; Mingqi Jiao; Hangxi Liu; Mei Lin; Sheping Zhang; Jun He; Ziyi Li; Changhui Xiao; Zhongliang Deng (Current Microbiology, 2026)

AI-driven discovery of natural product-derived FAK1 inhibitors for idiopathic pulmonary fibrosis - Xing-Yi Chen; Mei-Hong Lu; Bin Li; Ya Zhou; Li Liu; Hao Yang; Qiu-Yu Wang; Lin Chang; Yu-Lan Zhao; Dong-Mei Wang; Bin Li; Ben-Rong Mu (Molecular Diversity, 2026)

Engineering strategies for the biosynthesis of rare sugars in microbial cell factories - Heming Xu; Ran Lu; Mei-Li Sun; Lu Lin; Kaifeng Wang; Xiao-Jun Ji (World Journal of Microbiology and Biotechnology, 2026)

MnO2-functionalized membrane with enhanced demulsification and antifouling performance for stable oil-in-water emulsion separation - Sudong Yang; Zhiying He; Mei Zhu; Junjie Zheng; Yixuan Kuang; Hongyi Li; Xueting Yuan; Qing Xu; Qian Zhang; Peng Zhao; Jianmin Luo; Lin Chen (Journal of Environmental Chemical Engineering, 2026)

Dark sky protection in high-density urban fringe areas: Site suitability assessment for dark sky parks and light environment optimization strategies—a case study of Guangzhou - Benyan Jiang; Kailing Xu; Zihao Zheng; Jianjun Li; Hongguang Wang; Lin Mei (Journal of Environmental Management, 2026)

Fermented red quinoa (FRQ) effectively mitigates chronic alcohol-induced cognitive impairment and hepatic steatosis through multi-mechanistic pathways - Zi-Han Lin; Zhaohui Wang; FenFen Wei; Xinyao Zhu; Junwei Ma; Yan Wu; Song-Mei Chen; Li-Hua Song (Food Research International, 2026)

CircRNA_02540 alleviated the migration and ligament differentiation capacities of SM-MSCs suppressed by chronic inflammation via regulating miR-203a-3p/ZIC1 pathway - Yingzhao Liu; Wanwan Shao; Weiliang Miao; Mei Li; Yaofa Lin (Journal of Molecular Histology, 2026)

Isolation and biological evaluation of a novel steroid from Sagina japonica (Sw. ex Steud.) Ohwi - Jun-Hong Liu; Qian-Lian Yin; Xue Li; Mei Qing Zhang; Lin Guo Zou; Xin Jian Song; Li Jiang; Chun Hua Liu; Yong Jun Li (Natural Product Research, 2026)

cGAS-STING activation mediated by FAM83H-AS1/HMGB1 elicits NF-κB-dependent immune evasion in breast cancer - Zhi-Mei Liang; Lili Lin; Shu-Rong Li; Xin-Yu Ma; Wenda Zhang; Na-Na Li; Zheng-Hao Lai; Guorun Liang; Wei Zhao; Yiming Zhao; Man-Li Luo (Science Bulletin, 2026)

Dietary silymarin improves gut–liver health by enhancing intestinal barrier integrity and modulating TLR4/NF-κB and NLRP3-mediated inflammatory responses in Aeromonas hydrophila–infected grass carp - Feng Jia; Li Wei; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Hong-Yun Zhang; Xiao-Wan Jin; Hong-Mei Ren; Xiao-Qiu Zhou; Lin Feng (Fish & Shellfish Immunology, 2026)

Freeze–thaw cycles restructure PET microplastics in sediments into new habitat of microbial carbon metabolism - Naying Li; Bo Zhong; Xin Liu; Wei-Min Wu; Xintong Mei; Ruixi Liu; Li Zhou; Honghui Lin; Shaoliang Yi; Yixin He (Chemical Engineering Journal, 2026)

3D-printing of hierarchical porous monoliths using emulsion gels stabilized by lignin-containing cellulose nanofibrils for thermal insulation - Chuhang Liu; Xiaojie Shi; Bo Lin; Zekun Song; Feng jiang; Mei-Chun Li; Chaozheng Liu; Changtong Mei (Carbohydrate Polymers, 2026)

Alpha-ketoglutarate restores oral epithelial homeostasis via FOXM1-mediated cell cycle regulation - Yuan Wang; Yimeng Cai; Qi Yin; Shuqin Cao; Yuyu Li; Yuhan Li; Qiwen Li; Qian Wang; Pochun Lin; Li Mei; Malcolm Xing; Leixiao Yu; et al. (Science China Life Sciences, 2026)

Soybean Hyperspectral Leaf Area Index (LAI) Estimation Based On Soil-vegetation Separation Algorithm and Derivative Spectroscopy - Nai-ning Zhong; Yu-lin Liu; Yi-zheng Zhao; Yi-xuan Mei; Hao-lin Shen; Xin-Zhou Lei; Yu-ning Wu; Juan-li Ju; Youzhen Xiang (Journal of Soil Science and Plant Nutrition, 2026)

Short-, medium-, and long-chain chlorinated paraffins in sediments from the Pearl River Delta, China: Occurrence, sources, and risks - Fei-Xiang Xie; Yu-Fang Huang; Yong-Hong Zhang; Ya-Hui Xue; Run-Lin Chen; Xiao-Mei Huang; Hong-De Shi; Jia-Hui Huang; Hui-Ru Li (Science of The Total Environment, 2026)

Adjuvant-metal-ion-chelating PTEN mRNA with cell-membrane-coating augments the immune sensitivity for precise cancer immunotherapy - Mengyu Guo; Jin-Cheng Guo; Haodong Yao; Fene Gao; Lina Zhao; Lu Cai; Xuan Fan; Lin Bao; Xin Li; Xiaoyu Zhang; Mingdi Hu; Jie Mei; et al. (Science Bulletin, 2026)

Imprinting silica membranes with perpendicular mesochannels by monomicelle oriented assembly for selective adsorption of iodide ions - Xiaoxiao Chen; Xudong Zheng; Xi Zhang; Guomeng Li; Jingbo Sun; Lin Guo; Jinfeng Mei; Zhongyu Li (Process Safety and Environmental Protection, 2026)

Preparation of fluorescent wood based on a novel flavonoid skeleton fluorescent probe for naked eye detection of dichloromethane, trichloromethane, and carbon tetrachloride - Xue Mei; Qingmao Long; Aijiao Lu; Feng Wang; Xiaojia Zhu; Yanfei Lin; Xijuan Chai; Lianpeng Zhang; Li Liu; Guanben Du (Journal of Environmental Chemical Engineering, 2026)

Mercury isotope perspectives on vegetation-enhanced nickel mobilization and migration during laterite formation - Ruo-Lin Liu; Martin Yan Hei Li; Run-Sheng Yin; Mei-Fu Zhou; Jun-Hong Zhao (Geochimica et Cosmochimica Acta, 2026)

Energy-saving and fire/water-resistant recyclable aerogel coatings for thermal-insulating polyurethane foam - Cong-Mei Lin; Xue-Lian Chen; Fu-Rong Zeng; Li-Xiao Hao; Yu-Shi Wen; Bing-Ru Zhang; Bo-Wen Liu; Lin Zhang; Hai-Bo Zhao (Chemical Engineering Journal, 2026)

Targeted photodynamic therapy for multispecies dental biofilms using liposome encapsulated p-Toluquinone - Chen Liang; Yongli Li; Zuan-Tao Lin; Zhilong Wang; Ya He; Yan Dong; Zihan Ran; Sophia Zhang; Ying Zhao; Songling Wang; Mei X. Wu (Chemical Engineering Journal, 2026)

Defect passivation with Pb for high-performance Sb2S3 solar cells via vapor transport deposition - Gan Huang; Xin-Yi Cai; Hu Li; Jin-Rui Cai; Ying-Sen Xia; Zhi-Ping Huang; Li-Mei Lin; Fu-Bao Gong; Shui-Yuan Chen; Gui-Lin Chen (Chemical Engineering Journal, 2026)

Boron nitride nanosheets via arginine-assisted embedded with phosphomolybdic acid as pesticide carriers for visualization in pest control - Li Hao; Minyan Zhou; Jialin Zeng; Jiechun Lin; Lan Hua; Ziting Yin; Mei Guan; Qiangcheng Zheng; Hongjun Zhou; Xinhua Zhou (Chemical Engineering Journal, 2026)

Engineering phototrophic cyanobacteria as a robust platform for production of plant-derived bioactive terpenoids - Hui-Cheng Feng; Chun-Lin Tan; Xiang-Mei Zheng; Xin Yu; Jonathan Gershenzon; Sheng-Hong Li; Yan Liu (Chemical Engineering Journal, 2026)

Regulation of grain protein content by the amino acid permease gene OsAAP4 in rice - Ming-Xin Li; Feng-Lin Huang; Jin-Hong Lin; Jia-Yi Qu; Guo-Feng Wan; Gen-Cai Song; Jing Zhao; Yan Peng; Zhen-Ning Teng; Ling Liu; Cheng Zheng; Hou-Xiong Wu; et al. (Theoretical and Applied Genetics, 2026)

Intercropping reduces soil erosion, improves soil conditions, and increases productivity of a Camellia oleifera plantation - Zeyao Zhao; Lin Chen; Wanwan He; Wenjun Xie; Byron B. Lamont; Longsheng Chen; Li Mei; Zhaogui Yan (Plant and Soil, 2026)

Eight new dammarane-type triterpenoid saponins from Gynostemma pentaphyllum - Gang Li; Guang Yang; Xiao-juan Chen; Peng-xin Lu; Hai-zhen Liang; Mei-yan Wang; Jie Zhang; Bao-lin Guo; Bai-ping Ma (Natural Product Research, 2026)

Optical properties of dissolved organic matter play pivotal roles in mediating trace metal forms in a mangrove-dominated tidal estuary - Keisuke Nakayama; Meng-Chi Hung; Chih-Yu Chiu; Sen-Lin Tang; Mei-Li Hsueh; Chin-Ching Wu; I-Hao Hung; Ya-Hsin Liu; Jeng-Wei Tsai (Marine Pollution Bulletin, 2026)

Optimising light intensity and ammonium enrichment enhances ex-situ growth and survival of the cultured boring Giant clam, Tridacna crocea - Li Keat Lee; Teresa S. Tay; H.R. Samuel Lee; K.E. Kayden Tong; M.Y. Beryl Chean; Yuchen Sun; Mei Lin Neo (Aquaculture, 2026)

Acroeremophilanes A–I, eremophilane-type sesquiterpenoids from the Sinomenium acutum-derived symbiotic fungus Acrocalymma cycadis - Li-Bin Lin; Xue Cao; Wei Shi; Dan Shen; Mei-Niu Wang; Jing-Yu Wang; Jia-Hao Ning; Jia-Yao Hu; Dong-Zhu Duan; Xiao-Ling Wang; Jian Xiao (Phytochemistry, 2026)

Eight previously undescribed flavonoids and four previously undescribed bibenzyls from Macaranga kurzii and their potential antiviral activities - Yan-Zi Ma; Ding-Cheng Zhang; Liu Yang; Xue-Wen Wu; Bo Li; Muhammad Aurang Zeb; Yuan-Lin Kong; Xue-Mei Zhou; Wei-Lie Xiao; Chang-Bo Zheng; Xiao-Li Li (Phytochemistry, 2026)

Photo-responsive imprinted cellulose nanocrystalline aerogels for selective terbium recovery and controlled desorption - Youming Zhu; Xudong Zheng; Jingbo Sun; Lin Guo; Xinmiao Pan; Xiang Gu; Xuan Ma; Jinfeng Mei; Zhongyu Li (Journal of Cleaner Production, 2026)

Distinct links between climate warming, mariculture activities, and coastal benthic ecosystem change - Yong Xu; Jixing Sui; Lin Ma; Jinbao Wang; Qi Kou; Zhibin Gan; Lin Gong; Mei Yang; Qingxi Han; Xinzheng Li; Dong Dong (Journal of Environmental Management, 2026)

Dibifree, a dietary phytomix, improves glycemic control and adiposity via modulation of the gut–pancreas–adipose–immune axis in type 2 diabetes - Tzu-Yi Huang; Niann-Tzyy Dai; Hsiu-Jung Liao; Ly Hien Doan; Tai-Shan Cheng; Wen-Yu Hsieh; I-Hsuan Lin; Yu-Tang Huang; Chia-Ching Liaw; Hsiao-Sheng Liu; Wei-Ming Cheng; Chun-Li Su; et al. (Food Research International, 2026)

Machine learning-assisted sensor array based on enhanced dual enzyme-like activities of Fe SAzymes modulated via Pluronic surfactant for multi-category perfluoroalkyl intelligent recognition and quantification - Wen-Cai Jiang; Xiao-Mei Li; Jia-Hao Cheng; Li-Yao Xu; Ri-Za He; Gui-Lin Zou; Zhi-Bo Hou; Yan Zhao; Guo-Qi Zhang (Chemical Engineering Journal, 2026)

An extra-large panicle gene ELP1 from wild rice Oryza officinalis increases grain number and grain yield - Jiachen Ma; Mei Li; Yanan Lin; Jinjin Lian; Yizhengnan Zhu; Jing Yang; Wenfan Hu; Luyi Zhang; Shuting Li; Weilin Zhang (Theoretical and Applied Genetics, 2026)

Soil nutrient heterogeneity induces foraging behavior but does not improve overall growth performance in six bamboo species - Lin-Xuan He; Li-Li Zheng; Jia-Yu Zhang; Xiao-Mei Zhang; Jing-Pin Lei; Mai-He Li; Fei-Hai Yu (Plant and Soil, 2026)

A1-Reactive Astrocytes in the Posterior Part of Paraventricular Thalamic Nucleus Are Involved in Pain Modulation in Mice - Han-Xue Sun; Zhong-Yi Liu; Jia-Ni Li; Liu-Jie Zhao; Xue-Mei Wu; Chu-Han Liu; Jie Hong; Ke-Hua Zhu; Feng-Ling Wu; Si-Hai Chen; Yu-Lin Dong; Yun-Qing Li (Molecular Neurobiology, 2026)

CT-HiffNet: A contour-texture hierarchical feature fusion network for cropland field parcel extraction from high-resolution remote sensing images - Hao Wu; Junyang Xie; Weihao Deng; Anqi Lin; Abdul Rashid Mohamed Shariff; Shamshodbek Akmalov; Wenbin Wu; Zhaoliang Li; Qiangyi Yu; Qunming Wang; Jian Zhang; Xin Mei; et al. (Computers and Electronics in Agriculture, 2025)

Two new 2-(2-phenylethyl)chromone dimers from agarwood of Aquilaria malaccensis - Lin Zhang; Wei Li; Hao Wang; Jun Zeng; Wen-Hua Dong; Bei Jiang; Jing-Zhe Yuan; Fei Wu; Wen-Li Mei; Hao-Fu Dai (Phytochemistry Letters, 2025)

A unified framework for predicting vertical bearing capacity of fully embedded pipes/tunnels in clay seabed based on the undrained failure mechanisms - Yu Zhao; Xing-Tao Lin; Wei-Jian Li; Jun-Chen Zhang; Zhi-Yao Tian; Quan-Mei Gong (Ocean Engineering, 2025)

Clastic record from Northern Tethyan Himalaya: Implication for the initial India-Asian collision in the western Yarlung-Zangpo suture zone, South Tibet - Xu-dong Guo; Lin Ding; Fu-long Cai; Gui-zhen Guo; Xiao-yan Xu; Peng Han; Chang-jun Gu; Mei-yu Liu; Xiang-li Ding; Xu Liu; Xin-lei Li; Deng Zeng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Micro-ecosystem of plastisphere in high-altitude lake: Hotspots of anaerobic carbon cycle distinct from sediments - Naying Li; Bo Zhong; Xin Liu; Wei-Min Wu; Xintong Mei; Zao Yang; Abdul Rehman; Li Zhou; Honghui Lin; Yixin He (Journal of Hazardous Materials, 2025)

Machine learning intelligently selects feature values to construct a sensor array based on tri-functional Mn-doped covalent organic polymer nanozymes for identifying flavonoid compounds - Guo-Qi Zhang; Wen-Cai Jiang; Xiao-Mei Li; Ren-Jie Li; Yi Feng; Ri-Ge Li Nai; Hui-Lin Cheng; Zhi-Bo Hou; Xiao-Jun Luo; Yan Zhao (Food Chemistry, 2025)

Construction of 4,5 ′- diaminodibenzo-18-crown-6-grafted graphene cellulose composite aerogel for efficient and selective adsorption of Cs+ from acidic aqueous solution - Lin Guo; Xudong Zheng; Xuan Ma; Xiang Gu; Xinmao Pan; Jinfeng Mei; Zhongyu Li (Environmental Research, 2025)

Engineering NK cell membrane-camouflaged copper-BODIPY nanoassembly to synergize dual-phototherapy and cuproptosis for enhanced antitumor immunity - Xuya Yu; Yushi Zhang; Zhuona Rong; Xueping Li; Lingpeng Luo; Lu Zhang; Liyu Sun; Yayue Liu; Wen Li; Lin Mei; Feng Lv; Xiaocong Pang; et al. (Chemical Engineering Journal, 2025)

Self-adaptive auditory perceptual system for voice instruction recognition powered by triboelectric acoustic sensor - Si Yuan Zhou; Shi Han Wang; Jing Zhang; Lin Feng Wu; Wei Sheng Wang; Bei Chen Gong; Jia Kang Di; Xiang Mei Duan; Hua Ping Wu; Li Qiang Zhu (Chemical Engineering Journal, 2025)

Bletilla striata polysaccharide protects against UVA-induced skin damage by activating Nrf2/HO-1 signaling and inhibiting ferroptosis - Mei Wang; Yiyue Zhang; Jingmiao Jiao; Charareh Pourzand; Lin Yi; Chenshi Lin; Jianzhou Cui; Zhenqing Zhang; Julia Li Zhong (Carbohydrate Polymers, 2025)

Improving stability and UV protection properties of phycocyanin nanoparticle-based Pickering emulgels via amorphous cationic starch complexation - Yacheng Hao; Jiahao Mei; Dongfang Ling; Zhe Zhang; Sai Li; Zhiyong Gong; Xin Liu; Mingfeng Xu; Yilin Lin; Rongrong Yu (Carbohydrate Polymers, 2025)

Pluvial flood warnings in a tidally influenced basin enhanced by rainfall–tide compound indicators: Taipei case study - Mei-Ying Lin; Wen-Yih Sun; Huei-Syuan Fu; Chih-Hsin Chang; Wei-Bo Chen; Chieh-Ju Wang; Hsuan-Wei Wang; Yi-Chiang Yu; Yen-Wei Li (Stochastic Environmental Research and Risk Assessment, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Chlorholones A−H, bioactive sesquiterpenoids with diverse skeletons from Chloranthus holostegius - Zhao-Chun Zhan; Ting Lu; Hai-Shan Zhang; Mei-Ting Weng; Hui-hui Zhu; Qiang Lin; Hai-Yue Zhao; Yue-Hao Huang; Tian-Yuan Wu; Miao Wang; Yao-Lan Li; Yi-Wen Zhang; et al. (Phytochemistry, 2025)

Smoldering heterogeneous oily sludge: Key influencing factors - Yi Lin; Zehua Luo; Fuli Li; Chih-Huang Weng; Yanru Hao; Na Liu; Mei Hong (Journal of Cleaner Production, 2025)

Ethylene-responsive factor HvERF72 regulates starch synthesis and B-type starch granules initiation in barley - Gaozong Zhou; Jinjin Ding; Yulong Li; Qiang Xu; Yazhou Zhang; Huaping Tang; Pengfei Qi; Mei Deng; Jian Ma; Guoyue Chen; Jirui Wang; Na Lin; et al. (Carbohydrate Polymers, 2025)

Fermented Soybean Pulp Alleviates Disease Progression of 5×FAD Model Mice - Chun-Yen Yang; Yu-Hsuan Liu; Ta-Chun Lin; Kuo-Hsuan Chang; Hsiu Mei Hsieh-Li (Molecular Neurobiology, 2025)
Alzheimer’s disease (AD) is the most common neurodegenerative disorder of the central nervous system, characterized by memory loss and cognitive decline. The two main hypotheses regarding AD involve the accumulation of amyloid-β (Aβ) forming plaques and the intracellular hyperphosphorylation of tau protein, leading to the formation of neurofibrillary tangles (NFT). These processes are accompanied by neuroinflammation and oxidative stress, and eventual neuronal death. While soy foods are widely recognized for their nutritional benefits, soybean pulp (okara), the residue left over from making tofu or soybean milk, is mostly discarded as kitchen waste, despite being rich in nutrients such as dietary fiber, protein, and isoflavones. This underutilized byproduct may serve as a valuable resource for functional food development and sustainable resource use. In this study, fermented soybean pulp (FS) demonstrated neuroprotective effects. In vitro, FS at concentrations of 0.001 µg/mL and 0.01 µg/mL significantly improved cell viability in Aβ-induced HT-22 cells and reduced lipid peroxidation. Further, in vivo oral administration of FS attenuated the cognitive deficits of 5 × FAD mice, enhancing both short and long-term memory and reducing anxiety-like behaviors. Immunohistochemical analysis revealed that the FS-treated 5 × FAD mice group significantly reduced hippocampal amyloid plaque accumulation and gliosis. FS also upregulated the expression levels of brain-derived neurotrophic factor (BDNF), PSD95, and synaptophysin, while preventing hippocampal neuronal loss. Mechanistically, FS may activate the Nrf2 antioxidant pathway and NF-κB-mediated inflammation through the modulation of the Akt/GSK3β signaling axis in the hippocampus. These molecular actions likely contribute to increased antioxidant enzymes and suppressed neuroinflammatory responses. Overall, this study suggests that FS has therapeutic potential for alleviating cognitive and behavioral impairments in AD. Moreover, the repurposing of soybean pulp, which would otherwise be discarded, enhances its utilization value and supports sustainable green recycling.

Positive effects of gamma aminobutyric acid on growth and lipopolysaccharide-induced intestinal mucosal barrier damage in snakehead (Channa argus) - Xue-qin Wu; Xu-nan Li; Feng-kun Cai; Yun-jie Lin; Xiao-tian Niu; Xiu-mei Chen; Yan-nan Tong; Gui-qin Wang (Aquaculture International, 2025)

Two new withanolides from Physalis minima L - Li-Jie Zhang; Mei-Lin Peng; Shi-Ying Xu; Fu-Rui Wang; Lin-Lin Yu; Qin-Feng Zhu; Shang-Gao Liao; Guo-Bo Xu (Natural Product Research, 2025)

Oxymatrine possibly inhibits differentiation and maturation of oligodendrocytes in the remyelination of the toxin-induced demyelination animal model - Mei Li; Fei Huang; Jian Song; Renzhang Liang; Zhongwei Zhou; Yinglan Lin; Lili Hu; Jinghai Gu; Hua Yang; Shaozhang Hou; Huisheng Ma; Peng Wang (Metabolic Brain Disease, 2025)

Research progress on the regulation of plant growth and development by TOR kinase - Jiahui Xu; Ying Zhang; Jiahong Qi; Haojia Shi; Xianwen Liu; Mei Jin; Qingyu Guo; Qian Wang; Kaiyue Wang; Yongpeng Li; Xigang Liu; Lin Guo; et al. (Plant Science, 2025)

The influence of water flow disturbance form on the granulation of algae sludge: Granulation property, treatment effect and algae biological structure - Peng-fei Yu; Ao Wang; Hai-wen Sun; Ding Wang; Xing-guan Ma; Yu-jia Wang; Bo-mei Hu; Li-yao Han; Yu-bo Fu; Dian-lin Jiang; Shi-gang Tu (Journal of Water Process Engineering, 2025)

Corrosion inhibition of steel reinforcement with two vitamin-modified MgAl-LDHs in simulated concrete pore solutions: Experimental and theoretical investigation - Yong Wen; Xiaoqi Guo; Haimeng Lin; Lina Zhou; Mei Li; Qing-feng Liu (Journal of Environmental Chemical Engineering, 2025)

Synergizing dual superlyophobicity and catalytic self-cleaning in cobalt oxide decorated 3D carbon membranes for efficient oil/water separation - Zhiying He; Zhibin Zeng; Junjie Zheng; Mei Zhu; Xiran Yang; Shengyu Li; Haokun Zhang; Qian Zhang; Peng Zhao; Lin Chen; Sudong Yang (Journal of Environmental Chemical Engineering, 2025)

Interface iodine management strategy towards high-efficiency and stable perovskite solar cells - Jiaqi Zhang; Yanzhuo Gou; Weideren Dai; Bowen Zhou; Jinyi Zeng; Zimeng Zhu; Ziwei Zhang; Tao Mei; Liangyou Lin; Xianbao Wang; Qidong Tai; Jinhua Li (Chemical Engineering Journal, 2025)

Recyclable, photothermal dual responsive shape memory epoxy vitrimers containing dynamic oxime-carbamate bonds, dynamic ester bonds and hydrogen bonds based on vegetable oil - Xiaoqi Xie; Shouhai Li; Mei Li; Haiyang Ding; Mingtao Lin; Lina Xu; Na Yao; Qingyuan Feng; Xiaohua Yang; Xiao Feng; Yan Zhang; Yi Xing (Chemical Engineering Journal, 2025)

A GTPase activating protein Polrg1 regulates the development and cellulase expression of Penicillium oxalicum - Shuai Li; Wenchao Chen; Zhimin Shi; Lin Xu; Ziyin Xu; Yihang Qu; Yu Wang; Chunna Sun; Mei Chen; Zhonghai Li (World Journal of Microbiology and Biotechnology, 2025)

Isochrysis zhanjiangensis exhibits protective effects against metabolic abnormalities induced by high-fat diet in mice - Mei Wu; Yu Bai; Yanrong Li; Kang Chen; Jingyang Le; Jian Li; Chengxu Zhou; Spiros N. Agathos; Lin Zhang; Xiaojun Yan; Jichang Han (Marine Life Science & Technology, 2025)

Self-feedback cascading DNA circuit encapsulated within a gene-modified bifunctional virus-inspired nanovector for light-gated spatiotemporal biosensing in live organisms - Xiao-Xue Chen; Yong-Yao Song; Zhuo Chen; Tian-Tian Zhang; Wei-Lin Chen; Xiao-Mei Wang; Jun-Rui Hu; Cheng-Yu Li (Analytica Chimica Acta, 2025)

Seaweed polysaccharides as potential Prebiotics: Rationale, factors, Prebiotic activity manifestations, gut health mechanisms and extraintestinal impacts - Qianmin Lin; Li Zhong; Mei Zeng; Supaluck Kraithong; Xuewei Xia; Weiyang Kuang; Qingqing Wang; Riming Huang (Trends in Food Science & Technology, 2025)

Development and characterization of a high-resolution, high-sensitivity collinear resonance ionization spectroscopy system - Han-Rui Hu; Yang-Fan Guo; Xiao-Fei Yang; Zhou Yan; Wen-Cong Mei; Shao-Jie Chen; Yin-Shen Liu; Peng Zhang; Shi-Wei Bai; Dong-Yang Chen; Yong-Chao Liu; Shu-Jing Wang; et al. (Science Bulletin, 2025)

DEHP and its metabolite MEHP exposure impairs endometrial decidualization during early pregnancy via up-regulation of Mtmr6 - Li-Ping Tan; Liu Yuan; Yan Zhang; Jun-Lin He; Xin Yin; Yi-Dan Ma; Xue-Mei Chen; Wei-Ke Li; Fang-Fang Li; Ru-Fei Gao (Reproductive Toxicology, 2025)

Experimental study on the impact of safety valve venting pressure on thermal runaway in large-format lithium iron phosphate battery - Chaoshi Liu; Yong Liu; Zhixiang Cheng; Yuxuan Li; Pengjie Liu; Lin Liu; Yuanyuan Min; Qiangling Duan; Wenxin Mei; Qingsong Wang (Process Safety and Environmental Protection, 2025)

Alternative splicing of OsNPR3 promoted by the bacterial TAL effectors-targeted splicing regulator OsRBP11 antagonizes OsNPR1 function and enhances disease susceptibility in rice - Xiaochen Chen; Xiaohui Yao; Fang Yan; Shaofang Li; Zuo-Dong Wang; Fu-You Yin; Miao Zhou; Zhen Wang; Lina Qin; Baoguo Zhao; Kai Lu; Liyuan Zhang; et al. (Molecular Plant, 2025)

Ratiometric photoelectrochemical aptasensor for ultrasensitive kanamycin detection based on superior photoactive high-entropy sulfide nanosheets coupling with dual-atom nanozyme inducing polarity switch - Jia-Lin Li; Li-Ping Mei; Ai-Jun Wang; Pei Song; Jiu-Ju Feng (Chemical Engineering Journal, 2025)

Templating PbI2 intermediate phase toward crystal-plane-engineered formamidinium-based perovskite films for efficient and stable solar cells - Yanzhuo Gou; Jiaqi Zhang; Jinguo Cao; Weideren Dai; Wenbo Li; Bowen Jin; Yun Wang; Liangyou Lin; Congcong Wu; Tao Mei; Xianbao Wang; Qidong Tai; et al. (Chemical Engineering Journal, 2025)

Block copolymer architectures with poly(ε-caprolactone) for modulating interactions to enhance selectivity and stability of semiconducting single-walled carbon nanotube dispersions - Mei-Nung Chen; Rin Iwasaki; Mayoh Ashiya; Haoyu Zhao; Qi-An Hong; Yen-Ting Li; Kai-Lin Chen; Maina Moses Mburu; Wei-Ting Li; Xiaodan Gu; Wei-Hung Chiang; Takuya Isono; et al. (Chemical Engineering Journal, 2025)

The Adhesion Characteristics of Fouling Organism on Two Kinds of Mesh Coat - Lei Li; Jinmeng Bao; Dagui Liao; Yanan Wei; Cong Yan; Xiaoxu Fan; Shen Lin; Dan Liu; Wei Tian; Yanming Sui; Mei Jiang (Thalassas: An International Journal of Marine Sciences, 2025)

A Kinetic Study on the Accumulation of No.0 Fuel Oil and Pinghu Crude Oil Water-Accommodated Fraction in Exopalaemon carinicauda - Lei Li; Yiyun Zhang; Li Wei; Aijia Lin; Jiaying Cai; Zengqiao Wei; Qingyuan Wu; Junxiang Niu; Yanming Sui; Mei Jiang (Fishes, 2025)
The kinetic parameters of No.0 fuel oil and Pinghu crude oil water-accommodated fractions (WAFs) during accumulation and elimination in Exopalaemon carinicauda were quantified using a semi-static two-compartment kinetic model. The accumulation phase data were analyzed via nonlinear regression to obtain kinetic parameters, yielding critical values including the uptake rate constant (k1), elimination rate constant (k2), bioconcentration factor (BCF), equilibrium body burden (CAmax), and biological half-life (B1/2). Modeling results demonstrated distinct kinetic parameters for the two oils. For No.0 fuel oil, the average values were k1 = 5.21; k2 = 0.1105; BCF = 48.98; CAmax = 2.95 mg/kg; and B1/2 = 6.40 days. For Pinghu crude oil, the averages were k1 = 10.25; k2 = 0.1044; BCF = 98.15; CAmax = 8.48 mg/kg; and B1/2 = 6.64 days. The uptake rate constant (k1) and BCF generally decreased with increasing petroleum hydrocarbon exposure concentrations in ambient seawater, while the elimination rate constant (k2) remained relatively constant across different concentrations. CAmax increased proportionally with the petroleum hydrocarbon exposure concentration. Goodness-of-fit tests confirmed that the petroleum hydrocarbon concentrations in the experimental data were well described by the semi-static two-compartment model. Throughout the testing period, the concentration of No.0 fuel oil in Exopalaemon carinicauda remained lower than that of Pinghu crude oil.

A new illudane sesquiterpene from the edible fungus Pholiota nameko - Lian Yang; Huan Zhang; Shu-Hang He; Ju Xu; Xiao-Long Li; Fei-Xing Li; Dong-Mei Lin; Deng-Ji Lou; Xiao-Yan Yang (Natural Product Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

A symbiotic bacterium regulates the detoxification metabolism of deltamethrin in Aedes albopictus - Si-jia Deng; Lei Tu; Lin Li; Ju-ping Hu; Ju-lin Li; Jian-xia Tang; Mei-chun Zhang; Guo-ding Zhu; Jun Cao (Pesticide Biochemistry and Physiology, 2025)

Icing monitoring technology and application of 10 kV overhead distribution lines based on axial tension measurement - Lin Yang; Lulu Mei; Haochen He; Quan Liu; Yanpeng Hao; Licheng Li; Xinhao Lin (Cold Regions Science and Technology, 2025)

Engineering strategies for producing medium-long chain dicarboxylic acids in oleaginous yeasts - Xin Wang; Mei-Li Sun; Lu Lin; Rodrigo Ledesma-Amaro; Kaifeng Wang; Xiao-Jun Ji (Bioresource Technology, 2025)

GMNN mutations cause female infertility characterized by preimplantation embryo arrest through regulating DNA re-replication - Honghui Zhang; Wei Su; Xiaohong Jiang; Yang Wang; Bohan Yang; Xian Wan; Cheng Li; Shuai Zhao; Changlong Zhang; Shigang Zhao; Yuehong Bian; Mei Li; et al. (Science China Life Sciences, 2025)

Revealing the Oxidative Stress-Related Molecular Characteristics and Potential Therapeutic Targets of Schizophrenia through Integrated Gene Expression Data Analysis - Xiu-Mei Zhu; Ji Chen; Hua-Jie Ba; Chun Yang; Jian-Wei Liu; Rui Guo; Shi-Lin Li; Ping Huang; Cheng-Tao Li; Su-Hua Zhang (Molecular Neurobiology, 2025)

A Rho-Type GTPase Protein Pocdc42 Regulates the Development and Cellulase Expression of Penicillium oxalicum - Shuai Li; Wenchao Chen; Zhimin Shi; Ziyin Xu; Lin Xu; Yu Wang; Yihang Qu; Chunna Sun; Mei Chen; Zhonghai Li (Current Microbiology, 2025)

A portable point-of-care testing platform for rapid and sensitive miRNA-21 detection for heart failure diagnosis - Qian Kai Lin; Wen Qing Sun; Bo Zhang; Qiao Ling; Yan Qian; Cheng Zhi Huang; Chun Mei Li; Na Wang (Analytica Chimica Acta, 2025)

Antiviral prenylated C6–C3 derivatives containing a methylenedioxyl group from the roots of Illicium brevistylum - Jing-Yu Zhang; Qian-Ru Wang; Hui-Lin Yang; Rong-Mei Gao; Mi Li; Jia Yang; Yu-Huan Li; Li Li; Shuang-Gang Ma (Phytochemistry, 2025)

Green solvent hydrothermal recycling of end-of-life crystalline silicon photovoltaic modules - Kai Zhang; Shihao He; Danyan Qin; Xian Xie; Wei Zhang; Pan Deng; Jintao Li; Hongdan Rao; Heming Deng; Tao Mei; Xianbao Wang; Liangyou Lin (Chemical Engineering Journal, 2025)

Glutaminolysis and α-ketoglutarate-stimulated KCa3.1 expression contribute to β-adrenoceptor activation-induced myocardial fibrosis in mice - Ru-Yue Bai; Lin-Hong Wu; Yan Wang; Chen Guo; Gang She; Zheng-Da Pang; Jing-Jing Li; Xin-Yi Zhao; Meng-Zhuan Han; Xia-Xia Hai; Yi-Yi Yang; Yi Zhang; et al. (Science China Life Sciences, 2025)

Mechanistic insights into endometriosis: roles of Streptococcus agalactiae and L-carnitine in lesion development and angiogenesis - Yuan Zhuang; Ting Lyu; Yang Chen; Wei Li; Lei Tang; Shi-ping Xian; Peng-fei Yang; Lijie Wang; Qian-qian Zhang; Chaoming Mei; Yu-jing Lin; Zhixiang Yan; et al. (Angiogenesis, 2025)

The synthesis of arylmethylene bisindoles catalyzed by nickel perchlorate as potential antifungal agent against Clarireedia homoeocarpa - Ye Zhou; Ruyuan Wang; Rui Feng; Bi Wang; Shu Xu; Mei Tian; Wenhao Liang; Jin Chen; Yu Chen; Xu Feng; Li Lin; Jinyue Luo; et al. (Phytochemistry Letters, 2025)

Three new sesquiterpenes with cytotoxic activity from Croton tiglium - Wen-Ying Zhou; Xiao-Xiao Zheng; Yang-Mei Ou; Yang-Lin Ou; Hong-Yu Jang; Yu-Xin Peng; Yi-Yi Wang; Bi-Qing Zhao; Li Li (Phytochemistry Letters, 2025)

Modeling and mechanistic understanding of vertical dissolved methane transport in integrated vertical flow constructed wetlands (IVCWs) - Ru Xue; Ke Zhang; Xiaoling Liu; Bing Jiang; Hongbing Luo; Mei Li; You Mo; Cheng Liu; Lin Li; Wei Chen; Lin Cheng; Jia Chen; et al. (Journal of Water Process Engineering, 2025)

The effect of 254 nm ultraviolet C promoting ethanol-induced gastric injury healing - A potential physical factor therapy - Xiao Zhang; Dong-mei Li; Hong-long Chen; Xi-sheng Lin; Su-su Li; Le Yu; Nan Peng; Li-kang Wang; Na Wang; Yue-ming Gao (Journal of Photochemistry and Photobiology B: Biology, 2025)

Time series comparative genomics analysis reveals the adaptive evolution of caproic acid-producing bacteria to the long-term liquor brewing environment - Gan-Lin Li; Jun-Lan Mei; Li-Juan Chai; Xiao-Zhong Zhong; Ya-Ning Song; Zhen-Ming Lu; Xiao-Juan Zhang; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (Food Bioscience, 2025)

miR-758-3p Interferes with Neuronal Apoptosis in Cerebral Ischemia–Reperfusion by Inhibiting ILK - Xiaoli Min; Xuesong Bai; Qing Zhao; Wenwu Yang; Sixian Lin; Lei Xian; Rui Jing; Xuhui Li; Wenji Jia; Wei Miao; Mei Yin; Feifei Shang; et al. (Molecular Neurobiology, 2025)

COP1 Overexpression Attenuates Nociceptive Behaviors and Neuroinflammation in Cancer-Induced Bone Pain by Suppressing c/EBPβ - Dan-Yang Li; Lin Liu; Shao-Jie Gao; Dai-Qiang Liu; Long-Qing Zhang; Jia-Yi Wu; Fan-He Song; Xin-Yi Dai; Ya-Qun Zhou; Wei Mei (Journal of Neuroimmune Pharmacology, 2025)

New perspectives on the immune regulatory role of dietary silymarin in the intestines of juvenile grass carp (Ctenopharyngodon idella) - Feng Jia; Li Wei; Wei-Dan Jiang; Pei Wu; Yang Liu; Yao-Bin Ma; Xiao-Wan Jin; Hong-Mei Ren; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2025)

Advances in research on the control of pollen tube growth by calcium in higher plants - Yi Hua Lin; Mei Zhen Lin; Hui Qiao Tian; Dong Xiao Li (Plant Science, 2025)

Functional characterization of chemosensory proteins in three sympatric Tomicus bark beetles feeding on Pinus yunnanensis: Implication for the conservation and divergence of ligand-binding profiles - Lin-Mei Pu; Peng-Fei Wang; Yu-Yue Lu; An-Jin Yang; Li-Li Liu; Nai-Yong Liu (Pesticide Biochemistry and Physiology, 2025)

Discovery and configurations assignment of Ile/Leu-containing cyclic peptides with cytotoxic activity, Reniochpeptins A–D, from the marine sponge Reniochalina sp. - Shuai-Shuai Zhang; Zong-Mei Wu; Ying Wu; Ya-Jun Zeng; Yuan-Yuan Zhang; Xin-Li Lin; Si Zhang; Kai-Xuan Zhan; Hou-Wen Lin; Shu-Ping Wang (Phytochemistry, 2025)

Research on ship dynamic feature extraction and prediction method based on visual data - Siling Lin; Yong Li; Yu Hu; Jia Shi; Shaohua Wang; Peng Wang; Qiang Mei; Xiao Li; Haowen Wei (Ocean Engineering, 2025)

Luminescence dating of core DLC70-2 from the North Yellow Sea in China and its implication for late Quaternary transgressions - Nan Tang; Zhongbo Wang; Penghui Lin; Yuexin Liu; Zonghui Wu; Haozheng Tian; Xi Mei; Jun Sun; Jianghao Qi; Rihui Li; Shuyu Wu; Hongxian Chu; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Blue carbon potential from rehabilitating urban mangrove forests in coastal city - Peiyang Qiao; Yue Meng; Changxin Liu; Tingting Zhang; Mei Li; Liangxia Feng; Qinchang Chen; Jialin Zhang; Chen Lin; Xiaoxuan Gu; Luzhen Chen (Estuarine, Coastal and Shelf Science, 2025)

Effects of iron/aluminum mineral phases on soil organic carbon storage in different clay soils of subtropical acidic forests - Yi Li; Chen-chen Wang; Cui Zou; Yang Zhao; Pei Wei; Yu-ying Liu; Xiao-jun Zhao; Dun-mei Lin; Xian-jin He; Jun-long Huang; Jin-song Guo; Guang-yu Zhu (CATENA, 2025)

Accelerated detection of carbapenem resistance in Klebsiella pneumoniae via single-cell Raman spectroscopy - Jia-Cheng Ding; Li-Ting Dai; Jia-Xin Tang; Hui-Min Zhang; Le-Le Zhai; Chuang-Ye Cai; Zhi-Rou Xiao; Zhe-Mei Chen; Jia-Hui Ling; Meng-Xue Zou; Xi-Wu Cao; Li-Juan Lin; et al. (World Journal of Microbiology and Biotechnology, 2025)

Unearthing Vertical Stratified Archaeal Community and Associated Methane Metabolism in Thermokarst Sediments - Ze Ren; Mei Wang; Jinlei Yu; Lixiang Zhang; Zhenmei Lin; Xia Li; Yunlin Zhang (Environmental Microbiology, 2025)
Thermokarst lakes are hotspots for greenhouse gas emissions across the Arctic and Qinghai‐Tibet Plateau. Investigating the vertical stratification of archaeal communities in thermokarst lake sediments is essential for understanding their ecological roles and contributions to methane production. Here, we analysed archaeal communities along a depth gradient in thermokarst lake sediments. Alpha diversity (richness and Shannon index) generally decreased with depth. Euryarchaeota was the most abundant phylum, though its relative abundance declined with depth, while Thaumarchaeota increased. At the order level, Methanosarcinales and Nitrosopumilales showed increased relative abundance with depth, indicating adaptation to deeper anoxic layers, whereas Methanomicrobiales and Methanotrichales decreased. Beta diversity increased with depth, shifting from stochastic to deterministic processes. Network topology revealed reduced species connectivity but heightened modularity at depth, signalling niche specialisation. Functionally, genes associated with the initial steps of methane metabolism ( Fwd , Mtd , Mer ) increased with depth, while those involved in later steps ( Mtr , Mcr ) decreased, suggesting reduced energy conservation efficiency and lower overall methanogenesis rates in deeper sediments. These findings highlight the significant impact of vertical stratification on archaeal community structure, interaction networks, and functional capabilities.

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Three new dimeric 2-(2-phenethyl)chromones from the agarwood of Aquilaria malaccensis - Xian-Yun Yan; Wei Li; Hao Wang; Wen-Hua Dong; Jun Zeng; Fei Wu; Wen-Li Mei; Lin-Fu Liang; Hao-Fu Dai (Phytochemistry Letters, 2025)

Cooperation of Lactoplantibacillus plantarum and polyethylene microplastics facilitated the disappearance of tetracycline during anaerobic fermentation of whole plant maize - Yubo Zhang; Pan Wang; Yu Tang; Chaosheng Liao; Xiaolong Tang; Pai Hou; Cheng Chen; Xiaokang Huang; Guangrou Lu; Lin Li; Mingjie Zhang; Fuxiang Li; et al. (Journal of Hazardous Materials, 2025)

Microplastics enhance laccase-driven bisphenol A removal in multipollutant wastewater - Jie Zhang; Jiongna Liu; Xinyi Liu; Yu Su; Chunyang Yu; Xuemei Tan; Lin Zhuo; Mei Ye; Qinglin Luo; Biao Li (Journal of Environmental Management, 2025)

Structural controls on the magma emplacement and distribution of sulfide orebodies in the Kalatongke Cu-Ni sulfide district, NW China - Xue-Hai Wang; Ke-Zhang Qin; Xing-Wang Xu; Dong-Mei Tang; Ya-Jing Mao; Lei Zhang; Min-Qiang Zhang; Fang-Lin Yuan; Yi Li (Journal of Asian Earth Sciences, 2025)

Dietary pyridoxine promoted muscle protein deposition relating to PI3K/AKT/TOR pathway and the ubiquitin proteasome system in grass carp (Ctenopharyngodon idella) - Li-Fu Gong; Xiao-Qiu Zhou; Lin Feng; Pei Wu; Wei-Dan Jiang; Yao-Bin Ma; Xiao-Wan Jin; Hong-Mei Ren; Jia-Yong Tang; Fa-Li Wu; Yang Liu (Food Bioscience, 2025)

A remotely triggered phase change hydrogel dressing for controlled release and promoting healing of infected wounds - Xiaolong Hu; Hongyan Zhang; Zuan-Tao Lin; Yu Chen; Hao Cheng; Bi-Huan Zhong; Yongli Li; Xiao-Ping Liao; Jian Sun; Mei X. Wu; Gang-Biao Jiang (Chemical Engineering Journal, 2025)

Molecular chelating and shielding operation for organic photoelectrochemical transistor detection of chlorpyrifos - Lang Lin; Yu-Mei Li; Rui Ban; De-Man Han; Feng-Zao Chen; Wei-Wei Zhao (Analytica Chimica Acta, 2025)

Fabrication of photo-responsive chitosan imprinted aerogels for selective adsorption and green desorption of dysprosium ions - Youming Zhu; Xudong Zheng; Guomeng Li; Xi Zhang; Lin Guo; Jinfeng Mei; Zhongyu Li (Process Safety and Environmental Protection, 2025)

Mechanism of Epigallocatechin-3-gallate in the prevention and treatment of irritable bowel syndrome: A network pharmacology and gene expression omnibus chip data-based study - Fangchen Ye; Laifu Li; Lianli Wang; Yan Ran; Lin Mei; Yating Sun; Xinping Zhang; Fei Dai (PharmaNutrition, 2025)

Potential ecological risk of microplastics contamination to environment in protect area lakes - Li Naying; Mei Xintong; Zhong Bo; Wang Xiaofeng; Liu Xin; Yang zao; Lin Honghui; He Yixin (Journal of Hazardous Materials, 2025)

Performances and mechanisms of catalytic ozonation for paint wastewater via catalysts of Fe-Mn deposited within graphitized beads of γ-Al2O3 - Mei Dai; Chunping Yang; Liusiyu Yang; Yan Lin; Shanying He; Xiang Li; Qiuya Niu; Shaohua Wu (Journal of Cleaner Production, 2025)

Untargeted qualitative and targeted quantitative analysis of saponins reveal differential chemotypes of Gynostemma pentaphyllum and G. longipes from different geographical origins - Hai-Zhen Liang; Mei-Yan Wang; Guang Yang; Gang Li; Jie Zhang; Lan Yao; Yi Nan; Chang-Liang Huang; Xiao-Juan Chen; Juan Song; Feng Cao; Bao-Lin Guo; et al. (Food Chemistry, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Correction to: Scorpion Venom Heat-Resistant Peptide is Neuroprotective Against Cerebral Ischemia-Reperfusion Injury in Association with the NMDA-MAPK Pathway - Xu-Gang Wang; Dan-Dan Zhu; Na Li; Yue-Lin Huang; Ying-Zi Wang; Ting Zhang; Chen-Mei Wang; Bin Wang; Yan Peng; Bi-Ying Ge; Shao Li; Jie Zhao (Neuroscience Bulletin, 2025)

Cholesterol suppresses AMFR-mediated PDL1 ubiquitination and degradation in HCC - Wei-Qing Shao; Yi-Tong Li; Xu Zhou; Sheng-Guo Zhang; Ming-Hao Fan; Dong Zhang; Zhen-Mei Chen; Chen-He Yi; Sheng-Hao Wang; Wen-Wei Zhu; Ming Lu; Ji-Song Chen; et al. (Molecular and Cellular Biochemistry, 2025)

Seasonality and extreme flooding can override the effects of debris dam removal on riverine species: a case study of macroinvertebrates - Tsung-Tse Hsieh; Jia-Yi Li; Che-Chang Lin; Mei-Hwa Kuo; Ming-Chih Chiu (Aquatic Ecology, 2025)

Improved soil organic matter monitoring by using cumulative crop residue indices derived from time-series remote sensing images in the central black soil region of China - Mei-Wei Zhang; Xiao-Lin Sun; Mei-Nan Zhang; Hao-Xuan Yang; Huan-Jun Liu; Hou-Xuan Li (Soil and Tillage Research, 2025)

Bioactivity-guided isolation of potent inflammasome and mitochondria damage inhibitory diterpenoids from Orthosiphon wulfenioides - Wen-Chao Tu; Peng-Yun Yang; Xing-Jie Zhang; Yuan-Lin Kong; Bo Li; Hui-Juan Wang; Muhammad Aurang Zeb; Xiao-Li Li; Mei-Feng Liu; Wei-Lie Xiao (Phytochemistry, 2025)

Advancements in the development of porous nanomaterials for CO2 capture of deep decarbonization: Pore structure and chemical group optimization - Sifan Bao; Xudong Zheng; Zihuai Xu; Biao Ji; Zhouzhou Yang; Wei Sun; Lin Guo; Youming Zhu; Jinfeng Mei; Jian Rong; Zhongyu Li (Journal of Environmental Chemical Engineering, 2025)

Using isotope-tracer method with deuterium for quantitative study of hydrogen activation mechanism in direct coal liquefaction - Xiao-Dong Zhou; Xue-Long Yin; Lang Liu; Xue-Li Huang; Jing-Mei Liu; Ting Liu; He Lin; Feng-Yun Ma (Fuel, 2025)

Effect of tourmaline/organic montmorillonite on fume generation and suppression characteristics of asphalt binder and mixture - Xiule Chen; Yiming Li; Peifeng Cheng; Mei Lin; Meng Wang (Fuel, 2025)

High performance piperidinium based anion exchange membranes with different twisted backbone structures for fuel cells - Ying Jie Liu; Guo Liang Zhang; Yong Qi Hu; Hui Peng; Li Wei Lai; Ai Mei Zhu; Qiu Gen Zhang; Qing Lin Liu (Chemical Engineering Journal, 2025)

Light-emitting diodes affect plantlet growth of Spathiphyllum cannifolium by regulating photosynthesis and sucrose metabolism during ex vitro rooting - Shuo Yu; Kui-Hua Li; Hang-Lin Song; Yue Dai; Yin-Ji Jiang; Mei-Yu Jin; Xuan-Chun Piao; Mei-Lan Lian (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Genetic patchiness of the endangered giant clam Tridacna maxima from Peninsular Malaysia - Li Keat Lee; Ya Yi Huang; Chaolun Allen Chen; Mei Lin Neo; Kieng Soon Hii; Haifeng Gu; Po Teen Lim; Chui Pin Leaw (Coral Reefs, 2025)

Taxifolin regulates SLC31A1-mediated cuproptosis and tumor progression in hepatocellular carcinoma - Jike Li; Yuelian Wang; Lei Bao; Guo Chen; Qing Ye; Chengshi He; Lin Liu; Mei Luo (Human Cell, 2025)

Z/E configuration controlled by a Taxus sesquiterpene synthase facilitating the biosynthesis of (3Z,6E)-α-farnesene - Xue Tang; Xian-Jing Zhang; Jing-Feng Pan; Kai Guo; Chun-Lin Tan; Qiao-Zhuo Zhang; Li-Ping Long; Rui-Feng Ding; Xue-Mei Niu; Yan Liu; Sheng-Hong Li (Phytochemistry, 2025)

Recent progress on triterpenoid derivatives and their anticancer potential - Zi-Xuan Zhao; Qiong-Yu Zou; Ying-Hong Ma; Susan L. Morris‐Natschke; Xiang-Yuan Li; Lin-Chun Shi; Guo-Xu Ma; Xu‐Dong Xu; Mei‐Hua Yang; Zi-Jian Zhao; Yuan-Xiang Li; Jing Xue; et al. (Phytochemistry, 2025)

A multirisk-rescued biomimetic nanozyme against periodontitis via inflammation targeting and microenvironment reprogramming - Lin Li; Rui-Xin Wu; Jia Wang; Rui Jin; Xin-Yu Zhang; Mei Xu; Si-Yao Li; Rui Gao; Bei-Min Tian; Xiao-Tao He; Fa-Ming Chen; Yuan Yin (Chemical Engineering Journal, 2025)

Surface chemistry regulation enables highly durable superhydrophobic coatings with environmental robustness and pH-triggered recoatability - Mei-Lin Guo; Fang Wang; Ren-Yi Sun; Chun-Bo Li; Jin-Le Li; Fei Song; Yu-Zhong Wang (Chemical Engineering Journal, 2025)

Mitochondria-targeted delivery of zinc-coordinated resveratrol nanoparticles rescues the osteogenic potential of periodontal ligament stem cells compromised by inflammation for periodontal wound healing - Yu-Jie Tan; Xuan Li; Wen-Jie Zhang; Yu-Meng Cao; Jie-Kang Zou; Lin Jing; Dian Gan; Yu-Zhe Chen; Mei Xu; Ying An; Fa-Ming Chen; Xiao-Tao He; et al. (Chemical Engineering Journal, 2025)

Blocking the PD-1 signal transduction by occupying the phosphorylated ITSM recognition site of SHP-2 - Wenjie Li; Wenyi Mei; Hewei Jiang; Jie Wang; Xiaoli Li; Lina Quan; Yanyan Diao; Yanni Ma; Sisi Fan; Zhuwei Xie; Mengdie Gong; Huan Zhu; et al. (Science China Life Sciences, 2025)

Short-term coalbed methane concentration prediction and early warning based on the STL-ENN-GRU hybrid model - Kangle Li; Lin Jiang; Yan Zhang; Mei Wang; Yuancheng Li; Kun Yang (Earth Science Informatics, 2025)

Correction: MFG-E8 Ameliorates Nerve Injury-Induced Neuropathic Pain by Regulating Microglial Polarization and Neuroinflammation via Integrin β3/SOCS3/STAT3 Pathway in Mice - Longqing Zhang; Xinyi Dai; Danyang Li; Jiayi Wu; Shaojie Gao; Fanhe Song; Lin Liu; Yaqun Zhou; Daiqiang Liu; Wei Mei (Journal of Neuroimmune Pharmacology, 2024)

Cadmium bioavailability in market nori and kelp: A comparison with rice and mechanisms underlying reduction in rice cadmium bioavailability with nori and kelp consumption - Xu Duan; Lei Zhou; Sheng-Zhi Chen; Xin-Ying Lin; Rong-Yue Xue; Xi-Mei Xue; Dongmei Zhou; Hong-Bo Li (Science of The Total Environment, 2024)

Nitrogen fixation of different seasons and parts of seagrass Enhalus acoroides in Xincun Bay, northern South China Sea - Zhen-Zhen Wu; Xiao-Mei Li; Hui Zhao; Long Wei; Jun-De Dong; Mei-Lin Wu (Regional Studies in Marine Science, 2024)

Study on properties and CO2 emission of self-pulverizing calcium sulfoaluminate (SPCSA) after carbonization curing - Shuguo Li; Yang Lv; Chenhao He; Shengju Hou; Weinan Ma; Xiaodong Wen; Jianming Dan; Junpeng Mei; Lin Chi; Xiangguo Li (Journal of Environmental Chemical Engineering, 2024)

Sporelings and growth of the marine red alga, Gelidium elegans (Gelidiaceae), from Northern Taiwan - Showe-Mei Lin; Shih-Jhe Chen; Pin-Yu Huang; Li-Chia Liu; Yu-Shan Chiou (Journal of Applied Phycology, 2024)

A detailed analysis of 16S rRNA gene sequencing and conventional PCR-based testing for the diagnosis of bacterial pathogens and discovery of novel bacteria - Mei-Na Li; Ting Wang; Nan Wang; Qiang Han; Xue-Ming You; Shuai Zhang; Cui-Cui Zhang; Yong-Qiang Shi; Pei-Zhuang Qiao; Cheng-Lian Man; Teng Feng; Yue-Yue Li; et al. (Antonie van Leeuwenhoek, 2024)

Alteromonas arenosi sp. nov., a novel bioflocculant-producing bacterium, isolated from intertidal sand - Bi Luo; Jing-Yun Su; Ya-Fei Zhang; Yong-Hui Xiao; Yun-Lin Peng; Mei-Ling Sun; Yi Li (Antonie van Leeuwenhoek, 2024)

Benzo(a)pyrene exposure during pregnancy leads to germ cell apoptosis in male mice offspring via affecting histone modifications and oxidative stress levels - Lin Zhang; Wen-Qi Chen; Xiao-Ying Han; Hong-Li Wang; Peng-Zhi Gao; Dong-Mei Wang; Zheng Cao; Chang-Hua Sun; Dong Cheng; Jing Bai; Qi-Long He; Shu-Zhen Liu (Science of The Total Environment, 2024)

Effects of soil microplastic heterogeneity on plant growth vary with species and microplastic types - Xiao-Mei Zhang; Wei-Long Li; Wei Xue; Michael Opoku Adomako; Min Tang; Lin-Xuan He; Fei-Hai Yu (Science of The Total Environment, 2024)

Burden of biliary tract carcinoma in China (1990–2021): Findings from the 2021 Global Burden of Disease Study - Wei Zhang; Yi-Jun Wang; Jiang-Mei Liu; Xu-Heng Sun; Yan Jiang; Fang Shen; Li-Juan Shen; Jing Xiang; Jun-Feng Zhang; Lin-Hua Yang; Wen-Guang Wu; Tao Chen; et al. (Science Bulletin, 2024)

Force mechanism analysis of composite microbial dust suppressants based on extracellular polymeric substances (EPS) mode components - Mei-Xuan Ha; Yu Liu; Yue Feng; Xiang-Ming Hu; Yan-Yun Zhao; Jin-Di Liu; Li Chen; Yan-Lin Qu (Journal of Environmental Management, 2024)

Insufficient FUNDC1-dependent mitophagy due to early environmental cadmium exposure triggers mitochondrial redox imbalance to aggravate diet-induced lipotoxicity - Cai-Yu Lian; Hui-Jia Li; Wei-Hao Xia; Yue Li; Xue-Lei Zhou; Du-Bao Yang; Xue-Mei Wan; Lin Wang (Environmental Pollution, 2024)

Leaching-readsorption of VO43− optimized diffusion and adsorption of OH− on NiFeOOH catalytic interface for industrial water oxidation - Yu Ma; Mei-Xin Lin; Peng-Ji Su; Zi-Yi Gao; Xin Li; You-He Wang; Lian-Ming Zhao; Yong-Ming Chai; Bin Dong (Chemical Engineering Journal, 2024)

Modulated dual photo/electro luminescence via molecular engineering of Ds-A-Dw type TADF materials - Yanrui Liu; Paramaguru Ganesan; Mei Chen; Yuheng Li; Zilong Zhang; Fulin Lin; Baohua Zhang; Peng Gao (Chemical Engineering Journal, 2024)

Recent advances in anti-infective catheters for preventing catheters associated urinary tract infections - Liyuan Liu; Baoxia Xue; Mei Niu; Lin Chen; Yongzhen Yang; Bingshe Xu; Li Zhang (Chemical Engineering Journal, 2024)

Discovery of ElABCG39: a key player in ingenol transmembrane efflux identified through genome-wide analysis of ABC transporters in Euphorbia lathyris L. - Guyin Lin; Pirui Li; Linwei Li; Ruyuan Wang; Wanli Zhao; Mei Tian; Junzhi Wu; Shu Xu; Yu Chen; Xu Feng (Plant Cell Reports, 2024)

Agricultural management reshaped the diversity patterns and community assembly of rhizosphere bacterial communities in a desert farming system - Wen-Hui Lian; Mei-Xiang Li; Ling-Xiang Yue; Shuai Li; Zhi-Liang Lin; Chao-Jian Hu; Jia-Rui Han; Wen-Jun Li; Lei Dong (Applied Soil Ecology, 2024)

Biodegradation of phthalic acid esters by a novel marine bacterial strain RL-BY03: Characterization, metabolic pathway, bioaugmentation and genome analysis - Lei Ren; Xingjia Wang; John L. Zhou; Yang Jia; Hanqiao Hu; Chengyong Li; Zhong Lin; Mei Liang; Yanyan Wang (Chemosphere, 2024)

Exploring the therapeutic potential of Cassia species on metabolic syndrome: A comprehensive review - Lin Xu; Yue Yang; Bin Li; Hong Dong Liu; Ling Xia Xu; Dong Mei Yan; Xue Mei Gao (South African Journal of Botany, 2024)

Synthesis of a novel double Z-scheme BiVO4/Cu2O/g-C3N4 sonocatalyst and research on sonocatalytic degradation of tetracycline - Yang-Cheng Liu; Ying-Di Ge; Hui-Li An; Wan-Ting Ju; Xin-Yi Zhou; Mei-Yi Xing; Yang Wang; Lin Zhang; Xin Wang; Liang Xu (Journal of Environmental Chemical Engineering, 2024)

Mitigating thermal burden and enhancing minor phase emission energy transfer in perovskite by introducing dopamine-mediated silver nanoparticles - Zhen-Li Yan; Jhih-Yuan Chang; Chieh Tsao; Meng-Xiu Fang; Bi-Hsuan Lin; Jia-Hau Tsai; Mei-Hsin Chen; Ru-Jong Jeng; Chi-Ching Kuo (Chemical Engineering Journal, 2024)

A novel vanadium-copper rechargeable battery for solar energy conversion and storage - Chunkun Lin; Jiangxin Wang; Kaixin Zhang; Huibin Shi; Yibing Liu; Kuanhong Mei; Minmin Liu; Yu Zhang; Shuo Li (Chemical Engineering Journal, 2024)

Oxygen evolution reaction enhancing electrochemical performance of V-doped Ni(OH)2 for aqueous asymmetric supercapacitors - Ting Xiao; Hongxiang Lin; Can Tang; Xiuru Li; Yuting Mei; Lin Gao; Lihua Jiang; Peng Xiang; Shibing Ni; Yequan Xiao; Xinyu Tan (Chemical Engineering Journal, 2024)

Self-Healing fluorinated polymer deep eutectic electrolytes for stable lithium metal batteries - Yingzhi Yu; Canhui Ling; Jixu Yang; Antai Zhu; Tuoya Naren; Yuxin Chen; Yuejiao Chen; Weifeng Wei; Xiaobo Ji; Chengchao Li; Libao Chen; Lin Mei; et al. (Chemical Engineering Journal, 2024)

Chemical constituents from Ficus tikoua and chemotaxonomic significance - Han-Lei Wang; Jing Lu; Xue-Lin Chen; Ru Li; Kun Zhang; Yu-Ling Guo; Xia Zhao; Yu-Mei Zhang (Biochemical Systematics and Ecology, 2024)

Cuproptosis-Associated lncRNA Gene Signature Establishes New Prognostic Profile and Predicts Immunotherapy Response in Endometrial Carcinoma - Xi-Ya Jiang; Jing-Jing Hu; Rui Wang; Wei-Yu Zhang; Qin-Qin Jin; Yin-Ting Yang; Jie Mei; Lin Hong; Hui Yao; Feng Tao; Jie-Jie Li; Yu Liu; et al. (Biochemical Genetics, 2024)
Uterine corpus endometrial carcinoma (UCEC), a prevalent kind of cancerous tumor in female reproductive system that has a dismal prognosis in women worldwide. Given the very limited studies of cuproptosis-related lncRNAs (CRLs) in UCEC. Our purpose was to construct a prognostic profile based on CRLs and explore its assess prognostic value in UCEC victims and its correlation with the immunological microenvironment.Methods: 554 UCEC tumor samples and 23 normal samples’ RNA-seq statistics and clinical details were compiled from data in the TCGA database. CRLs were obtained using Pearson correlation analysis. Using LASSO Cox regression, multivariate Cox regression, and univariate Cox regression analysis, six CRLs are confirmed to develop a risk prediction model at last.We identified two main molecular subtypes and observed that multilayer CRLs modifications were related to patient clinicopathological features, prognosis, and tumor microenvironment (TME) cell infiltration characteristics, and then we verified the prognostic hallmark of UCEC and examined its immunological landscape.Finally, using qRT-PCR, model hub genes’ expression patterns were confirmed. Results: A unique CRL signature was established by the combination of six differently expressed CRLs that were highly linked with the prognosis of UCEC patients. According to their CRLs signatures, the patients were divided into two groups: the low-risk and the high-risk groups. Compared to individuals at high risk, patients at low risk had higher survival rates ( p

MFG-E8 Ameliorates Nerve Injury-Induced Neuropathic Pain by Regulating Microglial Polarization and Neuroinflammation via Integrin β3/SOCS3/STAT3 Pathway in Mice - Longqing Zhang; Xinyi Dai; Danyang Li; Jiayi Wu; Shaojie Gao; Fanhe Song; Lin Liu; Yaqun Zhou; Daiqiang Liu; Wei Mei (Journal of Neuroimmune Pharmacology, 2024)

Interpenetrating LiB/Li3BN2 phases enabling stable composite lithium metal anode - Piao Qing; Shaozhen Huang; Tuoya Naren; Quan Li; Haifeng Huang; Kecheng Long; Zhijian Liu; Lin Mei; Fu Sun; Weifeng Wei; Yu Zhang; Jianmin Ma; et al. (Science Bulletin, 2024)

Vanishing giants: An assessment on the population status of giant clams across Malaysia - Li Keat Lee; Mei Lin Neo; Kieng Soon Hii; Haifeng Gu; Chaolun Allen Chen; Po Teen Lim; Chui Pin Leaw (Regional Studies in Marine Science, 2024)

Anaerobic oxidation of methane and greigite formation: Evidence of isotopically heavy pyrite in Pleistocene coastal sediments from the South Yellow Sea - Xiaoxiao Yu; Xi Mei; Jianxing Liu; Baichuan Duan; Rui Zhang; Tiegang Li; Gangjian Wei; Mang Lin (Global and Planetary Change, 2024)

Screening and rational identification of a novel angiotensin-converting enzyme C-domain inhibitory peptide from Fabaceae food peptide library - Tin-Yun Ho; Hsin-Yi Lo; Guan-Ling Lu; Chia-Yu Lin; Mei-Li Stevens; Chiao-Che Chen; Chien-Yun Hsiang (Food Chemistry, 2024)

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

Molecular Cloning and Functional Analysis of ScHAK10 Gene Promoter from Sugarcane (Saccharum officinarum L.) - Hai-Bin Luo; Cheng-Mei Huang; Hui-Qing Cao; Yuan-Wen Wei; Lin Xu; Kai-Chao Wu; Zhi-Nian Deng; Xing-Jian Wu; Li-Ping Ye; Xiao-Ping Yi (Tropical Plant Biology, 2024)

Hinokione: an abietene diterpene with pancreatic β cells regeneration and hypoglycemic activity, and other derivatives with novel structures from the woods of Agathis dammara - Zheng Wang; Zhe-Wei Yu; Yi Zhang; Wen-Hui Wang; Xin-Yi Wu; Shun-Zhi Liu; Yan-Lin Bin; Bang-Ping Cai; Shi-Yan Huang; Mei-Juan Fang; Rong Qi; Ming-Yu Li; et al. (Journal of Natural Medicines, 2024)

Associations among global long interspersed nuclear element-1 DNA methylation, metal exposure, and chronic kidney disease - Yu-Mei Hsueh; Mei-Chieh Chen; Ying-Chin Lin; Chih-Yin Wu; Horng-Sheng Shiue; Sheng-Lun Hsu; Hsi-Hsien Chen; Ya-Li Huang (Archives of Toxicology, 2024)

Warming stimulates mangrove carbon sequestration in rising sea level at their northern limit: An in situ simulation - Peiyang Qiao; Ying Dong; Xiaoxuan Gu; Lian Xu; Mei Li; Wandong Chen; Li Lin; Xiaopin Ni; Luzhen Chen (Limnology and Oceanography, 2024)
Global warming and sea‐level rise are directly influencing the growth, distribution, and greenhouse gas emissions of mangrove forests. However, mangrove forests growing at their latitudinal limits are relatively susceptible to warming; nevertheless, few studies have focused on GHG emissions of latitudinal limits mangrove forests as related to global climate change. To address this knowledge gap, a multiyear in situ control experiment was established in a restored plantation at the northern distribution limit of Kandelia obovata , the most cold‐tolerant mangrove species in China, to simulate both warming and sea‐level rise. We investigated the growth patterns and sediment greenhouse gas emissions of a K. obovata population and identified the primary factors contributing to these changes. The results showed that warming and moderate sea‐level rise enhanced biomass by more than 18%, indicating that warming stimulated plant growth while excessive sea‐level rise inhibited it. The sediment greenhouse gas emissions ranged from 45.5 to 484.6 mgCO 2 m −2 h −1 , 5.6 to 590.3 μ gCH 4 m −2 h −1 , and 11.4 to 385 μ gN 2 O m −2 h −1 , which increased with warming while decreased with sea‐level rise, acting as the net source of greenhouse gas emission. Our study predicted that sea‐level rise, while directly changing sediment properties, had combined effects with warming on these studied mangrove forests that were predicted to emit more greenhouse gases from sediments in the future. These findings indicated that K. obovata plantations within their latitudinal limits tend to accumulate more CO 2 for biomass carbon storage under warming conditions, while stimulating sediment greenhouse gas emissions, which will offset their climate mitigating effect in future climatic scenarios.

Age-related alterations in vortex veins on indocyanine green angiography - Chen-Xi Cai; Shan-Shan Yu; Xiao-Mei Xiong; Bing-Qian Liu; Zhen-Qiang Lin; Qiang Wang; Jin-Li Cui; Ze-Hao Liu; Tao Li; Lin Lu; Ying Lin (GeroScience, 2024)
To determine age-related alterations in vortex veins in healthy subjects. A total of 228 healthy subjects (aged 4 to 86 years) were recruited and divided into four groups (G1, <21 years; G2, 21–40 years; G3, 41–60 years; and G4, 61–86 years). The clinical characteristics of the participants were recorded, and parameters including the number of vortex vein roots (NVVR), the central vortex vein diameter (CVVD), the mean root area of the vortex vein (MRAVV), and the weighted mean of the thickest branch diameter (WMTBD) were obtained by marking the vortex veins on indocyanine green angiography (ICGA). The NVVR in the age group over 60 years old was significantly lower than that in other age groups ( P < 0.05). The CVVD, MRAVV, and WMTBD of all age groups increased with increasing age ( P < 0.05). The NVVR was unevenly distributed among the quadrants ( P < 0.001). The proportions of type four vortex veins (complete systems including ampulla) and anastomotic branches of the vortex veins were significantly increased in elderly participants over 50 years of age ( P < 0.05). Subfoveal choroidal thickness was significantly correlated with age, NVVR, CVVD and MRAVV ( P < 0.05). This is the first study to reveal age-related alterations in vortex veins on ICGA in a healthy population. Aging may lead to partial vortex occlusion and residual vortex dilation. As age increases, anastomotic branches increasingly appear between the originally independent vortex veins. Translational relevance: Aging may lead to partial vortex occlusion and residual vortex dilation.

Colletotrichum cliviicola as a new causal agent causing leaf spot disease on Tilia tomentosa moench (silver linden) in China - Lin Chang; Xue-hai Li; Yi-lin Li; Zi-wen Gao; Yue-mei Zhang; Ning-Li; Zhao-lei Qu; Yi-hong Yang; Hui Sun (Crop Protection, 2024)

New perspectives on the role of vitamin D in the mucosal barrier system of fish gills infected with Flavobacterium columnare - Yao Zhang; Chao-Nan Li; Wei-Dan Jiang; Pei Wu; Yang Liu; Xiao-Wan Jin; Hong-Mei Ren; Lu Zhang; Hai-Feng Mi; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2024)

Enrichment mechanism of organic matter and silicon in lower Cambrian shale of the Yangtze Platform - Donglin Lin; Zhaodong Xi; Shuheng Tang; Gary G. Lash; Jin Li; Qiyang Gou; Ke Zhang; Xiaofan Mei; Kaifeng Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Fe0-mediated mixotrophic denitrification enhanced by carbon fiber for secondary effluent with low C/N ratio - Yi-Mei Cheng; Lin-Chun Jia; Gang Xue; Xian-Ying Li (Journal of Environmental Chemical Engineering, 2024)

Analysis of proteomics and in silico allergenicity prediction of soluble proteins in selenium-enriched peanut leaves - Qi Gao; Wei-Xuan Li; Zi-Heng Liu; Mei Tie; Xue-Jun Gu; Masaru Tanokura; You-Lin Xue (Food and Bioproducts Processing, 2024)

pH-responsive coacervate with adrenergic nerve blockade function inhibits triple-negative breast cancer metastasis by blocking nerve-tumor-immune loop - Jieting Chen; Chaoming Mei; Yan Tan; Fan Yang; Shirui Yang; Xin Wen; Xin Peng; Yong Lin; Dan Li (Chemical Engineering Journal, 2024)

Two-photon polymerization-based 3D micro-scaffolds toward biomedical devices - Wei Wang; Zi-Qing Chen; Bin Lin; Mei-Chen Liu; Yang Zhang; Shu-Juan Liu; Yang Li; Qiang Zhao (Chemical Engineering Journal, 2024)

Warming enhanced the interaction effects of fungi and fungivores and soil potassium mineralization in tropical forest - Feng Sun; Guanzhao Yan; Wei Lin; Wei He; Xianli Cheng; Yingwen Li; Akash Tariq; Jordi Sardans; Josep Penuelas; Jinchuang Wang; Mei Wang; Yuelin Li; et al. (CATENA, 2024)

Phylogeny and genetic diversity of Echinometra sea urchin in Taiwan - Mei-Fang Lin; Ming-Che Yang; Yi-Yuan Lin; Sheng-Chi Chung; Li-Lian Liu (Marine Biology Research, 2024)

Norditerpenoid alkaloids from Aconitum refractum var. circinatum as autophagy inducers - Mei-Zhen Ye; Zhen-Ling Wan; Hong-Yu Ruan; Yu-Qi Yang; Ying Chen; Lin Chen; Shuai Huang; Xian-Li Zhou (Phytochemistry, 2024)

Review on toxicology and activity of tomato glycoalkaloids in immature tomatoes - Li-hao Wang; De-hong Tan; Xue-song Zhong; Mei-qi Jia; Xue Ke; Yu-mei Zhang; Tong Cui; Lin Shi (Food Chemistry, 2024)

Risk analysis of air pollutants and types of anemia: a UK Biobank prospective cohort study - Laifu Li; Yan Ran; Yan Zhuang; Lianli Wang; Jiamiao Chen; Yating Sun; Shiwei Lu; Fangchen Ye; Lin Mei; Yu Ning; Fei Dai (International Journal of Biometeorology, 2024)

Impact of metformin on neocortical development during pregnancy: Involvement of ERK and p35/CDK5 pathways - Muhammet Oner; Mei-Chih Chen; Pang-Ting Cheng; Yu-Hsuan Li; Yu-Chiao Cheng; Ayse Celik; Shiuan-Woei Soong; Li-Wen Hsu; Din-You Lin; G.M. Shazzad Hossain Prince; Trayee Dhar; Hsu-Chen Cheng; et al. (Chemosphere, 2024)

Comparison of the regulatory effects of flavonoids and saponins from Eclipta prostrate on insulin resistance in HepG2 cells - Li Yang; Xiao-mei Zhan; Si-bo Zhao; Xi-lin Xu; Jian-guo Jiang; Wei Zhu (Food Bioscience, 2024)

Environmentally relevant concentrations of benzophenones exposure disrupt intestinal homeostasis, impair the intestinal barrier, and induce inflammation in mice - Yu-Jia Lin; Hong-Mei Li; Yan-Rong Gao; Ping-Fan Wu; Bin Cheng; Chen-Long Yu; Yu-Xin Sheng; Hai-Ming Xu (Environmental Pollution, 2024)

Constructing blocked-nanolayer by surface charge inversion over anion exchange membrane for improved antifouling performance - Dan Lu; Hongyu Jin; Yunchen Mao; Yukun Qian; Ge Li; Jing Wang; Ying Mei; Zhikan Yao; Zhuofan Gao; Lin Zhang (Desalination, 2024)

Regulatory effect of Yinchenhao decoction on bile acid metabolism to improve the inflammatory microenvironment of hepatocellular carcinoma in mice - Jian Shi; Lin Zhu; Bang-Yi Tang; Wan-Qing Yang; Sheng-Yan Xi; Chen-Long Zhang; Peng-Fei Li; Yu-Jie Wang; Kai-Hang Guo; Jing-Ru Huang; Chen-Rui Huang; Zhou-Xin Yu; et al. (Journal of Natural Medicines, 2024)

A Novel Bacillus amyloliquefaciens Specifically Improving the Solubility and Antioxidant Activities of Edible Bird’s Nest - Xin-Lin Li; Jian-Mei Lian; Xiao-Ling Chen; Qun-Yan Fan; Ying Yan; Feng-Jie Cui (Current Microbiology, 2024)

Correction to: Near‑global summer circulation response to the spring surface temperature anomaly in Tibetan Plateau –– the GEWEX/LS4P first phase experiment - Yang Zhang; Yan Pan; Yongkang Xue; Ismaila Diallo; Xubin Zeng; Shuting Li; J. David Neelin; William K. M. Lau; Aaron A. Boone; Frederic Vitart; Tandong Yao; Qi Tang; et al. (Climate Dynamics, 2024)

Effectiveness of a novel compound microbial agent for water quality and the gut microbiota of Micropterus salmoides - Qian Li; Li-Hui Sun; Bi-Cheng Yang; Jian-Hu Jiang; Jian-Ming Chen; Gang Zheng; Ling-Mei Gao; Jun Peng; Jian-Lin Guo (Frontiers in Marine Science, 2024)
The cultivation of largemouth bass ( Micropterus salmoides ), a species of significant economic value in aquaculture, has experienced notable growth recently. However, the deterioration of water quality seriously affects the metabolic responses of M. salmoides . While compound microbial agent (CMA) is widely utilized for ecological rehabilitation and water filtration, its application in M. salmoides has not been reported. Here, based on physio-biochemical tests and 16S rRNA sequencing, we investigated the effects of CMA (yeast, Bacillus subtilis , and lactic acid bacteria) on the water quality within the recirculating aquaculture system, along with physiological indices and gut microbiota of M. salmoides . Compared to the control and single microbial agent (yeast), CMA treatment improved the water quality by improving the dissolved oxygen and delaying the increase of pH, total nitrogen, total phosphorus, ammonia nitrogen, and nitrite. The 16s rRNA gene sequencing revealed that the water treated with CMA exhibited elevated levels of chao1, Shannon, Pd, and a larger population of dominant bacterial. Besides, higher values of ACE, chao1, Shannon, and OTU level, and lower Simpson index were found in CMA treated M. salmoides samples, suggesting that CMA treatment enhanced the species richness and diversity of gut microbiota of M. salmoides . Furthermore, CMA treatment hindered the generation and proliferation of harmful bacteria, such as the Mycoplasma mobile 163K species and the Erysipelotrichaceae family, which was associated with enhanced antioxidant enzymatic activity and decreased MDA level in both the serum and liver. These findings shed light on the essential roles of CMA in M. salmoides culturing and introduce an innovative approach to enhance the aquatic environment.

New sight in arginine-improved flesh quality: Role of MRFs, cyclins, and WNT signaling in grass carp (Ctenopharyngodon idellus) - Yu-Long Ma; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Hong-Mei Ren; Rui-Nan Zhang; Shu-Wei Li; Ling Tang; Lin Feng (Aquaculture, 2024)

The effects of different drying methods on the flavor profile of wheat germ using E-nose and GC-IMS - Yang Zhong; Gexing Zhang; Fangqin Zhang; Shuting Lin; Mei Wang; Yue Sun; Jin Liang; Xueling Li (Journal of Cereal Science, 2024)

Decoding the genome of bloodsucking midge Forcipomyia taiwana (Diptera: Ceratopogonidae): Insights into odorant receptor expansion - Ming-Der Lin; Chia-Hsien Chuang; Chih-Hsin Kao; Shu-Hwa Chen; Szu-Chieh Wang; Ping-Heng Hsieh; Guan-Yu Chen; Chun-Chia Mao; Jeng-Yi Li; Mei-Yeh Jade Lu; Chung-Yen Lin (Insect Biochemistry and Molecular Biology, 2024)

Evaluation of the Efficacy of Stem Cells Therapy in the Periodontal Regeneration: A Meta-Analysis and Mendelian Randomization Study - Jing Hu; Ze-Yue Ou-Yang; Ya-Qiong Zhao; Jie Zhao; Li Tan; Qiong Liu; Min-yuan Wang; Qin Ye; Yao Feng; Meng-Mei Zhong; Ning-Xin Chen; Xiao-Lin Su; et al. (Stem Cell Reviews and Reports, 2024)

An Hsp70 promoter–based mouse for heat shock–induced gene modulation - Hangang Chen; Yangli Xie; Mei Zhang; Junlan Huang; Wanling Jiang; Ruobin Zhang; Can Li; Xiaolan Du; Hua Chen; Qiang Nie; Sen Liang; Qiaoyan Tan; et al. (Journal of Molecular Medicine, 2024)

Clinicopathological characteristics and prognosis of Epstein-Barr virus–associated gastric cancer - Lin-lin Li; Ao-yang Yu; Mei Zhu; Lu-yao Ma; Meng-han Cao; Wen-lou Liu; Xiao-bing Qin; Chao Gao; Zheng-xiang Han; Hong-mei Wang (Archives of Virology, 2024)

Experimental optimization and mechanism analysis of extracting flavonoids with the supramolecular solvents-based methods - Zhi-lu Yu; Shi-yi Hou; Li-mei Lin; Yu-ran Chu; Ya-mei Li; Zhi-min Zhang; Jing Yan; Bo-hou Xia (Sustainable Chemistry and Pharmacy, 2024)

Structurally diverse cucurbitane-type triterpenoids from the tubers of Hemsleya chinensis with cytotoxic activity - Xiao-San Li; Qi-Lin Wang; Zhi-Peng Xu; Ming-Shang Liu; Xiao-Yan Liang; Jia-Chon Zheng; Hong-Yao Deng; Li Liu; Yong-Mei Huang; Mao-Xun Yang; Xue-Mei Yang (Phytochemistry, 2024)

Two unprecedented neuroprotective 2-(2-phenylethyl)chromone derivatives from cultivated “Qi-Nan” agarwood of Aquilaria sinensis - Lin Zhang; Hao Wang; Wen-Hua Dong; Jun Zeng; Li Yang; Wei Li; Hui-Qin Chen; Jing-Zhe Yuan; Cai-Hong Cai; Zhen-Yu Li; Wen-Li Mei; Hao-Fu Dai (Phytochemistry Letters, 2024)

Molecular mechanism of efficient degradation of TPM dyes by Serratia species WKD at high temperature - Yi Wei; Xin-Jiao Dong; Gang Li; Huan Wu; Lin-Na Du; Jia-Cheng Zhou; Jun Zhang; Yan-Ping Xiao; Yue-Mei Shang; Hong-Xia Liu (International Biodeterioration & Biodegradation, 2024)

Boosting the photocatalytic hydrogen generation: The multifunctional role of NiWO4 in NiS2/NiWO4/ZnIn2S4 hollow microsphere - Songsong Xu; Junrui Wang; Chaozhi Yang; Jintao Li; Jingwen Qian; Tao Mei; Jinhua Li; Jianying Wang; Liangyou Lin; Xianbao Wang (Fuel, 2024)

PM2.5 exposure-induced senescence-associated secretory phenotype in airway smooth muscle cells contributes to airway remodeling - Pei-Pei Cheng; Fan Yu; Shuai-Jun Chen; Xiao Feng; Zi-Heng Jia; Shi-He Hu; Xiao-Lin Cui; Ya-Ya Zhou; Qian Niu; Li-Mei Liang; Meng Wang; Lin-Jie Song; et al. (Environmental Pollution, 2024)

Host-guest synergistic hydrogen bond triggered signal amplification for visualizing the plant hormone salicylic acid - A-Ling Tang; Li-Long Zhang; Shuai Tan; Ping Yang; Wei Niu; Mei-Hong Ge; Lin-Lin Yang; Pei-Yi Wang; Li-Wei Liu; Xiang Zhou; Song Yang (Chemical Engineering Journal, 2024)

Chemical structure of hydrocarbons significantly affects removal performance and microbial responses in gas biotrickling filters - Xin Wu; Yan Lin; Yongyi Wang; Mei Dai; Shaohua Wu; Xiang Li; Chunping Yang (Bioresource Technology, 2024)

CRISPR/Cas9-mediated knockout of Bsr-d1 enhances the blast resistance of rice in Northeast China - Ying Zhang; Xiu-Feng Lin; Li Li; Ri-Hua Piao; Songquan Wu; Anqi Song; Mengmeng Gao; Yong-Mei Jin (Plant Cell Reports, 2024)

3D Models of Sarcomas: The Next-generation Tool for Personalized Medicine - Ruiling Xu; Ruiqi Chen; Chao Tu; Xiaofeng Gong; Zhongyue Liu; Lin Mei; Xiaolei Ren; Zhihong Li (Phenomics, 2024)

Near-global summer circulation response to the spring surface temperature anomaly in Tibetan Plateau –– the GEWEX/LS4P first phase experiment - Yang Zhang; Yan Pan; Yongkang Xue; Ismaila Diallo; Xubin Zeng; Shuting Li; J. David Neelin; William K. M. Lau; Aaron A. Boone; Frederic Vitart; Tandong Yao; Qi Tang; et al. (Climate Dynamics, 2024)
Subseasonal to seasonal (S2S) prediction of droughts and floods is one of the major challenges of weather and climate prediction. Recent studies suggest that the springtime land surface temperature/subsurface temperature (LST/SUBT) over the Tibetan Plateau (TP) can be a new source of S2S predictability. The project “Impact of Initialized Land Surface Temperature and Snowpack on Subseasonal to Seasonal Prediction (LS4P)” was initiated to study the impact of springtime LST/SUBT anomalies over high mountain areas on summertime precipitation predictions. The present work explores the simulated global scale response of the atmospheric circulation to the springtime TP land surface cooling by 16 current state-of-the-art Earth System Models (ESMs) participating in the LS4P Phase I (LS4P-I) experiment. The LS4P-I results show, for the first time, that springtime TP surface anomalies can modulate a persistent quasi-barotropic Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train from the TP via the northeast Asia and Bering Strait to the western part of the North America, along with the springtime westerly jet from TP across the whole North Pacific basin. The TRC wave train modulated by the TP thermal anomaly play a critical role on the early summer surface air temperature and precipitation anomalies in the regions along the wave train, especially over the northwest North America and the southern Great Plains. The participant models that fail in capturing the TRC wave train greatly under-predict climate anomalies in reference to observations and the successful models. These results suggest that the TP LST/SUBT anomaly via the TRC wave train is the first order source of the S2S variability in the regions mentioned. Furthermore, the TP surface temperature anomaly can influence the Southern Hemispheric circulation by generating cross-equator wave trains. However, the simulated propagation pathways from the TP into the Southern Hemisphere show large inter-model differences. More dynamical understanding of the TRC wave train as well as its cross-equator propagation into the Southern Hemisphere will be explored in the newly launched LS4P phase II experiment.

Remote effects of Tibetan Plateau spring land temperature on global subseasonal to seasonal precipitation prediction and comparison with effects of sea surface temperature: the GEWEX/LS4P Phase I experiment - Yongkang Xue; Ismaila Diallo; Aaron A. Boone; Yang Zhang; Xubin Zeng; William K. M. Lau; J. David Neelin; Tandong Yao; Qi Tang; Tomonori Sato; Myung-Seo Koo; Frederic Vitart; et al. (Climate Dynamics, 2024)
The prediction skill for precipitation anomalies in late spring and summer months—a significant component of extreme climate events—has remained stubbornly low for years. This paper presents a new idea that utilizes information on boreal spring land surface temperature/subsurface temperature (LST/SUBT) anomalies over the Tibetan Plateau (TP) to improve prediction of subsequent summer droughts/floods over several regions over the world, East Asia and North America in particular. The work was performed in the framework of the GEWEX/LS4P Phase I (LS4P-I) experiment, which focused on whether the TP LST/SUBT provides an additional source for subseasonal-to-seasonal (S2S) predictability. The summer 2003, when there were severe drought/flood over the southern/northern part of the Yangtze River basin, respectively, has been selected as the focus case. With the newly developed LST/SUBT initialization method, the observed surface temperature anomaly over the TP has been partially produced by the LS4P-I model ensemble mean, and 8 hotspot regions in the world were identified where June precipitation is significantly associated with anomalies of May TP land temperature. Consideration of the TP LST/SUBT effect has produced about 25–50% of observed precipitation anomalies in most hotspot regions. The multiple models have shown more consistency in the hotspot regions along the Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train. The mechanisms for the LST/SUBT effect on the 2003 drought over the southern part of the Yangtze River Basin are discussed. For comparison, the global SST effect has also been tested and 6 regions with significant SST effects were identified in the 2003 case, explaining about 25–50% of precipitation anomalies over most of these regions. This study suggests that the TP LST/SUBT effect is a first-order source of S2S precipitation predictability, and hence it is comparable to that of the SST effect. With the completion of the LS4P-I, the LS4P-II has been launched and the LS4P-II protocol is briefly presented.

Associations of residential greenness exposure and ambient air pollutants with newly-diagnosed drug-resistant tuberculosis cases - Wan-mei Song; Yi Liu; Dan Men; Shi-jin Li; Ning-ning Tao; Qian-yun Zhang; Si-qi Liu; Qi-qi An; Xue-han Zhu; Qi-lin Han; Yu-zhen Zhang; Ying-ying Li; et al. (Environmental Science and Pollution Research, 2024)

Migration of phosphorus in pig manure during pyrolysis process and slow-release mechanism of biochar in hydroponic application - Ru-Qing Jiang; Guang-Wei Yu; Lin-Hui Yu; Yu Wang; Chang-Jiang Li; Zhen-Jiao Xing; Xi-Mei Xue; Yin Wang; Cheng Yu (Science of The Total Environment, 2024)

Timing of India-Asia suturing: Evidence from a remnant peripheral foreland basin in Xigaze, South Tibet - Xu-Dong Guo; Lin Ding; Qiu-yun Guan; Deng Zeng; Chao Wang; Gui-zhen Guo; Hou-Qi Wang; Mei-Yu Liu; Xiang-Li Ding; Muhammad Qasim; Ya-Hui Yue; Jing Xie; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Risk assessment of pesticide compounds: IPT and TCZ cause hepatotoxicity, activate stress pathway and affect the composition of intestinal flora in red swamp crayfish (Procambarus clarkii) - Yan-Mei Zhang; Wei-Ren Dong; Chen-Yang Lin; Wen-Bin Xu; Bang-Ze Li; Guang-Xu Liu; Miao-An Shu (Environmental Pollution, 2024)

A top-down and in situ strategy for intrinsic acicular nanostructure enhanced ultradurable superhydrophobic and anti-icing aramid fabric - Jin-Le Li; Fang Wang; Chun-Bo Li; Ren-Yi Sun; Mei-Lin Guo; Gang Wu; Fei Song; Yu-Zhong Wang (Chemical Engineering Journal, 2024)

A Potential Source of Bias in Group-Level EEG Microstate Analysis - Michael Murphy; Jun Wang; Chenguang Jiang; Lei A. Wang; Nataliia Kozhemiako; Yining Wang; Jun Wang; Chenguang Jiang; Guanchen Gai; Kai Zou; Zhe Wang; Xiaoman Yu; et al. (Brain Topography, 2024)

Genetic architecture of ecological divergence between Oryza rufipogon and Oryza nivara - Qing‐Lin Meng; Cheng‐Gen Qiang; Ji‐Long Li; Mu‐Fan Geng; Ning‐Ning Ren; Zhe Cai; Mei‐Xia Wang; Zi‐Hui Jiao; Fu‐Min Zhang; Xian‐Jun Song; Song Ge (Molecular Ecology, 2024)
Ecological divergence due to habitat difference plays a prominent role in the formation of new species, but the genetic architecture during ecological speciation and the mechanism underlying phenotypic divergence remain less understood. Two wild ancestors of rice ( Oryza rufipogon and Oryza nivara ) are a progenitor‐derivative species pair with ecological divergence and provide a unique system for studying ecological adaptation/speciation. Here, we constructed a high‐resolution linkage map and conducted a quantitative trait locus (QTL) analysis of 19 phenotypic traits using an F 2 population generated from a cross between the two Oryza species. We identified 113 QTLs associated with interspecific divergence of 16 quantitative traits, with effect sizes ranging from 1.61% to 34.1% in terms of the percentage of variation explained (PVE). The distribution of effect sizes of QTLs followed a negative exponential, suggesting that a few genes of large effect and many genes of small effect were responsible for the phenotypic divergence. We observed 18 clusters of QTLs (QTL hotspots) on 11 chromosomes, significantly more than that expected by chance, demonstrating the importance of coinheritance of loci/genes in ecological adaptation/speciation. Analysis of effect direction and v ‐test statistics revealed that interspecific differentiation of most traits was driven by divergent natural selection, supporting the argument that ecological adaptation/speciation would proceed rapidly under coordinated selection on multiple traits. Our findings provide new insights into the understanding of genetic architecture of ecological adaptation and speciation in plants and help effective manipulation of specific genes or gene cluster in rice breeding.

Effective Detection of Cu(II) Ions Based on Carbon Dots@Exfoliated Layered Double Hydroxides Composites Fluorescence Probe - Quliang Lu; Yixian Mei; Yuting Wu; Houjun Lin; YanLi Li (Journal of Fluorescence, 2024)

Heat Shock Protein 22 Attenuates Nerve Injury-induced Neuropathic Pain Via Improving Mitochondrial Biogenesis and Reducing Oxidative Stress Mediated By Spinal AMPK/PGC-1α Pathway in Male Rats - Longqing Zhang; Lin Liu; Danyang Li; Jiayi Wu; Shaojie Gao; Fanhe Song; Yaqun Zhou; Daiqiang Liu; Wei Mei (Journal of Neuroimmune Pharmacology, 2024)

Structural and functional analysis of transforming growth factor beta regulator 1 (TBRG1) in the red swamp crayfish Procambarus clarkii: The initial insight into TBRG1's role in invertebrate immunity - Chen-Yang Lin; Wen-Bin Xu; Bang-Ze Li; Miao-An Shu; Yan-Mei Zhang (Fish & Shellfish Immunology, 2024)

Scalable, bio-inspired and self-floating bi-layer polyurethane foam solar evaporator with excellent capillary hydrodynamic effect - Jing Lin; Mei Wu; Hao Fang; Mengyue Wu; Shikuo Li; Hui Zhang; Yu Jiang; Fangzhi Huang (Chemical Engineering Journal, 2024)

Unraveling fluorescent mechanism of biomass-sourced carbon dots based on three major components: Cellulose, lignin, and protein - Tian-xiang Li; De-fang Zhao; Lin Li; Yang Meng; Yu-hui Xie; Dong Feng; Feng Wu; Delong Xie; Yuxin Liu; Yi Mei (Bioresource Technology, 2024)

Metal(Loid)s in Aquatic Products and Their Potential Health Risk - Shi-Lin Hu; Xiao-Chen Chen; Ying-Xin Xue; Li-Ying Zhi; Yu-Han Yang; Yong-Guan Zhu; Xi-Mei Xue (Exposure and Health, 2024)

Oncogenic and immunological roles of RACGAP1 in pan-cancer and its potential value in nasopharyngeal carcinoma - Cheng-shan Zheng; Wei-mei Huang; Hong-mei Xia; Jing-lin Mi; Yuan-qing Li; Hui-qing Liang; Li Zhou; Zhou-xue Lu; Fang Wu (Apoptosis, 2024)

Three new cardenolides from the fruits of Cascabela thevetia (L.) Lippold and their cytotoxic activities - Juan Long; Jia-Cheng Ouyang; Yu-Hao Luo; Qi-Jing Wu; Xiao-Tong Liao; Zhi-Le Chen; Qi-Lin Wang; Xiao-Yan Liang; Li Liu; Xue-Mei Yang; Xiao-San Li (Natural Product Research, 2024)

The dynamic mechanism of scientific and technological innovation in China’s marine biomedical industry - Xiu-Mei Fu; Yan-Xin Tan; Ying Liu; Ying-Hui Han; Qiao-Qiao Qi; Jing-Hang Li; Chun-Yu Lin (Frontiers in Marine Science, 2024)
As one of the important forces promoting the development of the marine economy, the marine biomedical industry (MBI) shows typical knowledge and technology-intensive characteristics. It is of great significance to explore the industrial innovation dynamic mechanism for breaking through the bottleneck of innovative development as well as achieving high-quality development. This paper constructed a system dynamics model for scientific and technological innovation (STI) in the MBI and then explored the dynamic mechanism of STI in the industry through simulation. The study found that, in the innovation environment subsystem, the two factors of the intellectual property protection intensity and the government’s scientific research funding input had the most significant positive driving effects on STI of the MBI; the promotion of government education funding input showed a significant strengthening trend over time, while the marine environmental regulation intensity had comparatively little effect on the level of STI. In the subsystem of innovation input, both innovation funding input and innovation personnel input were the direct driving forces for the improvement of the STI level. And enterprises played a dominant role in STI because the STI level of the MBI was more sensitive to the changes in enterprise innovation input. Compared with the individual factor input, the synergistic promotion effect of multiple factors is more significant. In addition, it was found that there was a low conversion rate of scientific research achievements in China’s MBI by analyzing the influence of various factors changing on technological output and economic output. Based on the research results, this paper puts forward corresponding policy suggestions in order to provide theoretical support and a practical basis for promoting the technological innovation level of China’s MBI as well as references for other countries.

Anthropogenic nitrogen pollution inferred by stable isotope records of crustose coralline algae - Aafaq Nazir; Chiao-Feng Lai; Shih-Wei Wang; Showe-Mei Lin; Hong-Chun Li; Ming-Tsung Chung; Pei-Ling Wang; Yung-Che Tseng; Jen-Chieh Shiao (Marine Pollution Bulletin, 2024)

Aridity drives the variability of desert soil microbiomes across north-western China - Lei Dong; Mei-Xiang Li; Shuai Li; Ling-Xiang Yue; Mukhtiar Ali; Jia-Rui Han; Wen-Hui Lian; Chao-Jian Hu; Zhi-Liang Lin; Guo-Yuan Shi; Pan-Deng Wang; Shao-Ming Gao; et al. (Science of The Total Environment, 2024)

Correlation between pyrethroid knockdown resistance and mutation frequency of voltage-gated sodium channel and its application in Aedes aegypti management - Hsin-Hua Lin; Zhong-Tai Li; Hau-You Tzeng; Cheng Chang; Shu-Mei Dai (Pesticide Biochemistry and Physiology, 2024)

The clinical trajectory of peripheral blood immune cell subsets, T-cell activation, and cytokines in septic patients - Xuan Lu; Cong-Ying Song; Ping Wang; Li Li; Li-Ying Lin; Shuai Jiang; Jia-Ning Zhou; Meng-Xiao Feng; Yun-Mei Yang; Yuan-Qiang Lu (Inflammation Research, 2024)

Improvement of flesh quality, muscle growth and protein deposition in adult grass carp (Ctenopharyngodon idella): The role of tryptophan - Lu-Qiao Xiao; Wei-Dan Jiang; Pei Wu; Yang Liu; Hong-Mei Ren; Ling Tang; Shu-Wei Li; Cheng-Bo Zhong; Rui-Nan Zhang; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2023)

Enhanced expression of RAGE/NADPH oxidase signaling pathway and increased level of oxidative stress in brains of rats with chronic fluorosis and the protective effects of blockers - Yan-Lin Ma; Jie Deng; Ting Zhang; Hong-Mei Li; Qiu-Zhe Liang; Kai-Lin Zhang (Journal of Trace Elements in Medicine and Biology, 2023)

Selective and efficient production of 1,5-pentanediol from tetrahydrofurfuryl alcohol using Ni-La(OH)3 catalysts - Wenqi Zhao; Xiaowei Bai; Xiangrui Lin; Yalkunjan Tur sun; Mei Zhong; Zhenghua Dai; Jian Li (Fuel, 2023)

The improvement of sodium dodecyl sulfate on the electrospinning of gelatin O/W emulsions for production of core-shell nanofibers - Jinming Dai; Mei Bai; Changzhu Li; Haiying Cui; Lin Lin (Food Hydrocolloids, 2023)

The inhibition effect and mechanism of litsea cubeba essential oil on the hemolytic activity of listeriolysin O - Mei Bai; Jinming Dai; Wei Hu; Changzhu Li; Haiying Cui; Lin Lin (Food Bioscience, 2023)

The first identification and functional analysis of two drosophila mothers against decapentaplegic protein genes (SpSmad1 and SpSmad2/3) and their involvement in the innate immune response in Scylla paramamosain - Bang-ze Li; Chen-yang Lin; Wen-bin Xu; Yan-mei Zhang; Qing-jun Shao; Wei-ren Dong; Miao-an Shu (Fish & Shellfish Immunology, 2023)

Spatial bandgap tailoring via a novel injection chemical bath deposition enables highly efficient carbon-based Sb2(S,Se)3 thin film solar cells - Peng Tang; Zi-Heng Huang; You-Xian Chen; Hu Li; Li-Quan Yao; Hui Li; Li-Mei Lin; Jin-Rui Cai; Ya-Lu Zhan; Dong Wei; Shui-Yuan Chen; Da-Qin Chen; et al. (Chemical Engineering Journal, 2023)

CDK6 is a novel predictive and prognosis biomarker correlated with immune infiltrates in multiple human neoplasms, including small cell lung carcinoma - Guo-Sheng Li; Zhi-Guang Huang; Dong-Ming Li; Yu-Lu Tang; Jin-Hua Zheng; Lin Yang; Yue Feng; Jun-Xi Peng; Jing-Xiao Li; Yu-Xing Tang; Neng-Yong Zeng; Mei-Hua Jin; et al. (Functional & Integrative Genomics, 2023)

Estimation of soil organic matter by in situ Vis-NIR spectroscopy using an automatically optimized hybrid model of convolutional neural network and long short-term memory network - Xiaoqing Wang; Mei-Wei Zhang; Qian Guo; Hua-Lei Yang; Hui-Li Wang; Xiao-Lin Sun (Computers and Electronics in Agriculture, 2023)

Dual roles of the Arabidopsis PEAT complex in histone H2A deubiquitination and H4K5 acetylation - Si-Yao Zheng; Bin-Bin Guan; Dan-Yang Yuan; Qiang-Qiang Zhao; Weiran Ge; Lian-Mei Tan; Shan-Shan Chen; Lin Li; She Chen; Rui-Ming Xu; Xin-Jian He (Molecular Plant, 2023)

Bibliometric analysis of publications on biodegradation of plastics: Explosively emerging research over 70 years - Shan-Shan Yang; Wei-Min Wu; Ji-Wei Pang; Lei He; Meng-Qi Ding; Mei-Xi Li; Yi-Lin Zhao; Han-Jun Sun; De-Feng Xing; Nan-Qi Ren; Jun Yang; Craig S. Criddle; et al. (Journal of Cleaner Production, 2023)

3D hierarchical fireproof gel polymer electrolyte towards high-performance and comprehensive safety lithium-ion batteries - Yirou Du; Xianshuai Liu; Lin Chen; Sihao Yin; Yuhui Xie; Ao Li; Xiaodong Liang; Yong Luo; Feng Wu; Yi Mei; Delong Xie (Chemical Engineering Journal, 2023)

Dextran-based micelles for combinational chemo-photodynamic therapy of tumors via in vivo chemiluminescence - Chendi Ding; Zhaoqing Shi; Meitong Ou; Yingbang Li; Li Huang; Wenyan Wang; Qili Huang; Meihang Li; Chunbo Chen; Xiaowei Zeng; Hongzhong Chen; Lin Mei (Carbohydrate Polymers, 2023)

Hybrid chain reaction and selective recognition-based homogeneous dual-fluorescence analysis of circulating tumor cells in clinical ovarian cancer samples - Qian Hu; Dan Tang; Mei Li; Xiaodu Liang; Juan Zhou; Yanming Meng; Yinhao Wei; Shixin Yan; Ruoyu Lin; Xiaoyu Niu; Lin Zhang (Analytica Chimica Acta, 2023)

Diffusion kurtosis imaging tractography reveals disrupted white matter structural networks in children with obstructive sleep apnea syndrome - Yanhua Li; Hongwei Wen; Wenfeng Li; Yun Peng; Hongbin Li; Jun Tai; Tingting Ji; Lin Mei; Yue Liu (Brain Imaging and Behavior, 2023)

Bi0·5Na0·5TiO3/ZnO Z-scheme heterojunction for piezo-photocatalytic water remediation: Mechanical energy harvesting and energy band configuration - Peng Wang; Wanqian Cai; Fangyuan Yu; Ping Zhou; Mei Lin; Cong Lin; Tengfei Lin; Min Gao; Chunlin Zhao; Xiangqi Li; Xiao Wu (Chemosphere, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

On conflict of natural resources-carbon emissions nexus in China: The role of economic policy uncertainty - Maoran Ye; Ling Tang; Lin Huang; Mei Li (Resources Policy, 2023)

Dietary threonine improves muscle nutritional value and muscle hardness associated with collagen synthesis in grass carp (Ctenopharyngodon idella) - Mei-Lan Wen; Pei Wu; Wei-Dan Jiang; Yang Liu; Cai-Mei Wu; Cheng-Bo Zhong; Shu-Wei Li; Ling Tang; Lin Feng; Xiao-Qiu Zhou (Food Chemistry, 2023)

Modulating the coordination environment of Co single-atom catalysts through sulphur doping to efficiently enhance peroxymonosulfate activation for degradation of carbamazepine - Wei Zhang; Mu Li; Jingwen Luo; Guan Zhang; Lin Lin; Feiyun Sun; Mei Li; Zijun Dong; Xiao-yan Li (Chemical Engineering Journal, 2023)

A comprehensive analysis of the Bencao (herbal) small RNA Atlas reveals novel RNA therapeutics for treating human diseases - Yinghao Cao; Yexuan Lin; Na Sun; Xinyi Du; Yixin Dong; Song Mei; Xingyu Deng; Xiaobei Li; Shaoting Guo; Kegong Tang; Jiaqi Liu; Xiangyu Qiao; et al. (Science China Life Sciences, 2023)

Three new compounds with their anti-glioma effects from the roots of Arnebia guttata Bunge - Yu-Mei Yan; Lin-Jun Zou; Min-Hui Li; Zhao-Cui Sun; Min Zhang; Xu-Dong Xu; Chun-Hong Zhang (Natural Product Research, 2023)

Optical properties and molecular composition of wintertime atmospheric water-soluble organic carbon in different coastal cities of eastern China - Haibiao Chen; Caiqing Yan; Qinglong Fu; Xinfeng Wang; Jiao Tang; Bin Jiang; Honglei Sun; Tiancheng Luan; Qiaoyun Yang; Qianbiao Zhao; Jun Li; Gan Zhang; et al. (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Selenium alleviates biological toxicity of thiamethoxam (TMX): Bioaccumulation of TMX, organ damage, and antioxidant response of red swamp crayfish (Procambarus clarkii) - Yan-Mei Zhang; Wen-Bin Xu; Chen-Yang Lin; Bang-Ze Li; Miao-An Shu (Journal of Hazardous Materials, 2023)

Antibacterial and antibiofilm performance of low-frequency ultrasound against Escherichia coli O157:H7 and its application in fresh produce - Mei Bai; Jinming Dai; Changzhu Li; Haiying Cui; Lin Lin (International Journal of Food Microbiology, 2023)

A novel bacteriocin RSQ01 with antibacterial activity and its application and metabolomic mechanism in milk preservation - Yan-Mei Zhang; Lin-Yu Yang; Jian-Ping Ying; Chao-Min Fu; Gang Wu; Xiao-Ran Li; Qi-Lin Zhang (Food Control, 2023)

Maternal di-(2-ethylhexyl) phthalate exposure elicits offspring IFN-λ upregulation: Insights from birth cohort, murine model, and in vitro mechanistic analysis - Fu-Chen Kuo; Mei-Lan Tsai; Shin-Ting Wu; Sih-Syuan Li; Chia-Fang Wu; Shu-Lin Wang; Michael W.Y. Chan; Jau-Ling Suen; Ming-Tsang Wu; Chih-Hsing Hung (Food and Chemical Toxicology, 2023)

Identification and functional analysis of cytosolic phospholipase A2 (cPLA2) from the red swamp crayfish Procambarus clarkii: The first evidence of cPLA2 involved in immunity in invertebrates - Chen-Yang Lin; Wen-Bin Xu; Bang-Ze Li; Miao-An Shu; Yan-Mei Zhang (Fish & Shellfish Immunology, 2023)

Evaluation of the impacts of ozone on the vegetation productivity of woodland and grassland ecosystems in China - WANG Qinyi; HUANG Mei; WANG Shaoqiang; CHEN Bin; LIU Zhenhai; WANG Zhaosheng; CHEN Shiliang; LI Hui; ZHU Tongtong; LI Donghui; LI Yuelin; Lin Hu; et al. (Ecological Modelling, 2023)

The associations of non-essential metal mixture with fasting plasma glucose among Chinese older adults without diabetes - Jing-Yuan Lei; Pan-Pan Wang; Hong-Li Wang; Yuan Wang; Liang Sun; Bing Hu; Su-Fang Wang; Dong-Mei Zhang; Gui-Mei Chen; Chun-Mei Liang; Fang-Biao Tao; Lin-Sheng Yang; et al. (Environmental Science and Pollution Research, 2023)

Antimony(III) removal by biogenic manganese oxides formed by Pseudomonas aeruginosa PA-1: kinetics and mechanisms - Qing Li; Yun He; Aijiang Yang; Xia Hu; Fang Liu; Jincheng Mu; Shixue Mei; Lin-Ping Yang (Environmental Science and Pollution Research, 2023)

Effects of dietary starch and metformin levels on the growth performance, body composition, hepatic glycolipid metabolism, and liver histology of juvenile largemouth bass Micropterus salmoides - Qin-Qin Liu; Ru Xia; Xin Deng; Hui-Jun Yang; Li Luo; Shi-Mei Lin; Chuan-Jie Qin; Yong-Jun Chen (Aquaculture, 2023)

Genomic analysis of Marinomonas algicola SM1966T reveals its role in marine sulfur cycling - Min Zhang; Xiao-Di Wang; Yue Lin; Shu-Yan Wang; Shan Zhang; Jin Cheng; Mei-Ling Sun; Peng Wang; Hui-Hui Fu; Chun-Yang Li; Nan Zhang (Marine Genomics, 2023)

Variations of methane fluxes and methane microbial community composition with soil depth in the riparian buffer zone of a sponge city park - Ru Xue; Ke Zhang; Xiaoling Liu; Bing Jiang; Hongbing Luo; Mei Li; You Mo; Cheng Liu; Lin Li; Liangqian Fan; Wei Chen; Lin Cheng; et al. (Journal of Environmental Management, 2023)

Detection of walnut oil adulterated with high-linoleic acid vegetable oils using triacylglycerol pseudotargeted method based on SFC-QTOF-MS - Jing-Jing Zhang; Yan Gao; Mei-Ling Zhao; Xiao Xu; Bo-Nan Xi; Li-Ke Lin; Jing-Yi Zheng; Bang Chen; Yu Shu; Cong Li; Yehua Shen (Food Chemistry, 2023)

Mechanism of eugenol inhibiting the growth of vegetative cells and spores of Bacillus cereus and its application in rice cakes - Haiying Cui; Mei Yang; XiaoChen Chen; Changzhu Li; Lin Lin (Food Bioscience, 2023)

Controlled deposition via a bifunctional layer enables dendrite-free zinc metal batteries - Han Wang; Quanyu Li; Shaozhen Huang; Liangjun Zhou; Lin Mei; Zhibin Wu; Baihua Qu; Weifeng Wei; Xiaobo Ji; Yuejiao Chen; Libao Chen (Chemical Engineering Journal, 2023)

Two new isoflavones from the barks of Dalbergia hancei Benth - Xiao-Mei Li; Nao Pang; Ya-Feng Wang; Rui-Jie He; Li Ge; Bing-Yuan Yang; Ke-Di Yang; Yong-Lin Huang (Natural Product Research, 2023)

A novel DVAPSO-LSTSVM classifier in compressed sensing domain for intelligent pipeline leakage diagnosis - Shuaiyong Li; Zhengxu Dai; Mengqian Cai; Liang Liu; Lin Mei (Process Safety and Environmental Protection, 2023)

Establishment of a lipopolysaccharide-induced inflammation model of human fetal colon cells - Keqi Yu; Shengtao Liao; Chuanfei Li; Ya Song; Zhechuan Mei; Lin Lv (Molecular Biology Reports, 2023)

Phylogenetic divergence associated with climate oscillations and topology illustrates the dispersal history of Formosan sambar deer (Rusa unicolor swinhoii) in Taiwan - Kuan-Yi Li; Chen Hsiao; Shih-Ching Yen; Chien-Yi Hung; You-Zhu Lin; Sheng-Wun Jheng; Pei-Ju Yu; Mei-Hsiu Hwang; Guo-Jing Weng; Ku-Lin Chen; Shu-Fen Lin; Shih-Wei Chang; et al. (Mammal Research, 2023)
The island of Taiwan represents an ideal context for studying the effects of climatic oscillations and topographic variation on large herbivores due to its varied tropical to sub-tropical climate zones at different elevational ranges. We explored the phylogenetics of Formosan sambar deer ( Rusa unicolor swinhoii ) using the control region of the mitochondrial genome. We detected 18 haplotypes among 454 sequences across the island and grouped them into six regions based on SAMOVA, with 68.78% variance among regions. A Bayesian phylogenetic dendrogram revealed two spatially segregated genetic clades. Neutrality tests and Bayesian skyline plots uncovered different demographic expansion histories for the two clades. We further tested divergence times and chronology to propose potential phylogenetic scenarios, which were examined using approximate Bayesian computation. Finally, we present a credible hypothesis for a glacial refugium in the northern part of the Central Mountain Range. Subsequent secondary contact between the two clades during interglacial periods has led to the extant genetic structure of Formosan sambar deer.

Aflatoxin B1 exposure induced developmental toxicity and inhibited muscle development in zebrafish embryos and larvae - Xiang-Ning He; Pei Wu; Wei-Dan Jiang; Yang Liu; Sheng-Yao Kuang; Ling Tang; Hong-Mei Ren; Hua Li; Lin Feng; Xiao-Qiu Zhou (Science of The Total Environment, 2023)

Preparation and characterization of gelatin active packaging film loaded with eugenol nanoparticles and its application in chicken preservation - Lin Lin; Canchao Mei; Ce Shi; Changzhu Li; Mohamed A. Abdel-Samie; Haiying Cui (Food Bioscience, 2023)

Antibacterial properties of citral against Staphylococcus aureus: From membrane damage to metabolic inhibition - Jinming Dai; Mei Bai; Changzhu Li; Wai San Cheang; Haiying Cui; Lin Lin (Food Bioscience, 2023)

Artificial intelligence and visual analytics in geographical space and cyberspace: Research opportunities and challenges - Min Chen; Christophe Claramunt; Arzu Çöltekin; Xintao Liu; Peng Peng; Anthony C. Robinson; Dajiang Wang; Josef Strobl; John P. Wilson; Michael Batty; Mei-Po Kwan; Maryam Lotfian; et al. (Earth-Science Reviews, 2023)

Experimental and numerical study of micro-tubular direct carbon solid oxide fuel cell fueled by the oilseed rape straw-derived biochar - Tingting Han; Yujiao Xie; Lin Li; Ke Miao; Yu Mei; Jian Song; Jinjin Zhang; Xiuxia Meng; Ngie Hing Wong; Jaka Sunarso; Fangyong Yu; Naitao Yang (Chemical Engineering Journal, 2023)

Palladium-catalyzed Sonogashira coupling to synthesis of gem‑difluoroenynes - Lin Li; Yan Mei; Junlei Zhang; Kehan He; Fei Pan (Journal of Fluorine Chemistry, 2023)

Microplastics affect arsenic bioavailability by altering gut microbiota and metabolites in a mouse model - Shan Chen; Jin-Lei Yang; Yao-Sheng Zhang; Hong-Yu Wang; Xin-Ying Lin; Rong-Yue Xue; Meng-Ya Li; Shi-Wei Li; Albert L. Juhasz; Lena Q. Ma; Dong-Mei Zhou; Hong-Bo Li (Environmental Pollution, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Cadmium mobility and health risk assessment in the soil-rice-human system using in vitro biaccessibility and in vivo bioavailability assay: Two year field experiment - Qiang Lin; Yasir Hamid; Haijun Yang; Jianfeng Jiang; Anqi Shan; Mei Wang; Bilal Hussain; Ying Feng; Tingqiang Li; Zhenli He; Xiaoe Yang (Science of The Total Environment, 2023)

Effects of low salinity stress on osmoregulation and gill transcriptome in different populations of mud crab Scylla paramamosain - Wen-Bin Xu; Yan-Mei Zhang; Bang-Ze Li; Chen-Yang Lin; Da-Yong Chen; Yuan-Xin Cheng; Xiao-Ling Guo; Wei-Ren Dong; Miao-An Shu (Science of The Total Environment, 2023)

Click-crosslinked in-situ hydrogel improves the therapeutic effect in wound infections through antibacterial, antioxidant and anti-inflammatory activities - Xiong-Xin Lei; Chen-Yu Zou; Juan-Juan Hu; Yan-Lin Jiang; Xiu-Zhen Zhang; Long-Mei Zhao; Tao He; Qing-Yi Zhang; Ya-Xing Li; Jesse Li-Ling; Hui-Qi Xie (Chemical Engineering Journal, 2023)

Platycodon grandiflorus subjected to full- and restricted-water regimes show differential biosynthesis of triterpenoid saponins - Min Li; Lin Cheng; Meng Zhang; Li Min Yang; Mei Han (Acta Physiologiae Plantarum, 2023)

Hyperbaric Oxygen Therapy Attenuated the Motor Coordination and Cognitive Impairment of Polyglutamine Spinocerebellar Ataxia SCA17 Mice - Meng-Ke Chiang; Ta-Chun Lin; Keng-Hsuan Lin; Ya-Chin Chang; Hsiu Mei Hsieh-Li; Dar-Ming Lai (The Cerebellum, 2023)

Genome-wide identification, structural and evolutionary characteristics, and expression analysis of aquaporin gene family members in Mercenaria mercenaria - Cong Zhou; Zhi-shu Lin; Ying Shi; Jie Feng; Zhi Hu; Mei-jie Yang; Pu Shi; Yong-ren Li; Yong-jun Guo; Tao Zhang; Hao Song (Frontiers in Marine Science, 2023)
Aquaporins (AQPs) are highly-selective transmembrane water transporters that are involved in the adaptation to environmental challenges. However, the structure, function, and evolution of AQPs in bivalves remain largely unknown. In this study, AQP gene family members were identified in nine bivalve species, and their abundance rangs from 7 to 15. Nine AQPs (MmAQPs) were identified in the genome of hard clam ( Mercenaria mercenaria ), which is a euryhaline bivalve that has evolved sophisticated osmoregulatory mechanisms and salinity adaptation. Structurally, all MmAQPs contain 6 or 12 transmembrane α-helices, a major intrinsic protein (MIP) domain, and 2 asparagine-proline-alanine (NPA) motifs. MmAQPs were classified into three subfamilies based on phylogenetic analysis: AQP1-like, AQP3-like, and AQP8-like. No AQP11-like subfamily member was identified in the genome of hard clam. Tandem duplication resulted in a lineage-specific expansion in AQP8-like subfamily in hard clams. MmAQP8 genes showed different expression sensitivity to different environmental stressors. The gene expression patterns of three MmAQP8 were similar under heat, hypoxia, and air exposure stress, but differed greatly under salinity stress, indicating that tandem duplication events may accelerate the functional divergence of AQP8 genes in hard clams. AQP3-like members may have undergone gene loss during evolution, resulting in weakened glycerol and urea penetration in hard clams. Three orthologs of MmAQPs were detected in the genomes of Cyclina sinensis and Archivesica marissinica through synteny analyses. Tissue expression profiles showed that MmAQP genes were highly expressed in the foot and hepatopancreas. Under environmental stress, the expression levels of most of the MmAQP genes changed significantly to maintain metabolic homeostasis. Several MmAQP genes were downregulated to reduce water permeability under salinity and air exposure stress. Several MmAQP genes were significantly upregulated to promote the transmembrane transport of ammonia and reactive oxygen species and activate anti-apoptotic responses to resist stress. This study provides a comprehensive understanding of the AQP gene family in hard clams, and lays a foundation for further studies to explore the functions of AQPs in bivalves.

Dispersal limitation and host selection drive geo-specific and plant-specific differentiation of soil bacterial communities in the Tibetan alpine ecosystem - Sai Qu; Congcong Shen; Lin Zhang; Jichen Wang; Li-Mei Zhang; Baodong Chen; Guo-Xin Sun; Yuan Ge (Science of The Total Environment, 2023)

Environmentally-friendly biorecovery of manganese from electrolytic manganese residue using a novel Penicillium oxalicum strain Z6-5-1: Kinetics and mechanism - Shuai Zhao; Bo-Wen Zheng; Yu-Cang Wang; Fei He; Li-Juan Wang; Xiong Lin; Xue-Mei Luo; Jia-Xun Feng (Journal of Hazardous Materials, 2023)

Effect of antifreeze protein on the quality and microstructure of frozen chicken breasts - Junlin Chen; Yaqi Fan; Xingguo Zhang; Zimeng Yuan; Hairu Zhang; Xinglian Xu; Jun Qi; Guoyuan Xiong; Lin Mei; Yuan Zhu; Linwei Yang; Chao Li (Food Chemistry, 2023)

Comparison of tropomyosin released peptide and epitope mapping after in vitro digestion from fish (Larimichthys crocea), shrimp (Litopenaeus vannamei) and clam (Ruditapes philippinarum) through SWATH-MS based proteomics - LiLi Xu; Xiao Mei Zhang; Yun Qi Wen; Jin Long Zhao; Tong Cheng Xu; Ling Yong; Hong Lin; Hong Wei Zhang; Zhen Xing Li (Food Chemistry, 2023)

P2X7Rs: new therapeutic targets for osteoporosis - Haoyun Huang; Yu-Mei He; Miao-Miao Lin; Yanchao Wang; Xiaomei Zhang; Li Liang; Xueling He (Purinergic Signalling, 2023)
Increasing evidence suggests that both the occurrence and progression of osteoporosis are associated with inflammation, especially in primary osteoporosis. The maintenance of skeletal homeostasis is dependent on the complex regulation of bone metabolism. Numerous evidence suggested that purinoceptor networks are essential for bone homeostasis. In this review, the relationship between inflammation and the development of osteoporosis and the role of P2X7 receptor (P2X7R) in regulating the dynamic regulation of bone reconstruction were covered. We also discussed how P2X7R regulates the balance between resorption and bone formation by osteoblasts and reviewed the relevance of P2X7R polymorphisms in skeletal physiology. Finally, we analyzed potential targets of P2X7R for osteoporosis.

Sex difference on fibroblast growth factors (FGFs) expression in skin and wound of streptozotocin(STZ)-induced type 1 diabetic mice - Nuo-qi Wang; Wei-hua Jia; Lin Yin; Na Li; Mei-dai Liang; Jia-min Shang; Bi-yu Hou; Li Zhang; Gui-fen Qiang; Guan-hua Du; Xiu-ying Yang (Molecular Biology Reports, 2023)

Fumigation activity of essential oils of Cinnamomum loureirii toward red imported fire ant workers - Huanling Xing; Yingqi Hu; Liupeng Yang; Jianhao Lin; Haiyi Bai; Yanqun Li; Rezwan Tanvir; Ling Li; Mei Bai; Zhixiang Zhang; Hanhong Xu; Hong Wu (Journal of Pest Science, 2023)

Distribution and physical–biological controls of dimethylsulfide in the western tropical Indian Ocean during winter monsoon - Shi-Mei Liang; Xing Zhai; Cheng-Xuan Li; Ming Xin; Ping Sun; Xuan-Li Liu; Lin Liu; Bao-Dong Wang (Frontiers in Marine Science, 2023)
New field observation on distribution, turnover, and sea–air flux of three dimethylated sulfur compounds (dimethylsulfide (DMS), dimethylsulfoniopropionate, and dimethylsulfoxide) in the western tropical Indian Ocean (WTIO; 4°N–10°S, 61°–65°E) were conducted under the major Global Change and Air–Sea Interaction Program during the 2021/2022 Northeast Monsoon (December 21, 2021 to January 11, 2022). Significantly high surface concentrations of DMS were identified in the region of the Seychelles–Chagos Thermocline Ridge (SCTR; 5°–10°S). This occurred because the shallow thermocline/nitracline and associated upwelling fueled biological production of DMS in the subsurface, which was brought to the surface through vertical mixing. The calculated sea–air DMS flux was also significantly strong in the SCTR region during the Northeast Monsoon owing to combination of high wind speed and high surface concentration of DMS. This finding is similar to results obtained previously during the Southwest Monsoon, suggesting that the SCTR region is an area of active DMS emission during both the Northeast Monsoon and the Southwest Monsoon. Microbial consumption was the dominant pathway of DMS removal, accounting for 74.4% of the total, whereas the processes of photolysis (17.7%) and ventilation (7.9%) were less important. Future work should be undertaken in the WTIO to establish how DMS emission is linked to aerosol properties and climate change.

A new species of Caulophacus (Hexactinellida: Lyssacinosida: Rossellidae) from the western Pacific Ocean, with new insights into the mitochondrial genome characteristics of hexactinellid sponges - Lin Gong; Mei Yang; Dorte Janussen; Martin Dohrmann; Xinzheng Li (Frontiers in Marine Science, 2023)
A new species, belonging to the rossellid subfamily Lanuginellinae Gray, 1872, is described based on two specimens collected from two different seamounts in the western Pacific Ocean. Species characterization was approached by analyzing the morphological and skeletal features as well as the complete mitochondrial genome. Caulophacus ( Caulodiscus ) iocasicus sp. nov. is distinguishable from its congeners by its branched external shape and a unique combination of microscleres. It only has hemionychohexasters while other C . ( Caulodiscus ) species additionally have either onychohexasters or discohexasters. Furthermore, the new species has microhexactins, which have not been reported from the other six species of C . ( Caulodiscus ). Regarding the mitochondrial genome, the occurrence of the atp8 gene, the absence of tRNA E , the translocation of tRNA D between cob and nad6 , and the rearrangement of nad6 - nad4 distinguish the new species from other rossellids and even other hexactinellids for which mitogenomic information is available. The herein revised morphological and molecular information of the genus Caulophacus also suggests that the monospecific subgenus C. ( Caulophacella ) should be removed from Caulophacus and reinstated as a separate genus in the subfamily Lanuginellinae.

Vitamin D serves as a modulator of immune organs in grass carp (Ctenopharyngodon idella) infected with Aeromonas hydrophila - Yao Zhang; Chao-Nan Li; Wei-Dan Jiang; Pei Wu; Yang Liu; Sheng-Yao Kuang; Ling Tang; Shu-Wei Li; Xiao-Wan Jin; Hong-Mei Ren; Xiao-Qiu Zhou; Lin Feng (Aquaculture, 2023)

Enhancements in flavor substances, mouthfeel characteristics and collagen synthesis in the muscle of sub-adult grass carp (Ctenopharyngodon Idella): Application of a dietary lysine nutrition strategy - Yan-Jie Tang; Lin Feng; Wei-Dan Jiang; Pei Wu; Yang Liu; Lu Zhang; Sheng-Yao Kuang; Hong-Mei Ren; Xiao-Wan Jin; Shu-Wei Li; Hai-Feng Mi; Xiao-Qiu Zhou (Aquaculture, 2023)

Contaminant characterization at pesticide production sites in the Yangtze River Delta: Residue, distribution, and environmental risk - Mei Li; Qiang Chen; Lu Yang; Ya Zhang; Jinlin Jiang; Shaopo Deng; Jinzhong Wan; Tingting Fan; Tao Long; Shengtian Zhang; Yusuo Lin (Science of The Total Environment, 2023)

Characterization of fibroblast growth factor receptor 4 (FGFR4) from the red swamp crayfish Procambarus clarkii and its role in antiviral and antimicrobial immune responses - Yan-Mei Zhang; Chen-Yang Lin; Bang-Ze Li; Wen-Bin Xu; Wei-Ren Dong; Miao-An Shu (Journal of Invertebrate Pathology, 2023)

Hydrogen-bond induced enhanced emission ratiometric fluorescent handy needle for visualization assay of amoxicillin by smartphone sensing platform - Lingfei Li; Liang Yang; Dan Lin; Shihao Xu; Chunsheng Mei; Shaoming Yu; Changlong Jiang (Journal of Hazardous Materials, 2023)

Associations between maternal phthalate exposure and neonatal neurobehaviors: The Taiwan maternal and infant cohort study (TMICS) - Hsing-Kang Chen; Shu-Li Wang; Yu-Hsun Chang; Chien-Wen Sun; Ming-Tsang Wu; Mei-Lien Chen; Yu-Jie Lin; Chia-Jung Hsieh (Environmental Pollution, 2023)

Short-Term Limited Water Irrigation Influences the Photosynthetic Pigments, Enzymatic and Non-Enzymatic Activities in Saccharum spontaneum L. at Vegetative Stage - Zhi-Nian Deng; Hai-Rong Huang; Cheng-Mei Huang; Krishan K. Verma; Hai-Bin Luo; Sheng-Li Jiang; Yi-Jie Li; Hui-Qing Cao; Kai-Chao Wu; Lin Xu (Sugar Tech, 2023)

Plastome evolution and phylogenomics of Impatiens (Balsaminaceae) - He Qiu; Zhi-Hui Zhang; Mei-Zhen Wang; Xin-Jie Jin; Jie-Dong Lin; Hans Peter Comes; Jing-Xuan Chen; Rui-Ning Cui; Ru-Qing Duan; Pan Li (Planta, 2023)

In situ phytostabilization of arable soils severely contaminated with cadmium at Yangshuo, Southern China, using cash crops and amendments: a comprehensive performance evaluation - Bo-Fang Yan; Mei-Lin Yan; Xue Xiao; Rong-Liang Qiu; Yuan-Qing Chao; Yin-Xin Li; Su-Lian Lv; Zhong-Xin Tan; Ye-Tao Tang (Journal of Soils and Sediments, 2023)

The interaction of MC3R and MC4R with MRAP2a in rainbow trout (Oncorhynchus mykiss) - Hui-Xia Yu; Yang Li; De-Bin Zhong; Xin Ren; Hao-Lin Mo; Ze-Bin Jiang; Jia-Jia Yu; Dong-Mei Xiong; Hai-Xia Liu; Li-Xin Wang (Fish Physiology and Biochemistry, 2023)

Phosphorus availability mediates plant–plant interaction and field productivity in maize-grass pea intercropping system: Field experiment and its global validation - Shuang-Guo Zhu; Hong-Yan Tao; Wen-Bo Li; Rui Zhou; Yan-Wen Gui; Li Zhu; Xiao-Lin Zhang; Wei Wang; Bao-Zhong Wang; Fu-Jian Mei; Hao Zhu; You-Cai Xiong (Agricultural Systems, 2023)

Prenatal titanium exposure and child neurodevelopment at 1 year of age: A longitudinal prospective birth cohort study - Yangqian Jiang; Yongyue Wei; Wenhui Guo; Jiangbo Du; Tao Jiang; Hongxia Ma; Guangfu Jin; Ting Chen; Rui Qin; Shiyao Tao; Qun Lu; Hong Lv; et al. (Chemosphere, 2023)

Comparative transcriptome analysis of early sexual differentiation in the male and female gonads of common carp (Cyprinus carpio) - Mei Wang; Lin Chen; Zhixiong Zhou; Junzhu Xiao; Baohua Chen; Peihong Huang; Chengyu Li; Yaguo Xue; Ruoting Liu; Yulin Bai; Mengzhen Yan; Shuimu Hu; et al. (Aquaculture, 2023)

The beneficial effects of exogenous protease K originated from Parengyodontium album on growth performance of grass carp (Ctenopharyngodon idella) in relation to the enhanced intestinal digestion and absorption capacities - Ling Feng; Lin Feng; Wei-Dan Jiang; Yang Liu; Lu Zhang; Sheng-Yao Kuang; Hong-Mei Ren; Xiao-Wan Jin; Shu-Wei Li; Hai-Feng Mi; Xiao-Qiu Zhou; Pei Wu (Aquaculture, 2023)

Bioaccumulation of Cd and comparative transcriptome analysis after the antagonism of Se in the hepatopancreas of estuary mud crab (Scylla paramamosain) - Yan-Mei Zhang; Chen-Yang Lin; Bang-Ze Li; Wei-Ren Dong; Miao-An Shu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Andrographolide ameliorates hepatic steatosis by suppressing FATP2-mediated fatty acid uptake in mice with nonalcoholic fatty liver disease - Li-Sha Ran; Ya-Zeng Wu; Yi-Wen Gan; Hong-Lian Wang; Li-Juan Wu; Chun-Mei Zheng; Yao Ming; Ran Xiong; Yong-Lin Li; Shi-Hang Lei; Xue Wang; Xiao-Qing Lao; et al. (Journal of Natural Medicines, 2023)
Excessive intrahepatocellular lipid accumulation or steatosis is caused by abnormal lipid metabolism and a common character of nonalcoholic fatty liver disease (NAFLD), which may progress into cirrhosis and hepatocellular cancer. Andrographolide (Andro) is the primary active ingredient extracted from Andrographis paniculata , showing a protective role against dietary steatosis with the mechanism not fully understood. In this study, we showed that administration of Andro (50, 100, and 200 mg/kg/day for 8 weeks, respectively) attenuated obesity and metabolic syndrome in high-fat diet (HFD)-fed mice with improved glucose tolerance, insulin sensitivity, and reduced hyperinsulinemia, hyperglycemia, and hyperlipidemia. HFD-fed mice presented hepatic steatosis, which was significantly prevented by Andro. In vitro, Andro decreased the intracellular lipid droplets in oleic acid-treated LO2 cells. The selected RT-PCR array revealed a robust expression suppression of the fatty acid transport proteins (FATPs) by Andro treatment. Most importantly, we found that Andro consistently reduced the expression of FATP2 in both the oleic acid-treated LO2 cells and liver tissues of HFD-fed mice. Overexpression of FATP2 abolished the lipid-lowering effect of Andro in oleic acid-treated LO2 cells. Andro treatment also reduced the fatty acid uptake in oleic acid-treated LO2 cells, which was blunted by FATP2 overexpression. Collectively, our findings reveal a novel mechanism underlying the anti-steatosis effect of Andro by suppressing FATP2-mediated fatty acid uptake, suggesting the potential therapeutic application of Andro in the treatment of NAFLD. Graphical abstract

Acinetobacter faecalis Sp. Nov., Isolated from Elephant Faeces - Xue-Mei Chen; De-Feng An; Si-Rong He; Shao-Juan Yang; Zu-Zhen Yang; Lian-Shuang Xiong; Gui-Ding Li; Ming-Guo Jiang; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2023)

Aberrant Topological Properties of Brain Functional Network in Children with Obstructive Sleep Apnea Derived from Resting-State fMRI - Tingting Ji; Xuemin Ren; Ting Long; Xiaodan Li; Lin Mei; Wentong Ge; Jie Zhang; Shengcai Wang; Yongli Guo; Zhifei Xu; Yun Peng; Jiangang Liu; et al. (Brain Topography, 2023)

A new formula of recovery factor for non-equilibrium transport of graded suspended sediment in the Middle Yangtze River - Lin-lin Li; Jun-qiang Xia; Mei-rong Zhou; Shan-shan Deng; Zhi-wei Li (Journal of Mountain Science, 2023)

Selenium attenuates the association of co-exposure to arsenic, cadmium, and lead with cognitive function among Chinese community-dwelling older adults - Bei-Jing Cheng; Jie Sheng; Hong-Li Wang; Yuan Wang; Hong-Juan Cao; Xiu-De Li; Ting-Ting Zhou; Xiang-Long Meng; Huan-Huan Nie; Su-Fang Wang; Dong-Mei Zhang; Gui-Mei Chen; et al. (Environmental Science and Pollution Research, 2022)

Correction to: Comparative Studies of Cerebral Reperfusion Injury in the Posterior and Anterior Circulations After Mechanical Thrombectomy - Matthew M. Bower; Shuichi Suzuki; Kiarash Golshani; Li-Mei Lin; Mohammad Shafie; Hermelinda G. Abcede; Jay Shah; Dana Stradling; Wengui Yu (Translational Stroke Research, 2022)

Copper Toxicity Differentially Regulates the Seedling Growth, Copper Distribution, and Photosynthetic Performance of Citrus sinensis and Citrus grandis - Xin-yu Li; Mei-lan Lin; Ping-ping Hu; Ning-wei Lai; Zeng-rong Huang; Li-song Chen (Journal of Plant Growth Regulation, 2022)

Uncovering expression and functional analysis of newly discovered high-affinity K+ transporter family members from sugarcane - Hai-bin Luo; Cheng-mei Huang; Yuan-wen Wei; Hui-ming Zhu; Hui-qing Cao; Sheng-li Jiang; Zhi-nian Deng; Kai-chao Wu; Lin Xu (Journal of Plant Biochemistry and Biotechnology, 2022)

The association between essential trace element mixture and atherosclerotic cardiovascular disease risk among Chinese community-dwelling older adults - Xiang-long Meng; Yuan Wang; Hong-li Wang; Huan-huan Nie; Bei-jing Cheng; Hong-juan Cao; Xiu-de Li; Su-fang Wang; Gui-mei Chen; Fang-biao Tao; Jie Sheng; Lin-sheng Yang (Environmental Science and Pollution Research, 2022)

Clinical profiles and antimicrobial resistance patterns of invasive Salmonella infections in children in China - Wen Song; Qingwen Shan; Yue Qiu; Xianyao Lin; Chunhui Zhu; Zhiqiang Zhuo; Caihong Wang; Jianning Tong; Rui Li; Chaomin Wan; Yu Zhu; Minxia Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
Invasive Salmonella infections result in a significant burden of disease including morbidity, mortality, and financial cost in many countries. Besides typhoid fever, the clinical impact of non-typhoid Salmonella infections is increasingly recognized with the improvement of laboratory detection capacity and techniques. A retrospective multicenter study was conducted to analyze the clinical profiles and antimicrobial resistance patterns of invasive Salmonella infections in hospitalized children in China during 2016–2018. A total of 130 children with invasive Salmonella infections were included with the median age of 12 months (range: 1–144 months). Seventy-nine percent of cases occurred between May and October. Pneumonia was the most common comorbidity in 33 (25.4%) patients. Meningitis and septic arthritis caused by nontyphoidal Salmonella (NTS) infections occurred in 12 (9.2%) patients and 5 (3.8%) patients. Patients < 12 months (OR: 16.04) and with septic shock (OR: 23.4), vomit (OR: 13.33), convulsion (OR: 15.86), C-reactive protein (CRP) ≥ 40 g/L (OR: 5.56), and a higher level of procalcitonin (PCT) (OR: 1.05) on admission were statistically associated to an increased risk of developing meningitis. Compared to 114 patients with NTS infections , 16 patients with typhoid fever presented with higher levels of CRP and PCT ( P < 0.05). The rates of resistance to ampicillin, sulfamethoxazole/trimethoprim, ciprofloxacin, and ceftriaxone among Salmonella Typhi and NTS isolates were 50% vs 57.3%, 9.1% vs 24.8%, 0% vs 11.2%, and 0% vs 9.9%, respectively. NTS has been the major cause of invasive Salmonella infections in Chinese children and can result in severe diseases. Antimicrobial resistance among NTS was more common.

Functional analysis of HADH c.99C>G shows that the variant causes the proliferation of pancreatic islets and leu-sensitive hyperinsulinaemia - Wu Long; Yue-Bing Wang; Peng-Fei Qu; Lin Ma; Si-Jie Wei; Yan-Mei Xi; Jin-Liang Du; Xue Tang; Kai Liu; Yu-Hua Li; Pu-Ping Lei (Journal of Genetics, 2022)

Altered Retinal Dopamine Levels in a Melatonin-proficient Mouse Model of Form-deprivation Myopia - Kang-Wei Qian; Yun-Yun Li; Xiao-Hua Wu; Xue Gong; Ai-Lin Liu; Wen-Hao Chen; Zhe Yang; Ling-Jie Cui; Yun-Feng Liu; Yuan-Yuan Ma; Chen-Xi Yu; Furong Huang; et al. (Neuroscience Bulletin, 2022)

Comparative Studies of Cerebral Reperfusion Injury in the Posterior and Anterior Circulations After Mechanical Thrombectomy - Matthew M. Bower; Shuichi Suzuki; Kiarash Golshani; Li-Mei Lin; Mohammad Shafie; Hermelinda G. Abcede; Jay Shah; Dana Stradling; Wengui Yu (Translational Stroke Research, 2022)
Cerebral reperfusion injury is the major complication of mechanical thrombectomy (MT) for acute ischemic stroke (AIS). Contrast extravasation (CE) and intracranial hemorrhage (ICH) are the key radiographical features of cerebral reperfusion injury. The aim of this study was to investigate CE and ICH after MT in the anterior and posterior circulation, and their effect on functional outcome. This is a retrospective study of all consecutive patients who were treated with MT for AIS at University of California Irvine Medical Center between January 1, 2014, and December 31, 2017. Patient characteristics, clinical features, procedural variables, contrast extravasation, ICH, and outcomes after MT were analyzed. A total of 131 patients with anterior circulation (AC) stroke and 25 patients with posterior circulation (PC) stroke underwent MT during the study period. There was no statistically significant difference in admission NIHSS score, blood pressure, rate of receiving intravenous tPA, procedural variables, contrast extravasation, and symptomatic ICH between the 2 groups. Patients with PC stroke had a similar rate of favorable outcome (mRS 0–2) but significantly higher mortality (40.0% vs. 10.7%, p < 0.01) than patients with AC stroke. Multivariate regression analysis identified initial NIHSS score (OR 1.1, CI 1.0–1.2, p = 0.01), number of passes with stent retriever (OR 2.1, CI 1.3–3.6, p < 0.01), and PC stroke (OR 9.3, CI 2.5–35.1, p < 0.01) as independent risk factors for death. There was no significant difference in functional outcomes between patients with and without evidence of cerebral reperfusion injury after MT. We demonstrated that AC and PC stroke had similar rates of cerebral reperfusion injury and favorable outcome after MT. Cerebral reperfusion injury is not a significant independent risk factor for poor functional outcome.

Temporal specificity of IL-6 knockout in enhancing the thermogenic capability of brown adipose tissue - Mei Dong; Cheng Gao; Yanxin Jia; Weijia Xu; Yan Liu; Xin Wen; Qingxin Liu; Hai Lin; Haifang Li (Journal of Physiology and Biochemistry, 2022)

Association of cognitive impairment and reduced cortical thickness in prefrontal cortex and anterior cingulate cortex with treatment-resistant depression - Mu-Hong Chen; Wan-Chen Chang; Pei-Chi Tu; Wei-Chen Lin; Cheng-Ta Li; Wen-Sheng Huang; Ya-Mei Bai; Shih-Jen Tsai; Tung-Ping Su (Brain Imaging and Behavior, 2022)

Vertical patterns of chlorophyll a in the euphotic layer are related to mesoscale eddies in the South China Sea - Mei-Lin Wu; You-Shao Wang; Yu-Tu Wang; Fu-Lin Sun; Xiaomei Li; Fang-Fang Gu; Jing-Chang Xiang (Frontiers in Marine Science, 2022)
Phytoplankton closely connects with the hydrodynamics and biogeochemical environment of the ocean. While research focusing on both the physiochemical factors and hydrodynamics regulating phytoplankton has already been conducted, the coupling mechanism between mesoscale eddies and the vertical distribution of phyto plankton in the South China Sea (SCS) is still not well understood. Here, phytoplankton was studied under one weak-cold and two warm eddies along the 18°N transect in the SCS. The results show that the vertical distribution of chlorophyll (chl- a ) presented a similar pattern at all four sampling stations. The mixed layer is less than 50 m. It is the same as the meridional salinity gradients that may be distinguished above a depth of 60 m. The subsurface chlorophyll maximum at the edge of a warm (WI) and cold eddy (CI) at E413 and E411 was shallower than that at the edge of a warm eddy (WII) at E407 and E409, indicating that temperature and salinity may be the important driving factors. On the whole, mesoscale eddies had a significant influence on the vertical pattern of chl- a in the SCS during the study period.

Astragalus Polysaccharides Reduce High-glucose-induced Rat Aortic Endothelial Cell Senescence and Inflammasome Activation by Modulating the Mitochondrial Na+/Ca2+ Exchanger - Xin-Yu Miao; Xiao-Xiao Zhu; Zhao-Yan Gu; Bo Fu; Shao-Yuan Cui; Yuan Zu; Ling-Jun Rong; Fan Hu; Xiang-Mei Chen; Yan-Ping Gong; Chun-Lin Li (Cell Biochemistry and Biophysics, 2022)

Massive Heat Shock Protein 70 Genes Expansion and Transcriptional Signatures Uncover Hard Clam Adaptations to Heat and Hypoxia - Zhi Hu; Hao Song; Jie Feng; Cong Zhou; Mei-Jie Yang; Pu Shi; Zheng-Lin Yu; Yong-Ren Li; Yong-Jun Guo; Hai-Zhou Li; Tao Zhang (Frontiers in Marine Science, 2022)
Heat shock protein 70 (HSP70) members participate in a wide range of housekeeping and stress-related activities in eukaryotic cells. In marine ecosystems, bivalves encounter abiotic stresses, including high temperatures and low dissolved oxygen. Here, 133 MmHSP70 genes were identified through combined methods including Blastp, HMM and manual filtration, based on the whole Mercenaria mercenaria genome. The MmHSP70 genes were unevenly distributed, and 41 genes (33.08%) were located on Chr 7. Phylogenetic analyses indicated that the MmHSP70 gene family mainly consisted of two clusters and the Hspa12 subfamily underwent lineage-specific expansion. A high-density collinear gene block was observed between M. mercenaria Chr 7 and Cyclina sinensis Chr 14. Tandem duplication MmHSP70 gene pairs experienced different levels of purifying selection, which could be an important source of sequence and functional constraints. MmHSP70 genes showed tissue-specific and stress-specific expression. Most tandem duplication HSP70 gene pairs had high expression under hypoxia stress. HSP70 B2 tandem duplication gene pairs showed significantly increased expression under heat plus severe hypoxia stress. This study provided a comprehensive understanding of the MmHSP70 gene family in the M. mercenaria and laid a significant foundation for further studies on the functional characteristics of MmHSP70 genes during exposure to heat and hypoxia stress.

The genes for sensory perception of sound should be considered in gene diagnosis of congenital sensorineural hearing loss and microtia - Ken Lin; Ding-Yun You; Li-Huan Zhang; Li-Juan Zhou; Jin-Yan Zu; Yang Xiao; Mei-Hua Sun; Dong-Su; Xue Cao; Tie-Song Zhang; Jing Ma (Journal of Applied Genetics, 2022)

Genetic diversity and population structure of Curcuma alismatifolia Gagnep. accessions revealed by SSR markers - Hui-Wen Yu; Ling-Jun Ke; Yi-Lan Xiao; Si-Jia Chen; Yuan-Yuan Li; Qi-Lin Tian; Yun-He Li; Jin-Shui Lin; Luan-Mei Lu (Genetic Resources and Crop Evolution, 2022)

Alternaria species causing leaf spot on hemp (Cannabis sativa) in Northern China - Hong Cheng; Lin Zhao; Xin Wei; Xi Liu; Guo-Yang Gao; Jian-Xin Deng; Mei-Jia Li (European Journal of Plant Pathology, 2022)

Identification of epigenetic modifications mediating the antagonistic effect of selenium against cadmium-induced breast carcinogenesis - Zhuo-Zhi Liang; Yi-Xin Zhang; Rui-Mei Zhu; Yue-Lin Li; Hong-Mei Jiang; Ruo-Bi Li; Qian-Xin Chen; Qing Wang; Lu-Ying Tang; Ze-Fang Ren (Environmental Science and Pollution Research, 2022)

Morphological and Molecular Characterization of Paragonimus skrjabini Complex from Yunnan, China: A Brief Report - Qiu-Hong Shu; Shu-De Li; Ming Tian; Yong Meng; Shu-Mei-Qi He; Min Zhu; Miao-Miao Wang; Wen-Lin Wang (Acta Parasitologica, 2022)
Purpose To perform environmental sampling and molecular identification of Paragonimus in endemic regions, which may help in minimizing transmission among humans. Methods Mountain crabs from the genus Potamiscus were collected and the encysted metacercariae were extracted and subjected to morphological identification, followed by animal inoculation in Sprague–Dawley (SD) rats. After 112 days of infection, animals were killed and adult worms were extracted from lungs and muscles. The morphology of adult worms was characterized by microscopy and molecular identification was done by polymerase chain reaction, followed by sequencing of cox1 and ITS2 genes. Phylogenetic analysis was done by maximum parsimony method. Results A total of 447 crabs were captured from the streams of Tongchang Town, Jinping County, Yunnan Province, China. The infection rate was found to be 41% (186 out of 447 crabs). The metacercariae of Paragonimus skrjabini was identified by the characteristics round or spherical encysted form measuring 410 to 460 × 400 to 460 µm. After animal infection in SD rats, adults were presumptively confirmed to be P. skrjabini , which was also confirmed by gene amplification and sequence analysis of cox1 and ITS2 regions. Paragonimus skrjabini clustered with previously reported P. skrjabini from Yunnan and Vietnam. The confidence values of their branches were > 95%. Phylogenetic analysis of the ITS2 region revealed two distinct clusters with distinct geographical grouping. Phylogenetic analysis with the combined data sets reiterated the geographical grouping with P. skrjabini from Yunnan clustering with strains from Vietnam. Conclusion Metacercariae of P. skrjabini was discovered in freshwater crabs in Yunnan province, China, and the strains were phylogenetically related to P. skrjabini from Vietnam.

A Challenge to Conventional Fish Meal: Effects of Soy Protein Peptides on Growth, Histomorphology, Lipid Metabolism and Intestinal Health for Juvenile Pompano Trachinotus ovatus - Huaxing Lin; Beiping Tan; Gyan Watson Ray; Min Zeng; Mei Li; Shuyan Chi; Qihui Yang (Frontiers in Marine Science, 2022)
This experiment was conducted to assess the possibility of replacing fish meal (FM) with soy protein peptide (SPP) at different levels—0% (FM), 14.29% (S5), 28.57% (S10), 57.14% (S20), 71.42%(S25)—and its effects on growth, histology, gene expression related to liver lipid metabolism and intestinal immunity in juvenile pompano Trachinotus ovatus (initial mean weight = 39.88 ± 0.15 g). 600 healthy and uniformed-size fish were distributed to five groups of three replicates, each with 40 fish in each floating cage and fed twice daily for 8 weeks. Results showed that no significant difference in the growth was observed with SPP replacing FM ( P > 0.05). Serum glutathione peroxidase activity in the S10 group was significantly higher than that in the FM group, and serum malondialdehyde content significantly decreased ( P < 0.05). SPP significantly improved intestinal immunity by increasing alkaline phosphatase and lysozyme activities and up-regulating interleukin 10 and complement 4 mRNA levels while simultaneously decreasing triglyceride and total cholesterol content and down-regulating interleukin 1β mRNA expression. Villus length and muscle thickness in the S10 group were significantly higher than those in the FM group ( P < 0.05). SPP significantly improved liver fat metabolism by increasing carnitine palmitoyl transferase I mRNA levels, and down-regulating fatty acid synthesis mRNA expression ( P < 0.05). In summary, SPP substitution for FM promoted intestinal health, liver lipid metabolism and reduced liver fat accumulation for juvenile pompano T. ovatus , with no significant effect on growth performance. Based on the second-order polynomial analysis model of LYZ activity, the optimal replacement SPP level for juvenile pompano T. ovatus was 11.82%.

Oxygen Metabolism-induced Stress Response Underlies Heart–brain Interaction Governing Human Consciousness-breaking and Attention - Xiao-Juan Xue; Rui Su; Ze-Feng Li; Xiao-Ou Bu; Peng Dang; Si-Fang Yu; Zhi-Xin Wang; Dong-Mei Chen; Tong-Ao Zeng; Ming Liu; Hai-Lin Ma; De-Long Zhang (Neuroscience Bulletin, 2022)

Development and validation of a 30-day death nomogram in patients with spontaneous cerebral hemorrhage: a retrospective cohort study - Qian Han; Mei Li; Dongpo Su; Aijun Fu; Lin Li; Tong Chen (Acta Neurologica Belgica, 2022)

Nakamurella leprariae sp. nov., isolated from a lichen sample - De-Feng An; Shao-Juan Yang; Long-Qian Jiang; Xin-Yu Wang; Xiao-Yu Huang; Lei Lang; Xue-Mei Chen; Ming-Qun Fan; Gui-Ding Li; Ming-Guo Jiang; Li-Song Wang; Cheng-Lin Jiang; et al. (Archives of Microbiology, 2022)

Genome-wide identification and expression analysis of glycosyltransferase gene family 1 in Quercus robur L. - Jie Zhang; Li-Mei Lin; Wen-Wen Cheng; Xin Song; Yue-Hong Long; Zhao-Bin Xing (Journal of Applied Genetics, 2021)

Analysis of the starch properties in tetraploid wheat–Aegilops sharonensis amphidiploid - Qing Li; Xuteng Zhang; Na Lin; Guzmán Carlos; Jingyu Lan; Huaping Tang; Pengfei Qi; Jian Ma; Jirui Wang; Guoyue Chen; Wei Li; Zhien Pu; et al. (Cereal Research Communications, 2021)

Long-term changes of water acidity in an intact forested watershed in south China - Xiao-dong Liu; Ying-jie Feng; Qi-feng Mo; Guo-wei Chu; Yue-lin Li; Qian-mei Zhang; Wei-qiang Zhang; Xian-hua Gan; Qing Zhou (Journal of Mountain Science, 2021)

Characterization and identification of SFDC ‐1, a novel AmpC ‐type β‐lactamase in Serratia fonticola - Xu Dong; Peiyao Zhang; Kexin Zhou; Jialei Liang; Qiaoling Li; Xueya Zhang; Danying Zhou; Wei Lu; Zhewei Sun; Hongmao Liu; Junwan Lu; Xi Lin; et al. (Environmental Microbiology, 2021)
Summary The clinical and environmental infections caused by AmpC β‐lactamases have been increasingly reported recently. In this study, we characterize the novel chromosome‐encoded AmpC β‐lactamase SFDC‐1 identified in Serratia fonticola strain R28, which was isolated from a rabbit raised on a farm in southern China. SFDC‐1 shared the highest amino acid identity of 79.6% with the functionally characterized AmpC β‐lactamase gene bla YRC‐1 , although it had highly homologous functionally uncharacterized relatives in the same species from different sources, including some of the clinical significance. The cloned bla SFDC‐1 exhibited resistance to a broad spectrum of β‐lactam antibiotics, including most cephalosporins with the highest resistance to ampicillin, cefazolin and ceftazidime, with increased MIC levels ≥128‐fold compared with the control strains. The purified SFDC‐1 showed catalytic activities against β‐lactams with the highest catalytic activity to cefazolin. The genetic context of bla SFDC‐1 and its relatives was conserved in the chromosome, and no mobile genetic elements were found surrounding them.

Chronic Exposure to Hypoxia Inhibits Myelinogenesis and Causes Motor Coordination Deficits in Adult Mice - Lin Chen; Shu-Yu Ren; Rui-Xue Li; Kun Liu; Jing-Fei Chen; Yu-Jian Yang; Yong-Bin Deng; Han-Zhi Wang; Lan Xiao; Feng Mei; Fei Wang (Neuroscience Bulletin, 2021)
Exposure to chronic hypoxia is considered to be a risk factor for deficits in brain function in adults, but the underlying mechanisms remain largely unknown. Since active myelinogenesis persists in the adult central nervous system, here we aimed to investigate the impact of chronic hypoxia on myelination and the related functional consequences in adult mice. Using a transgenic approach to label newly-generated myelin sheaths ( NG2-CreER TM ; Tau-mGFP ), we found that myelinogenesis was highly active in most brain regions, such as the motor cortex and corpus callosum. After exposure to hypoxia (10% oxygen) 12 h per day for 4 weeks, myelinogenesis was largely inhibited in the 4-month old brain and the mice displayed motor coordination deficits revealed by the beam-walking test. To determine the relationship between the inhibited myelination and functional impairment, we induced oligodendroglia-specific deletion of the transcription factor Olig2 by tamoxifen ( NG2-CreER TM ; Tau-mGFP; Olig2 fl/fl ) in adult mice to mimic the decreased myelinogenesis caused by hypoxia. The deletion of Olig2 inhibited myelinogenesis and consequently impaired motor coordination, suggesting that myelinogenesis is required for motor function in adult mice. To understand whether enhancing myelination could protect brain functions against hypoxia, we treated hypoxic mice with the myelination-enhancing drug-clemastine, which resulted in enhanced myelogenesis and improved motor coordination. Taken together, our data indicate that chronic hypoxia inhibits myelinogenesis and causes functional deficits in the brain and that enhancing myelinogenesis protects brain functions against hypoxia-related deficits.

A new species of Macandrewia (Demospongiae, Tetractinellida, Macandrewiidae) from a seamount in the Western Pacific Ocean - Lin Gong; Swee-Cheng Lim; Mei Yang; Xinzheng Li (Journal of Oceanology and Limnology, 2021)

Future variation in mountainous discharge in arid northwestern China: A basin case study - Lei Wu; Chang-bin Li; Xu-hong Xie; Jia-nan Lv; Jian-mei Wei; Xuan Zhou; Lin-shan Yang (Journal of Mountain Science, 2021)

Dicer Deletion in Astrocytes Inhibits Oligodendroglial Differentiation and Myelination - Kun Liu; Bin Yu; Jing-Fei Chen; Rui-Xue Li; Lin Chen; Shu-Yu Ren; Fei Wang; Feng Mei; Lan Xiao (Neuroscience Bulletin, 2021)
Increasing evidence has shown that astrocytes are implicated in regulating oligodendrocyte myelination, but the underlying mechanisms remain largely unknown. To understand whether microRNAs in astrocytes function in regulating oligodendroglial differentiation and myelination in the developing and adult CNS, we generated inducible astrocyte-specific Dicer conditional knockout mice (hGFAP-CreERT; Dicer fl/fl). By using a reporter mouse line (mT/mG), we confirmed that hGFAP-CreERT drives an efficient and astrocyte-specific recombination in the developing CNS, upon tamoxifen treatment from postnatal day 3 (P3) to P7. The Dicer deletion in astrocytes resulted in inhibited oligodendroglial differentiation and myelination in the developing CNS of Dicer cKO mice at P10 and P14, and did not alter the densities of neurons or axons, indicating that Dicer in astrocytes is required for oligodendrocyte myelination. Consequently, the Dicer deletion in astrocytes at P3 resulted in impaired spatial memory and motor coordination at the age of 9 weeks. To understand whether Dicer in astrocytes is also required for remyelination, we induced Dicer deletion in 3-month-old mice and then injected lysolecithin into the corpus callosum to induce demyelination. The Dicer deletion in astrocytes blocked remyelination in the corpus callosum 14 days after induced demyelination. Together, our results indicate that Dicer in astrocytes is required for oligodendroglia myelination in both the developing and adult CNS.

Evaluation of the RNA extraction methods in different Ginkgo biloba L. tissues - Xiao-lin Zhang; Xiao-li Huang; Jia Li; Mei Mei; Wan-qi Zeng; Xiu-jun Lu (Biologia, 2021)

Coupling effects of hydrological characteristics and nutrient load in sediments on the trophic state of reservoirs - Fan Xinyi; Yue Yihong; Mei Lin; Li Xiaoying; Hu Zhehui; Luo Jiajie; Liu Liu; Wang Fushun (Acta Geochimica, 2021)

A new ent -kaurane diterpene from Isodon henryi - Xue Jiang; Ling-Xia Zhang; Qing-Mei Feng; Hong Wu; Ya-Lin Liu; De-Qin Wang; Li-Ping Dai; Zhi-Min Wang (Natural Product Research, 2021)

Enhanced treatment of shale gas fracturing waste fluid through plant-microbial synergism - Bo Shao; Xu Tan; Ju-Long Li; Mei He; Lei Tian; Wen-Jie Chen; Yan Lin (Environmental Science and Pollution Research, 2021)

Proton Pump Inhibitor Exposure and Acute Myocardial Infarction Risk: A Nested Cohort Study - Hsiang-Jung Tseng; Chih-Ming Cheng; Shih-Jen Tsai; Wei-Chen Lin; Ya-Mei Bai; Chia-Fen Tsai; Tung-Ping Su; Cheng-Ta Li; Tzeng-Ji Chen; Mu-Hong Chen (Cardiovascular Toxicology, 2021)

Correction to: Synthetic antimicrobial agents inhibit aflatoxin production - Jing Li; Qing-Qing Zhi; Jie Zhang; Xiao-Yu Yuan; Li-Hong Jia; Yu-Lin Wan; Qiu-Yun Liu; Jian-Rong Shi; Zhu-Mei He (Brazilian Journal of Microbiology, 2021)

Synthetic antimicrobial agents inhibit aflatoxin production - Jing Li; Qing-Qing Zhi; Jie Zhang; Xiao-Yu Yuan; Li-Hong Jia; Yu-Lin Wan; Qiu-Yun Liu; Jian-Rong Shi; Zhu-Mei He (Brazilian Journal of Microbiology, 2021)

Identification and characterization of CONSTANS-like genes from Curcuma alismatifolia - Yuan-Yuan Li; Xiao-Huang Chen; Hui-Wen Yu; Qi-Lin Tian; Luan-Mei Lu (Horticulture, Environment, and Biotechnology, 2021)

Effects of plant growth regulators and polyamines on bract longevity in Bougainvillea buttiana - Kuan-Hung Lin; Jui-Mei Li; Chun-Wei Wu; Yu-Sen Chang (Horticulture, Environment, and Biotechnology, 2021)

Microbiological profiles and antimicrobial resistance patterns of pediatric bloodstream pathogens in China, 2016–2018 - Yue Qiu; Junwen Yang; Yiping Chen; Jinhong Yang; Qingxiong Zhu; Chunhui Zhu; Shuangjie Li; Jing Liu; Chaomin Wan; Yu Zhu; Minxia Chen; Yi Xu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Adaptive Evolution of Chalcone Isomerase Superfamily in Fagaceae - Li-Mei Lin; Hong-Yu Guo; Xin Song; Duo-Duo Zhang; Yue-Hong Long; Zhao-Bin Xing (Biochemical Genetics, 2021)

Interest-activity symptom severity predicts response to ketamine infusion in treatment-resistant depression - Mu-Hong Chen; Wei-Chen Lin; Hui-Ju Wu; Ya-Mei Bai; Cheng-Ta Li; Shih-Jen Tsai; Chen-Jee Hong; Pei-Chi Tu; Tung-Ping Su (Psychopharmacology, 2021)

Lentibacillus saliphilus. sp. nov., a moderately halophilic bacterium isolated from a saltern in Korea - Yun Wang; Gang-Qiang Jiang; Hong-Ping Lin; Peng Sun; Hong-Yan Zhang; Dong-Mei Lu; Li-Yun Wang; Chang-Jin Kim; Shu-Kun Tang (Archives of Microbiology, 2021)

Report of epibenthic macrofauna found from Haima cold seeps and adjacent deep-sea habitats, South China Sea - Dong Dong; Xinzheng Li; Mei Yang; Lin Gong; Yang Li; Jixing Sui; Zhibin Gan; Qi Kou; Ning Xiao; Junlong Zhang (Marine Life Science & Technology, 2021)
This work reports on a preliminary taxonomic study of epibenthic macroinvertebrates collected or observed by underwater video at the Haima cold seeps and in adjacent deep-sea habitats, including a mud volcano field and Ganquan Plateau, during an expedition in the South China Sea by the Chinese-manned submersible Shenhai Yongshi in May 2018. A total of 41 species belonging to 6 phyla were identified, among which 34 species were collected from the Haima cold seeps. Mollusks and crustaceans that are specialized in reducing habitats were predominant in biotopes of the Haima cold seeps, whereas sponges and cold-water corals and their commensals were prominent in communities of the mud volcano field and the slopes of Ganquan Plateau. The distribution and faunal composition of each taxonomic group are discussed.

Sesquiterpenoids and meroterpenoids from a mangrove derived fungus Diaporthe sp. SCSIO 41011 - Xiao-Wei Luo; Chun-Mei Chen; Kun-Long Li; Xiu-Ping Lin; Cheng-Hai Gao; Xue-Feng Zhou; Yong-Hong Liu (Natural Product Research, 2021)

Management of Gout-associated MSU crystals-induced NLRP3 inflammasome activation by procyanidin B2: targeting IL-1β and Cathepsin B in macrophages - Chun-Ying Qiao; Ying Li; Yue Shang; Min Jiang; Jian Liu; Zi-Ying Zhan; Huan Ye; Yong-Ce Lin; Jing-Ya Jiao; Rong-Hui Sun; Zhi-Hong Zhang; Mei-Hua Piao; et al. (Inflammopharmacology, 2020)

Using sowing date management to promote micronutrient quality and alleviate cadmium accumulation in rice grains - Lin-lin Shi; Ming-xing Shen; Hong-jun Wu; Chang-ying Lu; Li-juan Mei; Xin-lian Zhu; Hai-hou Wang; Yun-Sheng Song (Cereal Research Communications, 2020)

Greater promotion of DNRA rates and nrfA gene transcriptional activity by straw incorporation in alkaline than in acidic paddy soils - Ren Bai; Yun-Ting Fang; Liu-Ying Mo; Ju-Pei Shen; Lin-Lin Song; Ya-Qi Wang; Li-Mei Zhang; Ji-Zheng He (Soil Ecology Letters, 2020)

Whether the carbon emission from green roofs can be effectively mitigated by recycling waste building material as green roof substrate during five-year operation? - Liangqian Fan; Jingting Wang; Xiaoling Liu; Hongbing Luo; Ke Zhang; Xiaoying Fu; Mei Li; Xiaoting Li; Bing Jiang; Jia Chen; Shuzhi Fu; You Mo; et al. (Environmental Science and Pollution Research, 2020)

LMDS-1, a potential TrkB receptor agonist provides a safe and neurotrophic effect for early-phase Alzheimer’s disease - Chia-Hao Fan; Chia-Wei Lin; Hei-Jen Huang; Guey-Jen Lee-Chen; Ying-Chieh Sun; Wenwei Lin; Chiung-Mei Chen; Kuo-Hsuan Chang; Ming-Tsan Su; Hsiu Mei Hsieh-Li (Psychopharmacology, 2020)

Identification and validation of stable quantitative trait loci for grain filling rate in common wheat (Triticum aestivum L.) - Yu Lin; Xiaojun Jiang; Yang Tao; Xilan Yang; Zhiqiang Wang; Fangkun Wu; Shihang Liu; Caixia Li; Mei Deng; Jian Ma; Guangdeng Chen; Yuming Wei; et al. (Theoretical and Applied Genetics, 2020)

Neuroimaging Spectrum at Pre-, Early, and Late Symptomatic Stages of SCA17 Mice - Chiao-Chi Chen; Nai-Wei Yao; Chia-Wei Lin; Wei-Shuo Su; Chin-Tien Wu; Chen Chang; Hsiu Mei Hsieh-Li (The Cerebellum, 2020)

Mixture of Pb, Zn and Cu on root permeability and radial oxygen loss in the mangrove Bruguiera gymnorrhiza - Hao Cheng; You-Shao Wang; Chang-Da Li; Zhi-Hong Ye; Shafi Muhammad; Mei-Lin Wu; Fun-Lin Sun (Ecotoxicology, 2020)

Dynamics of radial oxygen loss in mangroves subjected to waterlogging - Hao Cheng; Mei-Lin Wu; Chang-Da Li; Fu-Lin Sun; Cui-Ci Sun; You-Shao Wang (Ecotoxicology, 2020)

Targeting Inflammation, PHA-767491 Shows a Broad Spectrum in Protein Aggregation Diseases - Yu-Han Chung; Chia-Wei Lin; Hsin-Yu Huang; Shu-Ling Chen; Hei-Jen Huang; Ying-Chieh Sun; Guan-Chiun Lee; Guey-Jen Lee-Chen; Ya-Ching Chang; Hsiu Mei Hsieh-Li (Journal of Molecular Neuroscience, 2020)

Combined effect of polymorphisms of MTHFR and MTR and arsenic methylation capacity on developmental delay in preschool children in Taiwan - Yu-Mei Hsueh; Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Horng-Sheng Shiue; Ssu-Ning Chien; Chih-Ying Lee; Ming-I. Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2020)

Detection of serum IgM and IgG for COVID-19 diagnosis - Ling Zhong; Junlan Chuan; Bo Gong; Ping Shuai; Yu Zhou; Yi Zhang; Zhilin Jiang; Dingding Zhang; Xiaoqi Liu; Shi Ma; Yi Huang; He Lin; et al. (Science China Life Sciences, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Viral metagenomics reveals sapoviruses of different genogroups in stool samples from children with acute gastroenteritis in Jiangsu, China - Wang Li; Surong Dong; Juan Xu; Xiaobin Zhou; Junling Han; Zhaqing Xie; Qin Gong; Hailin Peng; Chenglin Zhou; Mei Lin (Archives of Virology, 2020)
Sapoviruses (SAVs), including several genogroups (GI to GV), are one of the causes of acute gastroenteritis (AGE). In this study, viral metagenomics revealed the presence of sapoviruses of different genogroups in stool from children with AGE. Eight different complete SAV genomes were determined, of which five belonged to GI and the other three belonged to GII, GIV and GV, respectively. Although they were highly similar to published sequences, the GIV and GV were the first complete genome sequences of these SAVs found in China. In a prevalence investigation, 19% of subjects with AGE were positive for SAVs, while none of the control group was positive.

Scorpion Venom Heat-Resistant Peptide is Neuroprotective against Cerebral Ischemia-Reperfusion Injury in Association with the NMDA-MAPK Pathway - Xu-Gang Wang; Dan-Dan Zhu; Na Li; Yue-Lin Huang; Ying-Zi Wang; Ting Zhang; Chen-Mei Wang; Bin Wang; Yan Peng; Bi-Ying Ge; Shao Li; Jie Zhao (Neuroscience Bulletin, 2020)

Plasma biomarkers and plaque strain predict long-term cardiovascular events in patients with acute coronary syndrome - Mingjun Xu; Xiaobo Hu; Lin Wang; Wei Zhang; Lindi Wu; Jifu Li; Yuguo Chen; Pengfei Zhang; Haijun Su; Yaling Han; Cheng Zhang; Mei Zhang; et al. (Science China Life Sciences, 2020)

NRG1–ErbB4 signaling promotes functional recovery in a murine model of traumatic brain injury via regulation of GABA release - Weike Deng; Fei Luo; Bao-ming Li; Lin Mei (Experimental Brain Research, 2019)

Forecasts of MJO Events during DYNAMO with a Coupled Atmosphere-Ocean Model: Sensitivity to Cumulus Parameterization Scheme - Mei-Yu Chang; Tim Li; Pay-Liam Lin; Ting-Huai Chang (Journal of Meteorological Research, 2019)

The complete chloroplast genome of Taiwania cryptomerioides (Cupressales: Cupressaceae), an endangered relict conifer species endemic to East Asia - Ling-Li Wang; Yong-Liang Shi; Qi-Lin Zhang; Yan-Ru Guo; Hong-Mei Teng (Conservation Genetics Resources, 2019)

Association of plasma folate, vitamin B12 levels, and arsenic methylation capacity with developmental delay in preschool children in Taiwan - Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Pui-Lam Ao; Horng-Sheng Shiue; Shiau-Rung Huang; Chien-Tien Su; Ming-I Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2019)

The Neuroprotective Effect of L-Stepholidine on Methamphetamine-Induced Memory Deficits in Mice - Mei Zhou; Xiaokang Gong; Qin Ru; Qi Xiong; Lin Chen; Yuanren Si; Huaqiao Xiao; Chaoying Li (Neurotoxicity Research, 2019)

Half-dose ticagrelor versus high-dose clopidogrel in reducing platelet reactivity in acute coronary syndrome patients with high on-clopidogrel platelet reactivity (divide study) - Guang Zhong Liu; Song Zhang; Dang Hui Sun; Jing Shi; Wan Lan Bo; Wen Nan Wang; Chong Yang Zhang; Zhong Hua Wang; Wei Feng; Mei Jiao He; Yuan Yuan Liu; Shuang Li; et al. (European Journal of Clinical Pharmacology, 2019)

Lignans, flavonoids and coumarins from Viola philippica and their α-glucosidase and HCV protease inhibitory activities - Ya-Li Wang; Lin Zhang; Meng-Yan Li; Li-Wei Wang; Chao-Mei Ma (Natural Product Research, 2019)

Favus of Scrotum Due to Trichophyton rubrum in Immunocompetent Patients: A Clinical, Mycological and Ultrastructural Study - Ze-Hu Liu; Xiu-Jiao Xia; Yong Zhang; Yan Zhong; Bo Sang; Qiu-Ping Li; Mei Wang; Wen-Wen Lv; Hui-Lin Zhi; Xiang-Dong Wang; Cui-Ping Guan; Hong Shen (Mycopathologia, 2019)

Modeling Alzheimer’s Disease by Induced Pluripotent Stem Cells Carrying APP D678H Mutation - Kuo-Hsuan Chang; Guey-Jen Lee-Chen; Ching-Chang Huang; Jia-Li Lin; Yi-Jing Chen; Pei-Chi Wei; Yen-Shi Lo; Chin-Fa Yao; Ming-Wei Kuo; Chiung-Mei Chen (Molecular Neurobiology, 2019)

Mercury–Organic Matter Interactions in Soils and Sediments: Angel or Devil? - Mei He; Lei Tian; Hans Fredrik Veiteberg Braaten; Qingru Wu; Jie Luo; Li-Mei Cai; Jiang-Hui Meng; Yan Lin (Bulletin of Environmental Contamination and Toxicology, 2019)

The effects of different pharmacological agent treatments on ROS accumulation and functional protein activities in wheat endosperm PCD - Ze Lin; Yuanhong Qi; Dongcheng Liu; Fangfang Mao; Xiangyi Deng; Jiwei Li; Fangzhu Mei; Zhuqing Zhou (Acta Physiologiae Plantarum, 2019)

Expression of the intrarenal angiotensin receptor and the role of renin-angiotensin system inhibitors in IgA nephropathy - Zheng Zhang; Shi-min Jiang; Ye-ping Ma; Pei-lin Dai; Yi-ning Wang; Gu-ming Zou; Hong-mei Gao; Yue Yang; Wen-ge Li (Molecular and Cellular Biochemistry, 2019)

Transcriptome analysis of Panax zingiberensis identifies genes encoding oleanolic acid glucuronosyltransferase involved in the biosynthesis of oleanane-type ginsenosides - Qing-Yan Tang; Geng Chen; Wan-Ling Song; Wei Fan; Kun-Hua Wei; Si-Mei He; Guang-Hui Zhang; Jun-Rong Tang; Ying Li; Yuan Lin; Sheng-Chao Yang (Planta, 2019)

Postprandial change in glucose metabolism at the molecular level in the adipose tissue of omnivorous GIFT Oreochromis niloticus - Jing-Yun Feng; Qin-Qin Liu; Hang-Zhong Xu; Rui-Hong Chen; Li Luo; Shi-Mei Lin; Yong-Jun Chen; De-Shou Wang (Fisheries Science, 2019)

Transcriptome Reveals Differentially Expressed Genes in Saccharum spontaneum GX83-10 Leaf Under Drought Stress - Kai-Chao Wu; Li-Ping Wei; Cheng-Mei Huang; Yuan-Wen Wei; Hui-Qing Cao; Lin Xu; Hai-Bin Luo; Sheng-Li Jiang; Zhi-Nian Deng; Yang-Rui Li (Sugar Tech, 2018)

Species diversity and molecular phylogeny of non-geniculate coralline algae (Corallinophycidae, Rhodophyta) from Taoyuan algal reefs in northern Taiwan, including Crustaphytum gen. nov. and three new species - Li-Chia Liu; Showe-Mei Lin; Annalisa Caragnano; Claude Payri (Journal of Applied Phycology, 2018)

Factors regulating carbon sinks in mangrove ecosystems - Shi‐Bo Li; Po‐Hung Chen; Jih‐Sheng Huang; Mei‐Li Hsueh; Li‐Yung Hsieh; Chen‐Lu Lee; Hsing‐Juh Lin (Global Change Biology, 2018)
Mangroves are recognized as one of the richest carbon storage systems. However, the factors regulating carbon sinks in mangrove ecosystems are still unclear, particularly in the subtropical mangroves. The biomass, production, litterfall, detrital export and decomposition of the dominant mangrove vegetation in subtropical ( Kandelia obovata ) and tropical ( Avicennia marina ) Taiwan were quantified from October 2011 to July 2014 to construct the carbon budgets. Despite the different tree species, a principal component analysis revealed the site or environmental conditions had a greater influence than the tree species on the carbon processes. For both species, the net production (NP) rates ranged from 10.86 to 27.64 Mg C ha −1 year −1 and were higher than the global average rate due to the high tree density. While most of the litterfall remained on the ground, a high percentage (72%–91%) of the ground litter decomposed within 1 year and fluxed out of the mangroves. However, human activities might cause a carbon flux into the mangroves and a lower NP rate. The rates of the organic carbon export and soil heterotrophic respiration were greater than the global mean values and those at other locations. Only a small percentage (3%–12%) of the NP was stored in the sediment. The carbon burial rates were much lower than the global average rate due to their faster decomposition, indicating that decomposition played a critical role in determining the burial rate in the sediment. The summation of the organic and inorganic carbon fluxes and soil heterotrophic respiration well exceeded the amount of litter decomposition, indicating an additional source of organic carbon that was unaccounted for by decomposition in the sediment. Sediment‐stable isotope analyses further suggest that the trapping of organic matter from upstream rivers or adjacent waters contributed more to the mangrove carbon sinks than the actual production of the mangrove trees.

Exploration of phenol tolerance mechanism through antioxidative responses of an evolved strain, Chlorella sp. L5 - Lin Zhou; Yizhong Yuan; Xuyang Li; Shouhua Mei; Juan Gao; Quanyu Zhao; Wei Wei; Yuhan Sun (Journal of Applied Phycology, 2018)

A New Approach of Rpf Addition to Explore Bacterial Consortium for Enhanced Phenol Degradation Under High Salinity Conditions - Ziqiao Li; Yunge Zhang; Yuyang Wang; Rongwu Mei; Yu Zhang; Muhammad Zaffar Hashmi; Hongjun Lin; Xiaomei Su (Current Microbiology, 2018)

Identifying crack initiation stress threshold in brittle rocks using axial strain stiffness characteristics - Mei-ben Gao; Tian-bin Li; Lu-bo Meng; Chun-chi Ma; Hui-lin Xing (Journal of Mountain Science, 2018)

Impact of mixed anthropogenic and natural emissions on air quality and eco-environment—the major water-soluble components in aerosols from northwest to offshore isle - Yilun Jiang; Guoshun Zhuang; Qiongzhen Wang; Kan Huang; Congrui Deng; Guangyuan Yu; Chang Xu; Qingyan Fu; Yanfen Lin; Joshua S. Fu; Mei Li; Zhen Zhou (Air Quality, Atmosphere & Health, 2018)

Long-term study on seasonal changes in floristic composition and structure of marine macroalgal communities along the coast of Northern Taiwan, southern East China Sea - Showe-Mei Lin; Li-Chun Tseng; Put O. Ang; John Bolton; Li-Chia Liu (Marine Biology, 2018)

Effect of UGT2B7 genotypes on plasma concentration of valproic acid: a meta-analysis - Ping Wang; Xiao-Qian Lin; Wen-Ke Cai; Gui-Li Xu; Meng-Di Zhou; Mei Yang; Gong-Hao He (European Journal of Clinical Pharmacology, 2018)

Effect of dietary phospholipid levels on growth, lipid metabolism, and antioxidative status of juvenile hybrid snakehead (Channa argus×Channa maculata) - Shi-Mei Lin; Fa-Jian Li; Bundit Yuangsoi; Sompong Doolgindachbaporn (Fish Physiology and Biochemistry, 2018)

Epidemiology and clinical characteristics of human coronaviruses OC43, 229E, NL63, and HKU1: a study of hospitalized children with acute respiratory tract infection in Guangzhou, China - Zhi-Qi Zeng; De-Hui Chen; Wei-Ping Tan; Shu-Yan Qiu; Duo Xu; Huan-Xi Liang; Mei-Xin Chen; Xiao Li; Zheng-Shi Lin; Wen-Kuan Liu; Rong Zhou (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Barcode index numbers expedite quarantine inspections and aid the interception of nonindigenous mealybugs (Pseudococcidae) - Jing-Mei Ren; Muhammad Ashfaq; Xu-Nan Hu; Jun Ma; Fan Liang; Paul D. N. Hebert; Li Lin; Jean François Germain; Muhammad Z. Ahmed (Biological Invasions, 2018)

PAX3 Promotes Cell Migration and CXCR4 Gene Expression in Neural Crest Cells - Man Xu; Yongle Li; Jinfeng Du; Hengrong Lin; Sixian Cao; Zuming Mao; Ronghua Wu; Mei Liu; Yan Liu; Qiyou Yin (Journal of Molecular Neuroscience, 2018)

Tamoxifen usage correlates with increased risk of Parkinson’s disease in older women with breast cancer: a case–control study in Taiwan - Hsien-Feng Lin; Kuan-Fu Liao; Ching-Mei Chang; Cheng-Li Lin; Shih-Wei Lai (European Journal of Clinical Pharmacology, 2018)

Association of use of selective serotonin reuptake inhibitors with risk of acute pancreatitis: a case-control study in Taiwan - Hsien-Feng Lin; Kuan-Fu Liao; Ching-Mei Chang; Cheng-Li Lin; Shih-Wei Lai (European Journal of Clinical Pharmacology, 2017)

Assessment of germling ability of the introduced marine brown alga, Sargassum horneri, in Northern Taiwan - Showe-Mei Lin; Roger Huang; Hisao Ogawa; Li-Chia Liu; Yi-Chi Wang; Yushan Chiou (Journal of Applied Phycology, 2017)

Community responses to dam removal in a subtropical mountainous stream - Hao-Yen Chang; Ming-Chih Chiu; Yi-Li Chuang; Chyng-Shyan Tzeng; Mei-Hwa Kuo; Chao-Hsien Yeh; Hsiao-Wen Wang; Sheng-Hai Wu; Wen-Hui Kuan; Shang-Te Tsai; Kwang-Tsao Shao; Hsing-Juh Lin (Aquatic Sciences, 2017)

Correlation between proton pump inhibitors and risk of pyogenic liver abscess - Hsien-Feng Lin; Kuan-Fu Liao; Ching-Mei Chang; Cheng-Li Lin; Shih-Wei Lai (European Journal of Clinical Pharmacology, 2017)

Suppressive effect of microRNA319 expression on rice plant height - Wei-Ting Liu; Peng-Wen Chen; Li-Chi Chen; Chia-Chun Yang; Shu-Yun Chen; GuanFu Huang; Tzu Che Lin; Hsin-Mei Ku; Jeremy J. W. Chen (Theoretical and Applied Genetics, 2017)

Grape hexokinases are involved in the expression regulation of sucrose synthase- and cell wall invertase-encoding genes by glucose and ABA - Xiu-Qin Wang; Li-Li Zheng; Hao Lin; Fei Yu; Li-Hui Sun; Li-Mei Li (Plant Molecular Biology, 2017)

Epigenetic Downregulation of Scn3a Expression by Valproate: a Possible Role in Its Anticonvulsant Activity - Na-Na Tan; Hui-Ling Tang; Guo-Wang Lin; Yong-Hong Chen; Ping Lu; Hai-Jun Li; Mei-Mei Gao; Qi-Hua Zhao; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Molecular Neurobiology, 2017)

MicroRNA-27a Promotes Inefficient Lysosomal Clearance in the Hippocampi of Rats Following Chronic Brain Hypoperfusion - Hui Che; Yan Yan; Xiao-Hui Kang; Fei Guo; Mei-Ling Yan; Huai-Lei Liu; Xu Hou; Tong Liu; De-Kang Zong; Lin-Lin Sun; Ya-Nan Bao; Li-Hua Sun; et al. (Molecular Neurobiology, 2017)

Simulating climate change impacts and potential adaptations on rice yields in the Sichuan Basin, China - Che-Chen Xu; Wen-Xiang Wu; Quan-Sheng Ge; Yang Zhou; Yu-Mei Lin; Ya-Mei Li (Mitigation and Adaptation Strategies for Global Change, 2017)

Effects of soybean meal processing treatments on growth performance, nutrient digestibility, nitrogen and phosphorus excretion in red swamp crayfish, Procambarus clarkii - Jin-juan Wan; Mei-fang Shen; Jian-qing Tang; Hai Lin; Wei-hui Yan; Jia-jia Li; Lin Zhu (Aquaculture International, 2017)

Detection of chlorophylls in spores of seven ferns - Mei-Hwei Tseng; Kuei-Huei Lin; Yi-Jia Huang; Ya-Lan Chang; Sheng-Cih Huang; Li-Yaung Kuo; Yao-Moan Huang (Journal of Plant Research, 2017)

Insulin-independent GLUT4 translocation in proliferative vascular smooth muscle cells involves SM22α - Li-Li Zhao; Fan Zhang; Peng Chen; Xiao-Li Xie; Yong-Qing Dou; Yan-Ling Lin; Lei Nie; Pin Lv; Dan-Dan Zhang; Xiao-Kun Li; Sui-Bing Miao; Ya-Juan Yin; et al. (Journal of Molecular Medicine, 2017)

Predatory efficiency of the copepod Megacyclops formosanus and toxic effect of the red alga Gracilaria firma-synthesized silver nanoparticles against the dengue vector Aedes aegypti - Kandasamy Kalimuthu; Chellasamy Panneerselvam; Chi Chou; Showe-Mei Lin; Li-Chun Tseng; Kun-Hsien Tsai; Kadarkarai Murugan; Jiang-Shiou Hwang (Hydrobiologia, 2017)

Species-specific effects of leaf litter on seedling emergence and growth of the invasive Flaveria bidentis and its co-occurring native species: a common garden test - Ke-li Li; Hui-yan Li; Chao-he Huangfu; Dian-lin Yang; Hong-mei Liu; Hui Wang (Plant Ecology, 2016)

Halorussus salinus sp. nov., isolated from a marine solar saltern - Jia-Qi Xu; Wen-Mei Xu; Yang Li; Yao Zhou; Zhen-Zhen Lü; Jing Hou; Lin Zhu; Heng-Lin Cui (Archives of Microbiology, 2016)

RhoB/ROCK mediates oxygen–glucose deprivation-stimulated syncytiotrophoblast microparticle shedding in preeclampsia - Jian Han; Bo-ping Yang; Yi-lin Li; Hong-mei Li; Xiu-hui Zheng; Li-li Yu; Qiong Zhang; Ying-ru Zheng; Ping Yi; Li Li; Jian-xin Guo; Yuan-guo Zhou (Cell and Tissue Research, 2016)

Combined effects of age and polymorphisms in Notch3 in the pathogenesis of cerebral infarction disease - Chun-Yu Zhu; Yue Wang; Qing-Xuan Zeng; Yu Qian; Huan Li; Zi-Xia Yang; Ya-Mei Yang; Qiong Zhang; Fei-Feng Li; Shu-Lin Liu (Metabolic Brain Disease, 2016)

Bis(maltolato)oxovanadium(IV) (BMOV) Attenuates Apoptosis in High Glucose-Treated Cardiac Cells and Diabetic Rat Hearts by Regulating the Unfolded Protein Responses (UPRs) - Xiao-Qiang Cong; Mei-Hua Piao; Ying Li; Lin Xie; Ya Liu (Biological Trace Element Research, 2016)

Dietary lipid concentrations influence growth, liver oxidative stress, and serum metabolites of juvenile hybrid snakehead (Channa argus × Channa maculata) - Peng-Fei Zhao; Fa-Jian Li; Xiao-Ru Chen; Yong-Jun Chen; Shi-Mei Lin; Lu Zhang; Yun Li (Aquaculture International, 2016)

Synergistic antitumor activity of triple-regulated oncolytic adenovirus with VSTM1 and daunorubicin in leukemic cells - Jiao Zhou; Qiu-Mei Yao; Jin-Lan Li; Yan Chang; Ting Li; Wen-Ling Han; Hong-Ping Wu; Lin-Fang Li; Qi-Jun Qian; Guo-Rui Ruan (Apoptosis, 2016)

High seroprevalence of toxoplasma gondii and HIV-1 co-infection among drug users in Yunnan province, southwest China - Xin Chen; Mei Ye; Yan-Heng Zhou; Feng-Liang Liu; Lin Duo; Hong Li; Wei Pang; Yong-Tang Zheng (Science China Life Sciences, 2016)

Halomarina salina sp. nov., isolated from a marine solar saltern - Wen-Mei Xu; Jia-Qi Xu; Yao Zhou; Yang Li; Zhen-Zhen Lü; Jing Hou; Lin Zhu; Heng-Lin Cui (Antonie van Leeuwenhoek, 2016)

A pilot study on using chlorine dioxide gas for disinfection of gastrointestinal endoscopes - Ying Yi; Li-mei Hao; Shu-ren Ma; Jin-hui Wu; Tao Wang; Song Lin; Zong-xing Zhang; Jian-cheng Qi (Journal of Zhejiang University-SCIENCE B, 2016)

Paraventricular Nucleus Infusion of Epigallocatechin-3-O-Gallate Improves Renovascular Hypertension - Qiu-Yue Yi; Jie Qi; Xiao-Jing Yu; Hong-Bao Li; Yan Zhang; Qing Su; Tao Shi; Dong-Mei Zhang; Jing Guo; Zhi-Peng Feng; Mo-Lin Wang; Guo-Qing Zhu; et al. (Cardiovascular Toxicology, 2016)

Improvement of soybean transformation via Agrobacterium tumefaciens methods involving α-aminooxyacetic acid and sonication treatments enlightened by gene expression profile analysis - Yan-Min Zhang; Zi-Hui Liu; Rui-Juan Yang; Guo-Liang Li; Xiu-Lin Guo; Hua-Ning Zhang; Hong-Mei Zhang; Rui Di; Qing-Song Zhao; Meng-Chen Zhang (Plant Cell Reports, 2016)

Calcitriol regulates angiotensin-converting enzyme and angiotensin converting-enzyme 2 in diabetic kidney disease - Mei Lin; Ping Gao; Tianya Zhao; Lei He; Mengshi Li; Yaoyao Li; Hua Shui; Xiaoyan Wu (Molecular Biology Reports, 2016)

Context- and time-dependent neurobiological and behavioral sensitization induced by a single morphine exposure in mice - Wang-Jun Qin; Yan-Ting Wang; Peng-Mei Li; Xiao-Xing Wang; Jun-Xu Li; Hamid R. Noori; Rick E. Bernardi; Jian-Hui Liang; Xiang-Lin Zhang (Psychopharmacology, 2016)

Upregulation of Dickkopf1 by oscillatory shear stress accelerates atherogenesis - Mengmeng Li; Xinxin Liu; Yu Zhang; Mingxue Di; Han Wang; Lin Wang; Yifei Chen; Xiaoling Liu; Xiaoqing Cao; Renya Zeng; Yun Zhang; Mei Zhang (Journal of Molecular Medicine, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Phylogenetic relationships and Y genome origin in Kengyilia (Triticeae: Poaceae) based on single copy gene DMC1 - Gang Gao; Zi-lin Tang; Jia-bin Deng; Xue-mei Gou; Qian Wang; Yan Zhang; Chun-bang Ding; Li Zhang; Yong-hong Zhou; Rui-wu Yang (Biologia, 2016)

Species-specific differences in the role of L-type Ca2+ channels in the regulation of coronary arterial smooth muscle contraction - Hui Yang; Su-Juan Kuang; Fang Rao; Yu-Mei Xue; Xiao-Ying Liu; Zhi-Xin Shan; Xiao-Hong Li; Jie-Ning Zhu; Zhi-Ling Zhou; Xiao-juan Zhang; Qiu-Xiong Lin; Xi-Yong Yu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Effect of fish oil supplement in maintenance hemodialysis patients: a systematic review and meta-analysis of published randomized controlled trials - Lei He; Meng-si Li; Mei Lin; Tian-ya Zhao; Ping Gao (European Journal of Clinical Pharmacology, 2016)

Development of single-chain variable fragments (scFv) against influenza virus targeting hemagglutinin subunit 2 (HA2) - Tai-Wei Li; Shu-Fang Cheng; Yen-Tzu Tseng; Yu-Chih Yang; Wen-chun Liu; Sheng-Cyuan Wang; Mei-Ju Chou; Yu-Jen Lin; Yueh Wang; Pei-Wen Hsiao; Suh-Chin Wu; Ding-Kwo Chang (Archives of Virology, 2016)

Floral Transcriptome Analyses of Four Paphiopedilum Orchids with Distinct Flowering Behaviors and Development of Simple Sequence Repeat Markers - Dong-Mei Li; Wei Wu; Di Zhang; Xiao-Rong Liu; Xiao-Fei Liu; Yi-Jian Lin (Plant Molecular Biology Reporter, 2015)

Social Isolation During Adolescence Strengthens Retention of Fear Memories and Facilitates Induction of Late-Phase Long-Term Potentiation - Ji-Hong Liu; Qiang-Long You; Mei-Dan Wei; Qian Wang; Zheng-Yi Luo; Song Lin; Lang Huang; Shu-JI Li; Xiao-Wen Li; Tian-Ming Gao (Molecular Neurobiology, 2015)

Wide-angle incidence and P-wave transmission - Jun-Fa Xie; Cheng-Yu Sun; Mei-Yan Lin; Jing-Jing Li (Applied Geophysics, 2015)

Enteractinococcus lamae sp. nov. and Enteractinococcus viverrae sp. nov., isolated from animal faeces - Xiu Chen; Gui-Ding Li; Qin-Yuan Li; Cai-Juan Hu; Shu-Mei Qiu; Yi Jiang; Cheng-Lin Jiang; Li Han; Xue-Shi Huang (Antonie van Leeuwenhoek, 2015)

Soil labile organic carbon fractions in rhizosphere soil in citrus plantations in the Three Gorges Reservoir Area - Guo-Mei Jia; Bao-Lin Zhang; Jun-Tao Niu; Li-Ming Wang; Fang-Qing Chen (Agroforestry Systems, 2015)

Sphingobacterium rhinocerotis sp. nov., isolated from the faeces of Rhinoceros unicornis - Gui-Ding Li; Xiu Chen; Qin-Yuan Li; Fang-Ji Xu; Shu-Mei Qiu; Yi Jiang; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2015)

Retraction Note to: Lactoferrin promote primary rat osteoblast proliferation and differentiation via up-regulation of insulin-like growth factor-1 expression - Jian-ming Hou; Man Wu; Qing-ming Lin; Fan Lin; Ying Xue; Xu-hua Lan; En-yu Chen; Mei-li Wang; Hai-yan Yang; Feng-xiong Wang (Molecular Biology Reports, 2015)

Effect of antioxidants and light stabilisers on silver migration from nanosilver-polyethylene composite packaging films into food simulants - Qi-Zhi Su; Qin-Bao Lin; Chao-Fang Chen; Yu-Mei Wu; Li-Bing Wu; Xiao-Qing Chen; Zhi-Wei Wang (Food Additives & Contaminants: Part A, 2015)

Endoplasmic Reticulum Protein 29 Protects Axotomized Neurons from Apoptosis and Promotes Neuronal Regeneration Associated with Erk Signal - Yun-Hui Zhang; Visar Belegu; Yu Zou; Fang Wang; Bao-Jiang Qian; Ran Liu; Ping Dai; Wei Zhao; Fa-Bao Gao; Lei Wang; Li-Mei Cao; John W. McDonald; et al. (Molecular Neurobiology, 2015)

Effects of Fluoride on DNA Damage and Caspase-Mediated Apoptosis in the Liver of Rats - Guo Hua Song; Fu Bing Huang; Ji Ping Gao; Mao Lin Liu; Wen Biao Pang; Wei bin Li; Xiao Yan Yan; Mei Jun Huo; Xia Yang (Biological Trace Element Research, 2015)

Identification of a novel compound heterozygous mutation in PTPRQ in a DFNB84 family with prelingual sensorineural hearing impairment - Qing Sang; Honglin Mei; Ahan Kuermanhan; Ruizhi Feng; Luo Guo; Ronggui Qu; Yao Xu; Huawei Li; Li Jin; Lin He; Lei Wang (Molecular Genetics and Genomics, 2015)

A Novel Oral Preparation of Hydroxysafflor Yellow A Base on a Chitosan Complex: A Strategy to Enhance the Oral Bioavailability - Guan-nan Ma; Fang-lin Yu; Shan Wang; Zhi-ping Li; Xiang-yang Xie; Xing-guo Mei (AAPS PharmSciTech, 2015)

Smooth muscle 22α facilitates angiotensin II-induced signaling and vascular contraction - Xiao-Li Xie; Xi Nie; Jun Wu; Fan Zhang; Li-Li Zhao; Yan-Ling Lin; Ya-Juan Yin; Hui Liu; Ya-Nan Shu; Sui-Bing Miao; Huan Li; Peng Chen; et al. (Journal of Molecular Medicine, 2015)

The effects of land use and landscape position on labile organic carbon and carbon management index in red soil hilly region, southern China - Zhong-wu Li; Xiao-dong Nie; Xiao-lin Chen; Yin-mei Lu; Wei-guo Jiang; Guang-ming Zeng (Journal of Mountain Science, 2015)

Ectopic expression of a phytochrome B gene from Chinese cabbage (Brassica rapa L. ssp. pekinensis) in Arabidopsis thaliana promotes seedling de-etiolation, dwarfing in mature plants, and delayed flowering - Mei-Fang Song; Shu Zhang; Pei Hou; Hong-Zhong Shang; Hai-Ke Gu; Jing-Juan Li; Yang Xiao; Lin Guo; Liang Su; Jian-Wei Gao; Jian-Ping Yang (Plant Molecular Biology, 2015)

Inhibition of isoflavone biosynthesis enhanced T-DNA delivery in soybean by improving plant–Agrobacterium tumefaciens interaction - Yan-Min Zhang; Hong-Mei Zhang; Zi-Hui Liu; Xiu-Lin Guo; Hui-Cong Li; Guo-Liang Li; Chun-Zhi Jiang; Meng-Chen Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Characteristics of Na+ uptake in sugar beet (Beta vulgaris L.) seedlings under mild salt conditions - Guo-Qiang Wu; Qing-Zhao Shui; Chun-Mei Wang; Jin-Lin Zhang; Hui-Jun Yuan; Shan-Jia Li; Zuo-Jun Liu (Acta Physiologiae Plantarum, 2015)

Anxiolytic effects of ketamine in animal models of posttraumatic stress disorder - Li-Ming Zhang; Wen-Wen Zhou; Ya-Jun Ji; Ying Li; Nan Zhao; Hong-Xia Chen; Rui Xue; Xin-Guo Mei; You-Zhi Zhang; Heng-Lin Wang; Yun-Feng Li (Psychopharmacology, 2015)

The wheat NHX antiporter gene TaNHX2 confers salt tolerance in transgenic alfalfa by increasing the retention capacity of intracellular potassium - Yan-Min Zhang; Hong-Mei Zhang; Zi-Hui Liu; Hui-Cong Li; Xiu-Lin Guo; Guo-Liang Li (Plant Molecular Biology, 2015)

Bioaugmentation of a sequencing batch biofilm reactor with Comamonas testosteroni and Bacillus cereus and their impact on reactor bacterial communities - Zhongqin Cheng; Mei Chen; Liqun Xie; Lin Peng; Maohua Yang; Mengying Li (Biotechnology Letters, 2015)

Primary succession of soil enzyme activity and heterotrophic microbial communities along the chronosequence of Tianshan Mountains No. 1 Glacier, China - Jun Zeng; Xiao-xia Wang; Kai Lou; Moniruzzaman Khan Eusufzai; Tao Zhang; Qing Lin; Ying-wu Shi; Hong-mei Yang; Zhong-qing Li (Antonie van Leeuwenhoek, 2015)

Bio-efficacy potential of seaweed Gracilaria firma with copepod, Megacyclops formosanus for the control larvae of dengue vector Aedes aegypti - Kandasamy Kalimuthu; Show-Mei Lin; Li-Chun Tseng; Kadarkarai Murugan; Jiang-Shiou Hwang (Hydrobiologia, 2014)

TGFβ can stimulate the p38/β-catenin/PPARγ signaling pathway to promote the EMT, invasion and migration of non-small cell lung cancer (H460 cells) - Li-Chiung Lin; Shih-Lan Hsu; Chieh-Liang Wu; Chi-Mei Hsueh (Clinical & Experimental Metastasis, 2014)

Two new truffles species, Tuber alboumbilicum and Tuber pseudobrumale from China - Shu-Hong Li; Lin-Yong Zheng; Cheng-Yi Liu; Yun Wang; Lin Li; Yong-Chang Zhao; Xiao-Lei Zhang; Mei Yang; Hai-Kuan Xiong; Yuan Qing; Li Wang; De-Qun Zhou (Mycological Progress, 2014)

Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Activation of GABAB Receptors Ameliorates Cognitive Impairment via Restoring the Balance of HCN1/HCN2 Surface Expression in the Hippocampal CA1 Area in Rats With Chronic Cerebral Hypoperfusion - Chang-jun Li; Yun Lu; Mei Zhou; Xian-gang Zong; Cai Li; Xu-lin Xu; Lian-jun Guo; Qing Lu (Molecular Neurobiology, 2014)

Shinjulactone O, a new quassinoid from the root bark of Ailanthus altissima - Xiao-Lin Yang; Yong-Liang Yuan; Dong-Mei Zhang; Fei Li; Wen-Cai Ye (Natural Product Research, 2014)

RETRACTED ARTICLE: Lactoferrin promote primary rat osteoblast proliferation and differentiation via up-regulation of insulin-like growth factor-1 expression - Jian-ming Hou; Man Wu; Qing-ming Lin; Fan Lin; Ying Xue; Xu-hua Lan; En-yu Chen; Mei-li Wang; Hai-yan Yang; Feng-xiong Wang (Molecular Biology Reports, 2014)

Identification and expression of the elongator protein 2 (Ajelp2) gene, a novel regeneration-related gene from the sea cucumber Apostichopus japonicus - Yanli Mei; Feng Yao; Yang Wu; Bing Chu; Cheng Cheng; Yan Liu; Xuejie Li; Xiangyang Zou; Lin Hou (Molecular Biology Reports, 2014)

Molecular modeling study on the structural basis of binding mechanism of C6-substituted phthalides with monoamine oxidases - Pei Zhen Li; Yue Li Tian; Hong Lin Zhai; Fang Fang Deng; Mei Hong Xie; Xiao Yun Zhang (Medicinal Chemistry Research, 2014)

A new epimer of ocotillol from stems and leaves of American ginseng - Liu Han; Mei-Yu Lin; Qian Zheng; Hai-Yu Liu; Hai-Yan Liu; Gang Dong; Jin-Ping Liu; Ping-Ya Li (Natural Product Research, 2014)

Urinary Perchlorate Exposure and Risk in Women of Reproductive Age in a Fireworks Production Area of China - Qin Li; Yun-jiang Yu; Fei-fei Wang; Shi-wu Chen; Yan Yin; Hai-peng Lin; Fei Che; Peng Sun; Juan Qin; Jie Liu; Hong-mei Wang (Archives of Environmental Contamination and Toxicology, 2014)

Differential proteome analysis of mature and germinated seeds of Magnolia sieboldii K. Koch - Xiao-lin Zhang; Guang-lin Liu; Tian-lai Li; Ming-fang Qi; Mei Mei; Xiu-jun Lu (Trees, 2014)

Plutonium partitioning in three-phase systems with water, granite grains, and different colloids - Jinchuan Xie; Jianfeng Lin; Xiaohua Zhou; Mei Li; Guoqing Zhou (Environmental Science and Pollution Research, 2014)

Cloning and expression analysis of the gene encoding fibrinogen-like protein A, a novel regeneration-related protein from Apostichopus japonicus - Yang Wu; Feng Yao; Yanli Mei; Bing Chu; Cheng Cheng; Yan Liu; Xuejie Li; Xiangyang Zou; Lin Hou (Molecular Biology Reports, 2014)

MiR-200a is involved in proliferation and apoptosis in the human endometrial adenocarcinoma cell line HEC-1B by targeting the tumor suppressor PTEN - Rong Li; Jun-lin He; Xue-mei Chen; Chun-Lan Long; De-Hui Yang; Yu-Bin Ding; Hong-Bo Qi; Xue-Qing Liu (Molecular Biology Reports, 2014)

Primordial follicle assembly was regulated by notch signaling pathway in the mice - Chun-Lei Chen; Xia-Fei Fu; Lin-Qing Wang; Jun-Jie Wang; Hua-Gang Ma; Shun-Feng Cheng; Zhu-Mei Hou; Jin-Mei Ma; Guo-Bo Quan; Wei Shen; Lan Li (Molecular Biology Reports, 2014)

XPC Lys939Gln and Ala499Val polymorphisms in colorectal cancer susceptibility: a meta-analysis of case–control studies - Chuan Liu; Qinghua Yin; Mingzhen Ying; Junhui Lin; Lian Li; Guangjun Jiao; Mei Wang; Yajie Wang (Molecular Biology Reports, 2014)

Distribution of nutrients, heavy metals, and PAHs affected by sediment dredging in the Wujin'gang River basin flowing into Meiliang Bay of Lake Taihu - Rongfei Zhang; Dongsheng Jiang; Liujun Zhang; Yibin Cui; Mei Li; Lin Xiao (Environmental Science and Pollution Research, 2014)

Halobellus litoreus sp. nov., a Halophilic Archaeon Isolated from a Chinese Marine Solar Saltern - Mei-Lin Zhao; Xing-Xing Qiu; Wen-Jiao Zhang; Dong Han; Heng-Lin Cui; Zheng-Rong Li (Current Microbiology, 2014)

Artificial antigen synthesis and the development of polyclonal antibody-based immunoassay for citreoviridin determination - Zhen Hong Zhuang; Shan Jin Que; Yue Ming Gao; Jun Yuan; Zhou Ye; Min Du; Guang Mei Lin; Li Cai Liu; Shi Hua Wang (World Journal of Microbiology and Biotechnology, 2014)

MicroRNA Expression Aberration in Chinese Patients with Relapsing Remitting Multiple Sclerosis - Dan Yang; Wei-Zhi Wang; Xue-Mei Zhang; Hui Yue; Bing Li; Lin Lin; Jin Fu (Journal of Molecular Neuroscience, 2014)

Genetic variation in alkaloid accumulation in leaves of Nicotiana - Bo Sun; Fen Zhang; Guo-jun Zhou; Guo-hai Chu; Fang-fang Huang; Qiao-mei Wang; Li-feng Jin; Fu-cheng Lin; Jun Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Synthesis, characterization, and DNA binding of a novel ligand and its Cu(II) complex - Mei-Jin Li; Tao-Yu Lan; Zhi-Shan Lin; Changqing Yi; Guo-Nan Chen (JBIC Journal of Biological Inorganic Chemistry, 2013)

Hierarchically Clustering to 1,033 Genes Differentially Expressed in Mouse Superior Colliculus in the Courses of Optic Nerve Development and Injury - Qiang Mei; Yan-qi Zhang; Jian-jun Liu; Cheng-ren Li; Xing-shu Chen; Hong-li Li; Mao-lin Qin; Ya-zhou wu; Yun-lai Liu; Wen-qin Cai (Cell Biochemistry and Biophysics, 2013)

Vascular endothelial growth factor (VEGF) gene polymorphisms and risk of head and neck cancer: a meta-analysis involving 2,444 individuals - Wei-Dong Leng; Mei-Ni He; Qi-Lin Chen; Heng Gong; Li Zhang; Xian-Tao Zeng (Molecular Biology Reports, 2013)

Epidemiology and full genome sequence analysis of H1N1pdm09 from Northeast China - Xiaoyan Li; Mei Kong; Jinying Chen; Xu Su; Ming Zou; Liru Guo; Lin Li; Jianqing Ding (Virus Genes, 2013)

A novel role of ribonuclease inhibitor in regulation of epithelial-to-mesenchymal transition and ILK signaling pathway in bladder cancer cells - Xue Yao; Dan Li; Dong-mei Xiong; Lin Li; Rong Jiang; Jun-xia Chen (Cell and Tissue Research, 2013)

Halobellus rarus sp. nov., a halophilic archaeon from an inland salt lake of China - Wen-Jiao Zhang; Dong Han; Xing-Xing Qiu; Mei-Lin Zhao; Yun-Zhuang Mou; Heng-Lin Cui; Zheng-Rong Li (Antonie van Leeuwenhoek, 2013)

Novel triterpenoid saponins from the seeds of Celosia argentea L. - Qing Bin Wu; Yan Wang; Lin Liang; Qian Jiang; Mei Li Guo; Jun Jie Zhang (Natural Product Research, 2013)

Al-enhanced Expression and Interaction of 14-3-3 Protein and Plasma Membrane H+-ATPase is Related to Al-induced Citrate Secretion in an Al-resistant Black Soybean - Chuan-Long Guo; Qi Chen; Xiu-Ling Zhao; Xuan-qian Chen; Yan Zhao; Lin Wang; Kui-Zhi Li; Yong-Xiong Yu; Li-Mei Chen (Plant Molecular Biology Reporter, 2013)

Genetic diversity and evolutionary characterization of Chinese porcine reproductive and respiratory syndrome viruses based on NSP2 and ORF5 - Jian-Kui Liu; Chun-Hua Wei; Xiao-Yan Yang; Xi-Lin Hou; AI-Ling Dai; Xiao-Hua Li; Mei-Kang Wei; Xiu-Zhen Pan (Archives of Virology, 2013)

Inhibition of formyl peptide-stimulated phospholipase D activation by Fal-002-2 via blockade of the Arf6, RhoA and protein kinase C signaling pathways in rat neutrophils - Ya-Ru Tsai; Li-Jiau Huang; Hui-Yi Lin; Yun-Jie Hung; Miau-Rong Lee; Sheng-Chu Kuo; Mei-Feng Hsu; Jih-Pyang Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Levosimendan versus dobutamine in critically ill patients: a meta-analysis of randomized controlled trials - Xuan Huang; Shu Lei; Mei-fei Zhu; Rong-lin Jiang; Li-quan Huang; Guo-lian Xia; Yi-hui Zhi (Journal of Zhejiang University-SCIENCE B, 2013)

Purification and characterization of alkaline phosphatase from the gut of sea cucumber Stichopus japonicus - Hai-Tao Wu; Dong-Mei Li; Bei-Wei Zhu; Jing-Heng Cheng; Jin-Jian Sun; Feng-Lin Wang; Yang Yang; Yu-Kun Song; Chen-Xu Yu (Fisheries Science, 2013)

RETRACTED ARTICLE: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Identification of genetic associations of SP110/MYBBP1A/RELA with pulmonary tuberculosis in the Chinese Han population - Lei Cai; Shao-Li Deng; Li Liang; Hui Pan; Jia Zhou; Mei-Yan Wang; Jun Yue; Chun-Ling Wan; Guang He; Lin He (Human Genetics, 2013)

Docetaxel-loaded liposomes: preparation, pH sensitivity, Pharmacokinetics, and tissue distribution - Hong Zhang; Rui-ying Li; Xia Lu; Zhen-zhen Mou; Gui-mei Lin (Journal of Zhejiang University-SCIENCE B, 2012)

Haem Oxygenase-1 is Involved in Hydrogen Sulfide-induced Cucumber Adventitious Root Formation - Yu-Ting Lin; Mei-Yue Li; Wei-Ti Cui; Wei Lu; Wen-Biao Shen (Journal of Plant Growth Regulation, 2012)

Identification, fine mapping and characterization of Rht-dp, a recessive wheat dwarfing (reduced height) gene derived from Triticum polonicum - Hou-Yang Kang; Li-Juan Lin; Zhi-Jian Song; Jing-Ya Yuan; Mei-Yu Zhong; Hai-Qin Zhang; Xing Fan; Li-Na Sha; Yi Wang; Li-Li Xu; Jian Zeng; Yong-Hong Zhou (Genes & Genomics, 2012)

Rhodococcus sp. Q5, a novel agarolytic bacterium isolated from printing and dyeing wastewater - Zehua Feng; Lin Peng; Mei Chen; Mengying Li (Folia Microbiologica, 2012)

Production of monoclonal antibody and application in indirect competitive ELISA for detecting okadaic acid and dinophytoxin-1 in seafood - Shi-Ying Lu; Yu Zhou; Yan-Song Li; Chao Lin; Xian-Mei Meng; Dong-Ming Yan; Zhao-Hui Li; Shi-Yu Yu; Zeng-Shan Liu; Hong-Lin Ren (Environmental Science and Pollution Research, 2012)

Spatial variation of bacterial community structure of the Northern South China Sea in relation to water chemistry - Juan Ling; Jun-De Dong; You-Shao Wang; Yan-Ying Zhang; Chao Deng; Li Lin; Mei-Lin Wu; Fu-Lin Sun (Ecotoxicology, 2012)

Celecoxib inhibits growth of human autosomal dominant polycystic kidney cyst-lining epithelial cells through the VEGF/Raf/MAPK/ERK signaling pathway - Tao Xu; Nian-Song Wang; Li-Li Fu; Chao-Yang Ye; Sheng-Qiang Yu; Chang-Lin Mei (Molecular Biology Reports, 2012)

Cloning and expression of the two new variants of Nav1.5/SCN5A in rat brain - Cheng-Tao Ren; Dong-Mei Li; Shao-Wu Ou; Yun-Jie Wang; Yi Lin; Zhi-Hong Zong; Masaki Kameyama; Asako Kameyama (Molecular and Cellular Biochemistry, 2012)

Effect of Selenium on the Interaction Between Daunorubicin and Cardiac Myosin - Yang Liu; Bu-hai Li; Xiao-mei Sun; Ai-hua Lin; De-bin Wang (Biological Trace Element Research, 2012)

Risk stratification of spontaneous bacterial peritonitis in cirrhosis with ascites based on classification and regression tree analysis - Ke-Qing Shi; Yu-Chen Fan; Li Ying; Xian-Feng Lin; Mei Song; Ling-Fei Li; Xie-Yan Yu; Yong-Ping Chen; Ming-Hua Zheng (Molecular Biology Reports, 2012)

Differential DNA Methylation Status Between Human Preadipocytes and Mature Adipocytes - Jin-gai Zhu; Li Xia; Chen-bo Ji; Chun-mei Zhang; Guan-zhong Zhu; Chun-mei Shi; Lin Chen; Da-ni Qin; Xi-rong Guo (Cell Biochemistry and Biophysics, 2012)

Interaction between iron plaque and root border cells ameliorates aluminum toxicity of Oryza sativa differing in aluminum tolerance - Miao-Zhen Cai; Shu-Na Zhang; Cheng-Hua Xing; Fang-Mei Wang; Lei Zhu; Ning Wang; Li-Yu Lin (Plant and Soil, 2012)

Inhibitor of DNA-binding-1/inhibitor of differentiation-1 (ID-1) is implicated in various aspects of gastric cancer cell biology - Wei Li; Chun-Hua Zhang; Yi-Lin Hong; Jun Li; Yong-Mei Hu; Cui-Fen Zhao (Molecular Biology Reports, 2012)

Distribution and expression characteristics of triterpenoids and OSC genes in white birch (Betula platyphylla suk.) - Jing Yin; Chun-Lin Ren; Ya-Guang Zhan; Chun-Xiao Li; Jia-Lei Xiao; Wei Qiu; Xin-Yu Li; Hong-Mei Peng (Molecular Biology Reports, 2012)

MicroRNA- 1 represses Cx43 expression in viral myocarditis - Hong-Fei Xu; Yu-Jie Ding; Yi-Wen Shen; Ai-Min Xue; Hong-Mei Xu; Cheng-Liang Luo; Bei-Xu Li; Yue-Lin Liu; Zi-Qin Zhao (Molecular and Cellular Biochemistry, 2012)

Functional analysis of Waardenburg syndrome-associated PAX3 and SOX10 mutations: report of a dominant-negative SOX10 mutation in Waardenburg syndrome type II - Hua Zhang; Hongsheng Chen; Hunjin Luo; Jing An; Lin Sun; Lingyun Mei; Chufeng He; Lu Jiang; Wen Jiang; Kun Xia; Jia-Da Li; Yong Feng (Human Genetics, 2012)

Quantification of ecosystem carbon exchange characteristics in a dominant subtropical evergreen forest ecosystem - Yue-Lin Li; Guo-Yi Zhou; De-Qiang Zhang; Katherine Owen Wenigmann; Dennis Otieno; John Tenhunen; Qian-Mei Zhang; Jun-Hua Yan (Asia-Pacific Journal of Atmospheric Sciences, 2012)

Chronic alcohol intake-induced oxidative stress and apoptosis: role of CYP2E1 and calpain-1 in alcoholic cardiomyopathy - Ling Jing; Cheng-mei Jin; Shan-shan Li; Feng-min Zhang; Lin Yuan; Wei-min Li; Ying Sang; Shuang Li; Li-jun Zhou (Molecular and Cellular Biochemistry, 2012)

Gambogenic acid-induced time- and dose-dependent growth inhibition and apoptosis involving Akt pathway inactivation in U251 glioblastoma cells - Hong-Bo Chen; Lan-Zhen Zhou; Lin Mei; Xiao-Jun Shi; Xiao-Shan Wang; Qing-Lin Li; Laiqiang Huang (Journal of Natural Medicines, 2012)

Isolation and identification of an acetoin high production bacterium that can reverse transform 2,3-butanediol to acetoin at the decline phase of fermentation - Xian Zhang; Tao-wei Yang; Qing Lin; Mei-juan Xu; Hai-feng Xia; Zheng-hong Xu; Hua-zhong Li; Zhi-ming Rao (World Journal of Microbiology and Biotechnology, 2011)

Chemical composition of precipitation and its sources in Hangzhou, China - Hong Xu; Xiao-Hui Bi; Yin-Chang Feng; Feng-Mei Lin; Li Jiao; Sheng-Mao Hong; Wen-Gao Liu; Xiao-Yong Zhang (Environmental Monitoring and Assessment, 2011)

Effect of Different Iodine Nutrition on Cerebellum Pcp-2 in Rat Offspring During Lactation - Lu Zhang; Yi Na Sun; Yong Mei Li; Lai Xiang Lin; Yan Ye; Yu Qin Yan; Zu Pei Chen (Biological Trace Element Research, 2011)

Replicative senescence of human bone marrow and umbilical cord derived mesenchymal stem cells and their differentiation to adipocytes and osteoblasts - HuanChen Cheng; Lin Qiu; Jun Ma; Hao Zhang; Mei Cheng; Wei Li; Xuefei Zhao; Keyu Liu (Molecular Biology Reports, 2011)

Involvement of OsNPR1/NH1 in rice basal resistance to blast fungus Magnaporthe oryzae - Jia-Xun Feng; Lin Cao; Juan Li; Cheng-Jie Duan; Xue-Mei Luo; Ning Le; Haihong Wei; Shujia Liang; Chengcai Chu; Qinghua Pan; Ji-Liang Tang (European Journal of Plant Pathology, 2011)

Calcitonin gene-related peptide released from endothelial progenitor cells inhibits the proliferation of rat vascular smooth muscle cells induced by angiotensin II - Li Fang; Mei-Fang Chen; Zhi-Lin Xiao; Yin Liu; Guo-Long Yu; Xiao-Bin Chen; Xiu-Mei Xie (Molecular and Cellular Biochemistry, 2011)

A study on the effects of the surrounding faults on water loss in the Zoige Wetland, China - Mei Li; Rui Xu; Wendian Huang; Hailong Sun; Lin Luo (Journal of Mountain Science, 2011)

Spatial heterogeneity of bacterial community structure in the sediments of the Pearl River estuary - Fu-Lin Sun; You-Shao Wang; Mei-Lin Wu; Yu-Tu Wang; Qian P. Li (Biologia, 2011)

Health risk of semi-volatile organic pollutants in Wujin river inflow into Taihu Lake - Rongfei Zhang; Weili Wang; Xiaorong Shi; Xiezhi Yu; Mei Li; Lin Xiao; Yibin Cui (Ecotoxicology, 2011)

Interaction of green tea polyphenol epigallocatechin-3-gallate with sunitinib: potential risk of diminished sunitinib bioavailability - Jun Ge; Ben-Xu Tan; Ye Chen; Li Yang; Xing-Chen Peng; Hong-Ze Li; Hong-Jun Lin; Yu Zhao; Meng Wei; Ke Cheng; Long-Hao Li; Hang Dong; et al. (Journal of Molecular Medicine, 2011)

Enhancement of salt tolerance in alfalfa transformed with the gene encoding for betaine aldehyde dehydrogenase - Zi-Hui Liu; Hong-Mei Zhang; Guo-Liang Li; Xiu-Lin Guo; Shou-Yi Chen; Gui-Bo Liu; Yan-Min Zhang (Euphytica, 2011)

Asialoglycoprotein receptor interacts with the preS1 domain of hepatitis B virus in vivo and in vitro - Xi Zhang; Shu-mei Lin; Tian-yan Chen; Min Liu; Feng Ye; Yun-ru Chen; Lei Shi; Ying-li He; Lie-xiu Wu; Shu-qin Zheng; Ying-ren Zhao; Shu-lin Zhang (Archives of Virology, 2011)

Analysis of the Composition and Characteristics of Culturable Endophytic Bacteria Within Subnival Plants of the Tianshan Mountains, Northwestern China - Hong Mei Sheng; Hong Shan Gao; Lin Gui Xue; Shuo Ding; Chun Li Song; Hu Yuan Feng; Li Zhe An (Current Microbiology, 2011)

Isolation of a LEAFY homolog from Populus tomentosa: expression of PtLFY in P. tomentosa floral buds and PtLFY-IR-mediated gene silencing in tobacco (Nicotiana tabacum) - Xin-Min An; Dong-Mei Wang; Ze-Liang Wang; Bo Li; Wen-Hao Bo; Guan-Lin Cao; Zhi-Yi Zhang (Plant Cell Reports, 2011)

A multiple-dose pharmacokinetics of polyethylene glycol recombinant human interleukin-6 (PEG-rhIL-6) in rats - Xue-ling He; Hai-lin Yin; Jiang Wu; Ke Zhang; Yan Liu; Tao Yuan; Hai-lin Rao; Liang Li; Guang Yang; Xue-mei Zhang (Journal of Zhejiang University-SCIENCE B, 2011)

Determination of Trace Deoxyribonucleic Acid by Using Fluorescein Isothiocyanate-Phenosafranine as a Double-Luminescent Phosphorescence Probe - Jia-Ming Liu; Xiao-Mei Huang; Zhen-Bo Liu; Fei-Ming Li; Li-Ping Lin; Xin-Xing Wang; Chang-Qing Lin; Ya-Hong Huang; Zhi-Ming Li; Shao-Qin Lin (Journal of Fluorescence, 2011)

Change of air quality and its impact on atmospheric visibility in central-western Pearl River Delta - Jun-Ming Wan; Mang Lin; Chuen-Yu Chan; Zhi-Sheng Zhang; Guenter Engling; Xue-Mei Wang; Iat-Neng Chan; Shi-Yu Li (Environmental Monitoring and Assessment, 2011)

Association between human papillomavirus and adenocarcinoma of rectum and recto-sigmoid junction: a cohort study of 10,612 women in Taiwan - Li-Chung Chuang; Hui-Chi Chen; San-Lin You; Ching-Yu Lin; Mei-Hung Pan; Yi-Chun Chou; Chang-Yao Hsieh; Chien-Jen Chen (Cancer Causes & Control, 2010)

Morphological changes of Fusarium oxysporum induced by CF66I, an antifungal compound from Burkholderia cepacia - Xin Li; Hui-Ying Yu; Yi-Feng Lin; Hong-Mei Teng; Lei Du; Guo-Gang Ma (Biotechnology Letters, 2010)

Altered Expression of the Small Guanosine Triphosphatase RhoA in Human Temporal Lobe Epilepsy - Jie Yuan; Lin-yuan Wang; Jin-mei Li; Ning-jia Cao; Liang Wang; Gui-bo Feng; Tao Xue; Yang Lu; Xue-feng Wang (Journal of Molecular Neuroscience, 2010)

The CAG repeat in SCA12 functions as a cis element to up-regulate PPP2R2B expression - Chih-Hsin Lin; Chiung-Mei Chen; Yi-Ting Hou; Yih-Ru Wu; Hsiu-Mei Hsieh-Li; Ming-Tsan Su; Guey-Jen Lee-Chen (Human Genetics, 2010)

Propranolol regulates cardiac transient outward potassium channel in rat myocardium via cAMP/PKA after short-term but not after long-term ischemia - Li Zhang; Chao-Qian Xu; Yuan Hong; Jia-Lin Zhang; Ying Liu; Mei Zhao; Yan-Xiu Cao; Yan-Jie Lu; Bao-Feng Yang; Hong-Li Shan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Sensitive Phosphorimetric Determination of Bumetanide in Human Urine with Its Inhibition Effect on the Formation of [Fe-morin] 3+ Complex - Li-Qing Zeng; Jia-Ming Liu; Fei-Ming Li; Xiao-Mei Huang; Li-Ping Lin; Xin-Xing Wang; Li-Hong Zhang; Chang-Qing Lin (Journal of Fluorescence, 2010)

Erratum to: Novel mutations in the connexin43 (GJA1) and GJA1 pseudogene may contribute to nonsyndromic hearing loss - Hui-Mei Hong; Jiann-Jou Yang; Jia-Ching Shieh; Mei-Ling Lin; Shuan-Yow Li (Human Genetics, 2010)

Hepsin activates prostasin and cleaves the extracellular domain of the epidermal growth factor receptor - Mengqian Chen; Li-Mei Chen; Chen-Yong Lin; Karl X. Chai (Molecular and Cellular Biochemistry, 2010)

Molecular Cloning and Characterization of a Chitinase-Homologous Gene from Mikania micrantha Infected by Cuscuta campestris - Dong-Mei Li; Christian Staehelin; Wen-Tian Wang; Shao-Lin Peng (Plant Molecular Biology Reporter, 2010)

Effects of 60-day NO2 fumigation on growth, oxidative stress and antioxidative response in Cinnamomum camphora seedlings - Zhuo-mei Chen; Ying-xu Chen; Guo-jian Du; Xi-lin Wu; Feng Li (Journal of Zhejiang University-SCIENCE B, 2010)

Biological impact of harmaline, ricinine and their combined effects with Bacillus thuringiensis on Spodoptera exigua (Lepidoptera: Noctuidae) - Muhammad Rizwan-ul-Haq; Qiong Bo Hu; Mei Ying Hu; Qing Shen Lin; Wan Li Zhang (Journal of Pest Science, 2009)

Human papillomavirus type-distribution in cervical cancer in China: the importance of HPV 16 and 18 - Wen Chen; Xun Zhang; Anco Molijn; David Jenkins; Ju-Fang Shi; Wim Quint; Johannes E. Schmidt; Ping Wang; Yu-Ling Liu; Lian-Kun Li; Hong Shi; Ji-Hong Liu; et al. (Cancer Causes & Control, 2009)

Memory deficits and neurochemical changes induced by C-reactive protein in rats: implication in Alzheimer’s disease - Huan-Bing Lin; Xue-Mei Yang; Tie-Jun Li; Yu-Fang Cheng; Han-Ting Zhang; Jiang-Ping Xu (Psychopharmacology, 2009)

Effects of cannabinoid CB1 receptor antagonist rimonabant in consolidation and reconsolidation of methamphetamine reward memory in mice - Lu-lu Yu; Xue-yi Wang; Mei Zhao; Yu Liu; Yan-qin Li; Fang-qiong Li; Xiaoyi Wang; Yan-xue Xue; Lin Lu (Psychopharmacology, 2009)

Effects of Neuregulin on Expression of MMP-9 and NSE in Brain of Ischemia/Reperfusion Rat - Qin Li; Rui Zhang; Yin-lin Ge; Yuan-wu Mei; Yun-liang Guo (Journal of Molecular Neuroscience, 2009)

Anthraquinone derivatives from Micromonospora rhodorangea - Chun-Mei Xue; Li Tian; Wen-Han Lin; Zhi-Wei Deng (Natural Product Research, 2009)

Digenic inheritance of non-syndromic deafness caused by mutations at the gap junction proteins Cx26 and Cx31 - Xue-Zhong Liu; Yongyi Yuan; Denise Yan; Emilie Hong Ding; Xiao Mei Ouyang; Yu Fei; Wenxue Tang; Huijun Yuan; Qing Chang; Li Lin Du; Xin Zhang; Guojian Wang; et al. (Human Genetics, 2009)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

Distribution and Accumulation of Copper and Cadmium in Soil–Rice System as Affected by Soil Amendments - Ping Li; Xing-xiang Wang; Tao-lin Zhang; Dong-mei Zhou; Yuan-qiu He (Water, Air, & Soil Pollution, 2009)

New BZLF1 sequence variations in EBV-associated undifferentiated nasopharyngeal carcinoma in southern China - Kun-Mei Ji; Chun-Lin Li; Guang Meng; Ai-Dong Han; Xu-Li Wu (Archives of Virology, 2008)

A high-density intervarietal map of the wheat genome enriched with markers derived from expressed sequence tags - Shulin Xue; Zhengzhi Zhang; Feng Lin; Zhongxin Kong; Yong Cao; Chunjun Li; Hongying Yi; Mingfeng Mei; Huilan Zhu; Jizhong Wu; Haibin Xu; Dongmei Zhao; et al. (Theoretical and Applied Genetics, 2008)

Juvenile Tilapia (Oreochromis mossambicus) Strive to Maintain Physiological Functions After Waterborne Copper Exposure - Su Mei Wu; Hui Ru Ding; Li-Yih Lin; Yu-Siang Lin (Archives of Environmental Contamination and Toxicology, 2008)

Evolutionary and functional study of the CDPK gene family in wheat (Triticum aestivum L.) - Ai-Li Li; Yuan-Fang Zhu; Xiao-Mei Tan; Xiang Wang; Bo Wei; Han-Zi Guo; Zeng-Lin Zhang; Xiao-Bo Chen; Guang-Yao Zhao; Xiu-Ying Kong; Ji-Zeng Jia; Long Mao (Plant Molecular Biology, 2008)

Solid Substrate–Room Temperature Phosphorimetry for the Determination of Trace Terbutaline Sulfate Based on Its Inhibition Oxidation of Rhodamine 6G by Sodium Periodate - Jia-Ming Liu; Fei Gao; Wen-Yan Gao; Li-Qing Zeng; Xiao-Mei Huang; Zhi-Ming Li; Xiu-Chai Huang; Wei-Nv Lin; Fang-Mei Wang; Chang-Ling Nie (Journal of Fluorescence, 2008)

Highly efficient Agrobacterium-mediated transformation of embryogenic cell suspensions of Musa acuminata cv. Mas (AA) via a liquid co-cultivation system - Xia Huang; Xue-Lin Huang; Wang Xiao; Jie-Tang Zhao; Xue-Mei Dai; Yun-Feng Chen; Xiao-Ju Li (Plant Cell Reports, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Genotypic Analysis of Multidrug-Resistant Mycobacterium tuberculosis Isolates Recovered From Central China - Shu-Lin Zhang; Hua Qi; Dun-Lian Qiu; Da-Xu Li; Jie Zhang; Chang-Mei Du; Guo-Bin Wang; Zhi-Rong Yang; Qun Sun (Biochemical Genetics, 2007)

Improved production of pristinamycin coupled with an adsorbent resin in fermentation by Streptomyces pristinaespiralis - Bo Jia; Zhi-Hua Jin; Yin-Lin Lei; Le-He Mei; Ning-Hui Li (Biotechnology Letters, 2006)

Protoplast Fusion between Geotrichum candidium and Phanerochaete chrysosporium to Produce Fusants for Corn Stover Fermentation - Yong Zhang; Shu-Mei Lin; Yu-Jing Zhu; Chang-Jiang Liu; Yan Dong; Fang-Fang Li; Gao-Feng Wu; Hai-Yan Wang; Jing-Hai Zhang (Biotechnology Letters, 2006)

Construction and characterization of a transformation-competent artificial chromosome (TAC) library ofZizania latifolia (Griseb.) - Fan Na Kong; Shao Mei Jiang; Li Xue Shi; Cheng Li Song; Min De Jin; Shao Lin Jiang; Manli Weng; Bin Wang (Plant Molecular Biology Reporter, 2006)

Effect of fenofibrate on the level of asymmetric dimethylarginine in individuals with hypertriglyceridemia - Tian-Lun Yang; Mei-Fang Chen; Xin Xia; Bai-Lin Luo; Yuan-Jian Li (European Journal of Clinical Pharmacology, 2006)

Identification of the Apoptosis Inhibitor Gene p49 of Spodoptera litura Multicapsid Nucleopolyhedrovirus - Mei Yu; Zhaofei Li; Kai Yang; Tiehao Lin; Yingxue Gong; Lijing Pan; Yi Pang (Virus Genes, 2005)

Characterizinig Precipitation Chemistry in Changhua, Central Taiwan Using Weather Conditions And Multivariate Analysis - Chuan-Te Chang; Teng-Chiu Lin; Mei-Li Hsueh (Water, Air, & Soil Pollution, 2005)

Fenofibrate decreases asymmetric dimethylarginine level in cultured endothelial cells by inhibiting NF-κB activity - Tian-Lun Yang; Mei-Fang Chen; Bai-Lin Luo; Qi-Ying Xie; Jun-Lin Jiang; Yuan-Jian Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2005)

Characterization of Usher syndrome type I gene mutations in an Usher syndrome patient population - Xiao Mei Ouyang; Denise Yan; Li Lin Du; J. Fielding. Hejtmancik; Samuel G. Jacobson; Walter E. Nance; An Ren Li; Simon Angeli; Muriel Kaiser; Valerie Newton; Steve D. M. Brown; Thomas Balkany; et al. (Human Genetics, 2005)

Hydrophilic excipients modulate the time lag of time-controlled disintegrating press-coated tablets - Shan-Yang Lin; Mei-Jane Li; Kung-Hsu Lin (AAPS PharmSciTech, 2004)

Formulation design of double-layer in the outer shell of dry-coated tablet to modulate lag time and time-controlled dissolution function: Studies on micronized ethylcellulose for dosage form design (VII) - Shan-Yang Lin; Kung-Hsu Lin; Mei-Jane Li (The AAPS Journal, 2004)

Rapid Detection and Characterization of Surfactin-Producing Bacillus subtilis and Closely Related Species Based on PCR - Feng-Chia Hsieh; Mei-Chen Li; Tsung-Chun Lin; Suey-Sheng Kao (Current Microbiology, 2004)

Effect of fenofibrate on LDL-induced endothelial dysfunction in rats - Tian-Lun Yang; Mei-Fang Chen; Bai-Ling Luo; Jing Yu; Jun-Lin Jiang; Yuan-Jian Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)

A G-Quadruplex Ligand 3,3′-Diethyloxadicarbocyanine Iodide Induces Mitochondrion-Mediated Apoptosis But Not Decrease of Telomerase Activity in Nasopharyngeal Carcinoma NPC-TW01 Cells - Chung-Pin Li; Jen-Hsin Huang; Ai-Chi Chang; Yi-Mei Hung; Chao-Hsiung Lin; Yee Chao; Shou-Dong Lee; Jacqueline Whang-Peng; Tze-Sing Huang (Pharmaceutical Research, 2004)

Diverse apoptotic pathways in enterovirus 71–infected cells - Shih-Cheng Chang; Jing-Yi Lin; Lily Yen-Cheng Lo; Mei-Ling Li; Shin-Ru Shih (Journal of NeuroVirology, 2004)

Identification of genes involved in the host response to enterovirus 71 infection - Shin-Ru Shih; Victor Stollar; Jing-Yi Lin; Shih-Cheng Chang; Guang-Wu Chen; Mei-Ling Li (Journal of NeuroVirology, 2004)

Evidence of a founder effect for the 235delC mutation of GJB2 (connexin26) in east Asians - Denise Yan; Hong-Joon Park; Xiao Mei Ouyang; Arti Pandya; Katsumi Doi; Raadnabazar Erdenetungalag; Li Lin Du; Naoki Matsushiro; Walter E. Nance; Andrew J. Griffith; Xue Zhong Liu (Human Genetics, 2003)

Conversion of an obligate autotrophic bacteria to heterotrophic growth: expression of a heterogeneous phosphofructokinase gene in the chemolithotroph Acidithiobacillus thiooxidans - Ke Li Tian; Jian Qun Lin; Xiang Mei Liu; Ying Liu; Chang Kai Zhang; Wang Ming Yan (Biotechnology Letters, 2003)

Risk of hepatocellular carcinoma and habits of alcohol drinking, betel quid chewing and cigarette smoking: a cohort of 2416 HBsAg-seropositive and 9421 HBsAg-seronegative male residents in Taiwan - Li-Yu Wang; San-Lin You; Sheng-Nan Lu; Hsi-Chang Ho; Mei-Hui Wu; Chien-An Sun; Hwai-I Yang; Chien-Jen Chen (Cancer Causes & Control, 2003)

Identification of estrogen-responsive genes in chick liver - Yunfeng Zhu; Mei Wang; Hong Lin; Zheng Li; Jia Luo (Cell and Tissue Research, 2001)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)